Multi-layer sintered ceramic body

Through the multi-layer sintered ceramic body structure, combined with polycrystalline YAG, alumina and zirconia layers, the corrosion resistance and mechanical strength problems of large-sized semiconductor processing chamber components are solved, high corrosion resistance and low dielectric loss in plasma environments are achieved, and the yield rate is improved.

CN116867752BActive Publication Date: 2025-07-04HERAEUS CONAMIC NORTH AMERICA LLC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202180083025.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2021-04-20
Filing Date
2021-12-17
Publication Date
2025-07-04
Estimated Expiration
2041-12-17

AI Technical Summary

Technical Problem

The prior art is difficult to provide corrosion-resistant, corrosion-resistant, low dielectric loss and high mechanical strength multi-layer sintered ceramic bodies, especially under large-size conditions, which leads to corrosion, erosion and particle contamination in plasma environments, affecting the yield rate.

Method used

A multi-layer sintered ceramic body structure is adopted, including a polycrystalline YAG layer, alumina and zirconia layer. By accurately controlling the difference in thermal expansion coefficient and density matching, an integral sintered ceramic body is formed to enhance interlayer adhesion and mechanical processing.

Benefits of technology

It provides high corrosion resistance, low dielectric loss and high mechanical strength to halogen process gas in plasma environment. It is suitable for large-size semiconductor processing chamber components, reducing particle contamination and improving yield.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116867752B_ABST
    Figure CN116867752B_ABST
Patent Text Reader

Abstract

The present disclosure relates to a multi-layer sintered ceramic body, the multi-layer sintered ceramic body comprising: at least one first layer comprising polycrystalline YAG, wherein the at least one first layer comprising polycrystalline YAG comprises pores, wherein the pores have a maximum size of 0.1 μm to 5 μm; at least one second layer comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia; and at least one third layer comprising at least one of YAG, alumina, and zirconia, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first layer, the at least one second layer, and the at least one third layer is 0 to 0.75×10-6 / °C as measured according to ASTM E228-17, and wherein the at least one first layer, the at least one second layer, and the at least one third layer form an integral multi-layer sintered ceramic body. A preparation method is also disclosed.
Need to check novelty before this filing date? Find Prior Art

Description

TECHNICAL FIELD

[0001] The present disclosure relates to corrosion-resistant multi-layer sintered ceramics and components formed therefrom, methods of producing the ceramics, and uses in semiconductor plasma processing chambers. BACKGROUND OF THE INVENTION

[0002] Semiconductor processing requires the use of halogen-based gases in combination with high electric and magnetic fields to create a plasma environment. This plasma environment is generated within a vacuum chamber for etching or depositing materials on a semiconductor substrate. These vacuum chambers include component parts such as disks or windows, gaskets, syringes, rings, and cylinders. During semiconductor plasma processing, the substrate is typically supported within the vacuum chamber by a substrate holder, as disclosed, for example, in US 5,262,029 and US 5,838,529. Process gases for creating the plasma processing environment can be supplied to the chamber through various gas supply systems. Some processes involve the use of radio frequency (RF) fields and introduce the process gas into the processing chamber while applying the RF field to the process gas to generate a plasma of the process gas. Ceramic materials used to form these components, especially for RF applications, need to have a low dielectric loss tangent of approximately 1×10 -3 and less. Higher dielectric losses cause overheating and hot spots within the component during use, resulting in process variability and yield loss. The use of components made from high-purity starting powders and manufacturing processes that maintain the initial purity will provide sintered ceramics that meet these low-loss requirements. The harsh plasma processing environment requires the use of highly corrosion- and erosion-resistant materials for the chamber components. These components have been formed from materials that provide corrosion and erosion resistance in a plasma environment and have been described, for example, in US5,798,016, US 5,911,852, US 6,123,791, and US 6,352,611. In addition, plasma processing chambers have been designed to include components such as disks, rings, and cylinders that confine the plasma to the wafer being processed. However, these parts used in plasma processing chambers are constantly under plasma attack and thus eventually corrode, erode, or accumulate contaminants and polymer deposits. Plasma etching and deposition conditions result in corrosion and roughening of the surfaces of the chamber parts that are exposed to the plasma. This corrosion contributes to wafer-level contamination by

[0003] releasing particles from the component surface into the chamber, resulting in yield loss of semiconductor devices.

[0004] To address this issue, chamber components typically have a surface layer that is corrosion and erosion resistant when exposed to process gases. The surface layer can be formed on a substrate or base that may have excellent mechanical, electrical, or other desirable properties. Corrosion resistant thin films or coatings, such as yttrium oxide or yttrium aluminum garnet (YAG), are known to be deposited on substrates formed of different materials. The corrosion resistant thin films or coatings are less expensive and stronger than most corrosion resistant materials. Such thin films or coatings have been made by several methods. Chemical vapor deposition has been used to deposit corrosion resistant thin films on substrates. However, due to internal film stresses, chemical vapor deposition is limited to relatively thin layers and there are typically small holes in the thin film. These internal film stresses result in poor interlayer adhesion and cause delamination, typically at the interface between the corrosion resistant film and the substrate, rendering these layers prone to cracking and flaking, thus leading to undesirable particulate contamination. Corrosion resistant coatings or thin films made by aerosol or plasma spraying techniques typically exhibit a high level of porosity of 3% to about 50% and a corresponding low density. In addition, these thin films produced by aerosol or spraying methods exhibit poor interfacial adhesion between the substrate material and the corrosion resistant layer, resulting in flaking and peeling and subsequent chamber contamination. Figure 1 Schematically shows delamination and cracking of a thin film deposited on a ceramic substrate.

[0005] Commercially available methods for depositing thin films on sintered substrates limit the film thickness to less than about 0.45 mm and smaller. Such film thicknesses typically have pores generated by non-uniformities in the underlying substrate, and the presence of the pores and the limited film thickness render the thin film surface layer prone to cracking, thus exposing the underlying substrate to corrosive process gases and particle generation during processing.

[0006] Other methods of forming corrosion resistant, high strength sintered bodies and / or components include laminating preformed thin films, applying pressure to the thin films to form a laminate, and then co-sintering the laminate. These methods typically use pressureless sintering, and the flatness of the sintered body depends on a close match of the sintering rates of the individual thin films. As Figure 2Schematically depicted, if the sintering rate of the top film (Film A) is greater than the sintering rate of the bottom film (Film B), the sintered ceramic laminate will have a concave curvature, and if the sintering rate of the bottom film (Film B) is greater than the sintering rate of the top film (Film A), the sintered ceramic laminate will have a convex curvature (both are configured with Film A of the top film facing upward). The change in the sintering rate generates residual stress in the sintered laminate, making it prone to breakage, microcracking, and subsequent particle release, especially at large sizes. Therefore, the materials selected for co-sintering are limited to those having the same or very similar sintering time, temperature, and duration curves as known to those skilled in the art. Additionally, these sintered laminates generally exhibit poor interfacial adhesion between the layers, resulting in peeling and flaking of the top layer, as well as low density, making them prone to breakage, delamination, and cracking.

[0007] Drilling and machining of features to form components from ceramic bodies may generate small, visually undetectable microcracks beneath (subsurface) and above the surface of these brittle, non-metallic materials. This surface and subsurface damage may lead to particle contamination due to corrosion or exfoliation and / or fracture of the brittle material. The machinability of components formed from brittle materials is becoming increasingly challenging to prevent particle release into the plasma processing chamber and / or prevent fracture and cracking (especially at large component sizes).

[0008] Therefore, there is a need in the art for a multi-layer sintered ceramic body for use in a plasma processing chamber, having a combined set of properties including plasma resistance, high interlayer adhesion, high mechanical strength, and improved machinability. Specifically, there is a need for large-sized (greater than 100 mm, e.g., from 100 mm to 625 mm), corrosion-resistant, high-strength sintered ceramic bodies to enable large-scale manufacturing of semiconductor devices. Summary of the Invention

[0009] To meet these and other needs, and in view of its objectives, the present disclosure provides embodiments of multi-layer sintered ceramic bodies and methods for preparing large multi-layer sintered ceramic bodies having improved mechanical, electrical, and thermal properties and that can be processed.

[0010] Sintered ceramic bodies (also referred to herein as multi-layer sintered ceramic bodies or corrosion-resistant bodies) and manufacturing methods are described herein. These ceramic bodies provide high corrosion resistance to chlorine- and fluorine-based process gases, low dielectric loss, high thermal conductivity, and enhanced machinability, and are thus desirable for use as components in semiconductor processing chambers utilizing halogen-based process gases. The ceramic bodies are particularly suitable for use as large chamber components having dimensions of 100 mm and greater.

[0011] Embodiment 1. A multi-layer sintered ceramic body, the multi-layer sintered ceramic body comprising: at least one first layer comprising polycrystalline YAG, wherein the at least one first layer comprising polycrystalline YAG comprises pores, wherein the pores have a maximum size of 0.1 μm to 5 μm; at least one second layer comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia; and at least one third layer comprising at least one selected from the group consisting of YAG, alumina, and zirconia, wherein the at least one second layer is disposed between the at least one first layer and the at least one third layer, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between any of the at least one first layer, the at least one second layer, and the at least one third layer is 0 to 0.75×10 -6 / °C, and wherein the at least one first layer, the at least one second layer, and the at least one third layer form an integral sintered ceramic body.

[0012] Embodiment 2. The multi-layer sintered ceramic body according to Embodiment 1, wherein the absolute value of the difference in coefficient of thermal expansion between any of the layers is 0 to 0.7×10-6 / °C.

[0013] Embodiment 3. The multi-layer sintered ceramic body according to any one of the preceding embodiments, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between any of the at least one first layer, the at least one second layer, and the at least one third layer is maintained over the entire temperature range of 200°C to 1400°C.

[0014] Embodiment 4. The multi-layer sintered ceramic body according to any one of the preceding embodiments, wherein the at least one first layer has a density of 4.47 g / cc to 4.56 g / cc as measured according to ASTM B962-17.

[0015] Embodiment 5. The multi-layer sintered ceramic body according to any one of the preceding embodiments, wherein the at least one first layer has a Sa of 0.0005 μm to 2 μm as measured according to ISO standard 25178-2-2012 or a Sz of 0.3 μm to 5 μm as measured according to ISO standard 25178-2-2012.

[0016] Embodiment 6. The multi-layer sintered ceramic body according to any one of the preceding embodiments, wherein the at least one second layer comprises zirconia in an amount of 10% to 30% by volume relative to the volume of the at least one second layer.

[0017] Embodiment 7. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the at least one second layer comprises partially stabilized zirconia.

[0018] Embodiment 8. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the multi-layer sintered ceramic body has a maximum size of 100 mm to about 625 mm.

[0019] Embodiment 9. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the at least one second layer comprises zirconia in an amount of about 16% by volume relative to the volume of the at least one second layer.

[0020] Embodiment 10. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein, as measured using XRD, SEM, and image processing methods, the at least one first layer comprises 98% to 99.9% polycrystalline YAG by volume, and the balance comprises at least one crystalline phase selected from the group consisting of alumina, yttria, YAM, YAP, and combinations thereof.

[0021] Embodiment 11. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the at least one first layer comprising polycrystalline YAG comprises pores, wherein, as measured using SEM, the pores have a maximum size of 0.1 μm to 1 μm.

[0022] Embodiment 12. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein, as measured using SEM, the at least one first layer comprising polycrystalline YAG has about 2 μm 2 / mm 2 to about 800 μm 2 / mm 2 of cumulative pore distribution.

[0023] Embodiment 13. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein, as measured using SEM, the at least one first layer comprising polycrystalline YAG has a porosity of 0.0005% to 2% by surface area percentage.

[0024] Embodiment 14. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein, as measured using the ICPMS method, the at least one first layer comprising polycrystalline YAG has a total impurity content of less than 5 ppm to 50 ppm relative to the mass of the at least one first layer.

[0025] Embodiment 15. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the at least one second layer has a density of 4.19 g / cc to 4.46 g / cc as measured according to ASTM B962-17.

[0026] Embodiment 16. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the at least one second layer contains 16 vol% of zirconia and has a density of about 4.32 g / cc as measured according to ASTM B962-17.

[0027] Embodiment 17. The multi-layer sintered ceramic body according to Embodiment 20, wherein the at least one second layer has a coefficient of thermal expansion (CTE) of 6.98×10 -6 / °C to 9.26×10 -6 / °C in the temperature range of 200°C to 1400°C as measured according to ASTM E228-17.

[0028] Embodiment 18. The multi-layer sintered ceramic body according to any one of Embodiments 19 to 21, wherein the at least one second layer has a dielectric loss of 7×10 -4 or less at 1 MHz frequency and ambient temperature as measured according to ASTM D150.

[0029] Embodiment 19. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the at least one second layer has a total impurity content of 5 ppm to 200 ppm relative to the mass of the at least one second layer as measured using the ICPMS method.

[0030] Embodiment 20. The multi-layer sintered ceramic body according to any one of the foregoing embodiments, wherein the at least one first layer has a thickness d1, the at least one second layer has a thickness d2, and the at least one third layer has a thickness d3, wherein the thickness d2 of the at least one second layer is 60% to 85% of the total thickness of the at least one first layer, the at least one second layer, and the at least one third layer.

[0031] Embodiment 21. A method for preparing a multi-layer sintered ceramic body, the method comprising the following steps: a) combining powders comprising yttrium oxide and alumina to prepare a first powder mixture; b) combining alumina powder with at least one of partially stabilized zirconia powder and stabilized zirconia powder to prepare a second powder mixture; c) combining alumina powder, yttrium oxide powder with at least one of unstabilized zirconia powder, partially stabilized zirconia powder and stabilized zirconia powder to prepare at least one third powder mixture; d) calcining at least one of the powder mixtures by applying heat to raise the temperature of at least one of the first powder mixture, the second powder mixture and the third powder mixture to a calcination temperature and maintaining the calcination temperature to effect calcination, thereby forming at least one of a first calcined powder mixture, a second calcined powder mixture and a third calcined powder mixture; e) separately disposing the first powder mixture, the second powder mixture and the third powder mixture in an internal volume defined by a tool set of a sintering device to form at least one layer of the first powder mixture, at least one layer of the second powder mixture and at least one layer of the third powder mixture, and creating a vacuum condition within the volume, wherein the tool set includes a die, the die including side walls, the side walls including an inner wall and an outer wall, wherein the inner wall has a diameter defining the internal volume capable of receiving the powder; and an upper punch and a lower punch operably coupled to the die, wherein each of the upper punch and the lower punch has an outer wall, the outer wall defining a diameter smaller than the diameter of the inner wall of the die, whereby when at least one of the upper punch and the lower punch moves within the internal volume of the die, a gap is defined between each of the upper punch and the lower punch and the inner wall of the die, wherein the gap is 10 μm to 100 μm wide; f) applying pressure and sintering the layers of the first powder mixture, the second powder mixture and the third powder mixture while heating to a sintering temperature to form the multi-layer sintered ceramic body, wherein at least one layer of the first powder mixture forms at least one first layer, at least one layer of the second powder mixture forms at least one second layer, and at least one layer of the third powder mixture forms at least one third layer; and g) lowering the temperature of the multi-layer sintered ceramic body, wherein at least one of the first layers comprises polycrystalline YAG, and at least one of the second layers comprises alumina, wherein the alumina comprises at least one of stabilized zirconia and partially stabilized zirconia, and at least one of the third layers comprises yttrium oxide, alumina and at least one of unstabilized zirconia, stabilized zirconia and partially stabilized zirconia, wherein at least one of the second layers is disposed between at least one of the first layers and at least one of the third layers.

[0032] Embodiment 22. The method according to embodiment 21, wherein the combined total impurity content of the first powder mixture, the second powder mixture, and the third powder mixture is 200 ppm or less as measured using ICPMS.

[0033] Embodiment 23. The method according to embodiment 21 or 22, wherein the second powder mixture comprises partially stabilized zirconia or stabilized zirconia in an amount of not less than 15% and not greater than 34% by weight relative to the weight of the second powder mixture.

[0034] Embodiment 24. The method according to any one of embodiments 21 to 23, wherein the first powder mixture, the second powder mixture, and the third powder mixture are crystalline as determined by an x-ray diffraction method.

[0035] Embodiment 25. The method according to any one of embodiments 21 to 24, wherein the second powder mixture comprises partially stabilized zirconia.

[0036] Embodiment 26. The method according to any one of embodiments 21 to 25, wherein the second powder mixture comprises yttria-partially stabilized zirconia.

[0037] Embodiment 27. The method according to any one of embodiments 21 to 26, wherein the second powder mixture comprises 3 mol% yttria-partially stabilized zirconia.

[0038] Embodiment 28. The method according to any one of embodiments 21 to 27, wherein the pressure applied to the at least one first layer, the at least one second layer, and the at least one third layer of the first powder mixture, the second powder mixture, and the third powder mixture is 5 MPa to 100 MPa.

[0039] Embodiment 29. The method according to any one of embodiments 21 to 28, wherein the temperature of the calcination step is 600 °C to 1200 °C.

[0040] Embodiment 30. The method according to any one of embodiments 21 to 29, wherein the sintering temperature is 1000 °C to 1700 °C.

[0041] Embodiment 31. The method according to any one of embodiments 21 to 30, the method further comprising the steps of: h) optionally annealing the multi-layer sintered ceramic body by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature; and i) lowering the temperature of the annealed multi-layer sintered ceramic body.

[0042] Embodiment 32. The method according to any one of Embodiments 21 to 31, the method further comprising the step of: j) machining the multi-layer sintered ceramic body to form multi-layer sintered ceramic components in the shape of windows, covers, dielectric windows, RF windows, rings, focusing rings, machining rings, deposition rings, nozzles, injectors, gas injectors, shower heads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESC), and positioning plates.

[0043] Embodiment 33. A multi-layer sintered ceramic body prepared by the method according to any one of Embodiments 21 to 32.

[0044] Embodiment 34. The multi-layer sintered ceramic body according to Embodiment 33, the multi-layer sintered ceramic body having a maximum dimension of 100 mm to about 625 mm.

[0045] The embodiments of the present invention can be used alone or in combination with each other. Description of the Drawings

[0046] When read in conjunction with the accompanying drawings, the present disclosure is best understood from the following detailed description. It should be emphasized that, according to convention, the various features of the drawings are not to scale. Instead, for clarity, the dimensions of the various features are arbitrarily enlarged or reduced. The following figures are included in the drawings:

[0047] Figure 1 Shows a lamination structure known in the art;

[0048] Figure 2 Shows a lamination structure known in the art;

[0049] Figure 3 Shows the CTE difference between at least one phase of YAG, spinel, and yttrium oxide / zirconium oxide (depicted as Y / Zr) compared to alumina within a certain temperature range;

[0050] Figure 4 Shows an overall multi-layer structure having mismatched CTE values between at least one first layer and at least one second layer;

[0051] Figure 5 depicts an SEM micrograph of the interface of a lamination structure known in the art;

[0052] Figure 6 Depicts an exemplary schematic diagram of a multi-layer sintered ceramic body according to an embodiment disclosed herein;

[0053] Figure 7 Shows the variation of the CTE of at least one second layer 102 containing zirconia in alumina according to an embodiment disclosed herein;

[0054] Figure 8 Shows the X-ray diffraction results of at least one second layer 102 according to an embodiment disclosed herein;

[0055] Figure 9 a), Figure 9 b) and Figure 9c ) depict the variation of the CTE of a multi-layer sintered ceramic body according to an embodiment disclosed herein, the multi-layer sintered ceramic body comprising a composition of at least one first layer containing YAG and at least one second layer;

[0056] Figure 10 Depicts the yttrium oxide / aluminum oxide binary phase diagram;

[0057] Figure 11 a) depicts an SEM micrograph of the surface of at least one first layer 100 containing polycrystalline YAG obtained using the backscattered detection (BSD) method, and Figure 11 b) depicts an SEM image of the same area from the surface after threshold conversion to reveal porosity and alumina phase according to an embodiment disclosed herein;

[0058] Figure 12 a) depicts Figure 11 The topographical SEM micrograph of the surface of at least one first layer containing YAG (using the topographical imaging method) and Figure 12 b) depicts the topographical SEM image of the same area from the surface after threshold conversion to reveal porosity and alumina phase according to an embodiment disclosed herein;

[0059] Figure 13 Shows the X-ray diffraction results of at least one first layer 100 containing YAG according to an embodiment disclosed herein;

[0060] Figure 14 Shows the relationship between the pore area and pore diameter of the overall multi-layer sintered ceramic body, the overall multi-layer sintered ceramic body comprising: at least one first layer 100 containing YAG and at least one second layer 102 containing about 16 vol% zirconia;

[0061] Figure 15 Shows the relationship between the cumulative pore area and pore diameter of a multi-layer sintered ceramic body according to an embodiment disclosed herein, the multi-layer sintered ceramic body comprising: at least one first layer 100 containing YAG and at least one second layer 102 containing about 16 vol% zirconia and the balance being alumina;

[0062] Figure 16 a) depicts an SEM micrograph of the surface of at least one layer containing YAG of the multi-layer sintered ceramic body, and Figure 16 b) shows atFigure 14 and Figure 15 Total % of surface area with porosity within the 7 images of

[0063] Figure 17 .

[0063] Figure 17 a), Figure 17 b) and Figure 17 c) depict the variation of the CTE of a multi - layer sintered ceramic body according to an embodiment disclosed herein, the multi - layer sintered ceramic body comprising at least one first layer 100 containing spinel and at least one second layer 102.

[0064] Figure 18 Shows the x - ray diffraction results of a calcined powder mixture of a composition forming at least one first layer 100 containing magnesium aluminate spinel;

[0065] Figure 19 Depicts an SEM micrograph of the surface of at least one first layer 100 containing magnesium aluminate spinel according to an embodiment disclosed herein;

[0066] Figure 20 a), Figure 20 b) and Figure 20 c) depict the variation of the CTE of an overall multi - layer sintered ceramic body according to an embodiment disclosed herein, the overall multi - layer sintered ceramic body comprising an embodiment of at least one first layer 100 and at least one second layer 102, the at least one first layer comprising at least one crystalline phase of a ceramic material containing yttrium oxide and zirconium oxide.

[0067] Figure 21 a) shows the non - linear interface 104 of the overall multi - layer sintered ceramic body, and Figure 21 b) depicts a 500x SEM image of the surface of at least one first layer 100 according to an embodiment disclosed herein, the at least one first layer comprising approximately 20 mol% zirconium oxide and approximately 80 mol% yttrium oxide;

[0068] Figure 22 a) depicts a schematic diagram of a multi - layer sintered ceramic body 98, and Figure 22 b) shows an enlarged schematic diagram showing the non - linear interface 104 and the second interface 105 according to an embodiment disclosed herein;

[0069] Figure 23 a) shows the curvature (T) and Figure 23 b) depicts the average interface line (IL) characterizing the non - linear interface 104 according to an embodiment disclosed herein;

[0070] Figure 24 a) depicts a 5000x SEM micrograph of the non - linear interface 104 of a multi - layer sintered ceramic body, and Figure 24b) shows the measurement results of the curvature (T) of the non-linear interface 104 according to the embodiments disclosed herein;

[0071] Figure 25 a) shows the number of grains per unit interface length (in μm) of the non-linear interface 104, and Figure 25 b) depicts the curvature (T) of the non-linear interface 104 according to the embodiments disclosed herein;

[0072] Figure 26 a) and Figure 26 b) show SEM micrographs at 1000x (and 5000x) of at least a third layer of the multi-layer sintered ceramic body as disclosed herein;

[0073] Figure 27 a), Figure 27 b) and Figure 27 c) show exemplary cross-sectional views of embodiments of the multi-layer sintered ceramic body as disclosed herein before and after a machining process for forming a multi-layer sintered component including through-holes 112 as disclosed herein;

[0074] Figure 28 Depicts a schematic diagram of a tool set of a pressure-assisted sintering device according to the embodiments disclosed herein;

[0075] Figure 29 Shows a cross-sectional view of an SPS sintering device having a tool set located in a vacuum chamber (not shown), the SPS sintering device having a simple arrangement for sintering ceramic materials;

[0076] Figure 30A Shows Figure 29 an embodiment of, showing a foil layer;

[0077] Figure 30B Shows Figure 29 an alternative embodiment of, showing two foil layers;

[0078] Figure 30C Shows Figure 29 another alternative embodiment of, showing three foil layers;

[0079] Figure 31A and Figure 31B is Figure 29 a top view of the SPS sintering device of;

[0080] Figure 32 is a graph depicting the radial variation of the average coefficient of thermal expansion (CTE) of graphite materials A and B at 1200 °C; and

[0081] Figures 33 to 34Depicts semiconductor plasma processing systems 9500 and 9600. DETAILED DESCRIPTION

[0082] The following detailed description assumes that the present disclosure is implemented within equipment (such as an etching chamber or a deposition chamber) necessary as part of a device fabricated on a semiconductor wafer substrate. However, the present invention is not limited thereto. The workpiece can have various shapes, sizes, and materials. In addition to semiconductor wafer processing, other workpieces that can utilize embodiments of the present invention include various articles such as fine feature size inorganic circuit boards, magnetic recording media, magnetic recording sensors, mirrors, optical elements, micro-mechanical devices, etc.

[0083] Corrosion-resistant ceramics used as components in semiconductor reaction chambers are described herein, particularly multi-layer sintered ceramic bodies having more than one layer and their preparation. Semiconductor etching and deposition reactors require reactor components having surfaces that are highly resistant to the corrosion and erosion of halogen-containing plasmas necessary for processing. These surfaces preferably minimize the release of particles from the component surface into the chamber. Additionally, the chamber components must have sufficient mechanical strength for handling and use, especially at large (e.g., diameter > 100 mm) component sizes. Sintered ceramic bodies can be machined into sintered components and, therefore, must be able to be handled and machined at large sizes while providing corrosion resistance, low particle generation, and high mechanical strength. The sintered ceramic bodies disclosed herein comprise at least one first layer having at least one polycrystalline ceramic material, the at least one polycrystalline ceramic material comprising YAG (yttrium aluminum garnet or yttrium aluminate) of the formula Y3Al5O 12 having a garnet structure (having a composition comprising a ratio of about 3:5 of yttrium oxide and alumina), spinel (magnesium aluminate spinel, MgAl2O4), and yttrium oxide and zirconia, wherein zirconia is present in the yttrium oxide in an amount of not less than 10 mol% ZrO2 and not greater than 25 mol% ZrO2. These materials have excellent corrosion and erosion resistance. The use of these materials results in semiconductor plasma processing chamber components having surfaces that provide improved plasma tolerance compared to other materials when subjected to halogen-based plasma etching and deposition conditions.

[0084] In one embodiment, a multi-layer sintered ceramic body is described herein, the multi-layer sintered ceramic body comprising: at least one first layer comprising a polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium oxide and zirconium oxide, wherein zirconium oxide is present in an amount of not less than 10 mol% and not more than 25 mol%; at least one second layer comprising alumina and zirconium oxide, wherein the zirconium oxide comprises at least one of stabilized zirconia and partially stabilized zirconia; and at least one third layer comprising at least one selected from the group consisting of YAG, alumina, and zirconium oxide, wherein at least one second layer is disposed between at least one first layer and at least one third layer, and wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between at least one first layer, at least one second layer, and at least one third layer is from 0 to 0.75×10 -6 / °C, and wherein at least one first layer, at least one second layer, and at least one third layer form an integral sintered ceramic body.

[0085] As the semiconductor manufacturing industry moves towards larger semiconductor substrate diameters, chamber components of larger sizes (diameter approximately 100 mm to about 625 mm) are required. Thus, the multi-layer sintered ceramic body as disclosed herein must have sufficient strength during use and handling to avoid breakage. The multi-layer sintered ceramic body as disclosed herein also comprises at least one second layer containing zirconium oxide and alumina, the at least one second layer having high mechanical strength and also having the preferred electrical and material properties as disclosed below.

[0086] Reference Figure 6 , a multi-layer sintered ceramic body 98 is disclosed, the multi-layer sintered ceramic body having at least one first layer 100 which is the outermost layer and has a plasma-facing surface 106, the plasma-facing surface providing resistance to corrosion and erosion by halogen-based plasmas and ion bombardment, a controlled porosity distribution at small pore diameters, high purity, high density, and low surface roughness. Preferably, at least one first layer 100 has a coefficient of thermal expansion (CTE) such that, as measured according to ASTM E228-17, the amount by which the CTE differs from that of at least one second layer 102 and at least one third layer 103 is from 0 to 0.75×10 -6 / °C (in absolute value). In some embodiments, the CTE of at least one first layer and at least one second layer is substantially the same. Further, the multi-layer sintered ceramic body 98 according to an embodiment of the present disclosure includes a non-linear interface 104 defined by at least one first layer 100 and at least one second layer 102 (see Figure 21 ), whereby the non-linear interface 104 can provide enhanced adhesion between these layers.

[0087] Embodiments of the present disclosure also relate to a specific multi-layer sintered ceramic body that includes at least one second layer 102 having a composition range that includes zirconia and alumina. Within the composition range of yttria and zirconia, the at least one second layer 102 exhibits high mechanical strength, enhanced hardness (Young's modulus), high thermal conductivity, low dielectric loss, high dielectric constant, and a CTE that matches the coefficient of thermal expansion (CTE) of the at least one first layer 100 and the at least one third layer 103 within the disclosed range.

[0088] The at least one third layer 103 includes multiple phases of at least one of YAG, alumina, and zirconia, whereby the at least one third layer provides improved machinability. The at least one third layer 103 can provide a sintering curve similar to that of the at least one first layer 100, thereby providing greater uniformity within these layers during sintering. The CTE of the at least one third layer 103 matches the CTE of the at least one first layer and the at least one second layer within the range disclosed herein.

[0089] The at least one first layer, the at least one second layer, and the at least one third layer having CTE values within the range disclosed herein provide for the preparation of large-sized (100 mm to about 625 mm) monolithic multi-layer sintered bodies and chamber components fabricated therefrom. Additionally, methods for preparing such corrosion-resistant multi-layer sintered ceramics and their use in plasma processing chambers are disclosed.

[0090] Definitions - As used herein, the following terms are defined as follows: "alumina" is understood to be alumina containing Al2O3, "zirconia" is understood to be zirconia containing ZrO2, and "yttria" is understood to be yttria containing Y2O3.

[0091] As used herein, the terms "semiconductor wafer", "wafer", "substrate", and "wafer substrate" may be used interchangeably. Wafers or substrates used in the semiconductor device industry typically have a diameter of 200 mm, or 300 mm, or 450 mm.

[0092] As used herein, the term "sintered ceramic body" is synonymous with "multi-layer sintered ceramic body", "multi-layer corrosion-resistant ceramic", "corrosion-resistant body", "sintered ceramic", "multi-layer monolith", and like terms, and refers to an integral, one-piece sintered ceramic article formed by co-compacting more than one powder mixture by applying pressure and heat, which results in an integral, dense multi-layer sintered ceramic body. The integral multi-layer sintered ceramic body can be machined into an integral, multi-layer sintered ceramic component that can be used as a chamber component in plasma processing applications. Thus, the multi-layer sintered ceramic body disclosed herein is not formed by laminating pre-formed layers, i.e., the multi-layer sintered ceramic body disclosed herein is not a laminated material.

[0093] As used herein, the terms "co-compacting" or "co-compaction" refer to a process in which at least two loose powder materials are placed within a mold and subjected to pressure to form a powder compact. The powder compact does not contain binders, dispersants, or other similar organic materials required to form a green body, shaped body, or tape common in the art.

[0094] "Integral" or "one-piece" means a single piece or single unitary part that is complete in itself without additional parts, i.e., the part is a single monolithic piece formed as a unit with another part.

[0095] As used in this document, the term "substantially" is a descriptive term denoting approximation and means "to a considerable degree" or "to a large extent but not completely the specified", and is intended to avoid strict numerical boundaries for specified parameters.

[0096] As used herein, the terms "sintered ceramic component" or "multi-layer sintered ceramic component" refer to a sintered ceramic body, multi-layer sintered ceramic body, or corrosion-resistant ceramic after a machining step of forming the ceramic into a desired shape for a semiconductor processing chamber as disclosed herein.

[0097] As used herein, the term "powder mixture" means more than one starting powder that is mixed together prior to the sintering process and that, after the sintering step, forms at least one layer of a multi-layer sintered ceramic body therefrom.

[0098] When applied to the heat treatment of ceramics, the term "annealing" is to be understood herein to mean heat treatment of the disclosed multi-layer sintered ceramic body in air to relieve stress and / or normalize the stoichiometry.

[0099] As used herein, the term "tool set" is a set of tools that can include at least a mold and at least two punches. When fully assembled, the tool set defines a volume for placement of the disclosed powder mixture.

[0100] As used herein, the term "phase" is to be understood to mean different crystalline regions, portions, or layers of a sintered ceramic body having a specific crystal structure.

[0101] As used herein, "solid solution" is defined as a mixture of different elements having the same lattice structure. The mixture within the lattice can be substitutional, where atoms of one starting crystal replace atoms of another starting crystal, or interstitial, where atoms occupy positions normally vacant within the lattice.

[0102] As used herein, the term "nanopowder" is intended to encompass those powders having a specific surface area greater than 20 m 2 / g.

[0103] As used herein, the term "phase" is understood to mean different crystalline regions, portions or layers of a sintered ceramic body having a specific crystal structure.

[0104] As used herein, the term "layer" is understood to mean a material of a certain thickness, typically one of several. The material can be, for example, a ceramic powder, a powder mixture, a calcined powder mixture or a sintered region or sintered portion.

[0105] As used herein, "ambient temperature" refers to a temperature range of about 22 °C to 25 °C.

[0106] As used herein, the term "purity" means the absence of various contaminants in a) the starting materials from which a powder mixture can be formed, b) the processed powder mixture (or calcined powder mixture), and c) the multi-layer sintered ceramic body or component as disclosed herein. Higher purity (close to 100%) indicates a material that is substantially free of contaminants or impurities, or has a very low amount of contaminants or impurities, and that materially contains the material composition present in the disclosed starting powder.

[0107] As used herein, the term "impurity" refers to those compounds / contaminants present in the powder or sintered ceramic other than the intended compound itself (starting powders of magnesium oxide, aluminum oxide, yttrium oxide and zirconium oxide, stable compounds (where applicable), powder mixtures and ceramics formed therefrom). Impurities can be present in the starting powder, powder mixture, processed powder mixture and sintered ceramic body. The impurity content of the powders, powder mixtures and the first and second layers of the sintered body as disclosed herein is determined using the ICPMS method.

[0108] As used herein, the term "dopant" is a substance added to the bulk material to impart desired properties (e.g., altering electrical properties) in the ceramic material. Generally, if used, the dopant is present at a low concentration, i.e., > 0.002 wt% to < 0.05 wt%.

[0109] Impurities differ from dopants in that dopants, as defined herein, are those compounds intentionally added to the starting powder or powder mixture to achieve certain electrical, mechanical, optical or other properties such as grain size modification in the multi-layer sintered ceramic body. The term "dopant" as used herein does not include Hf and Y included in the zirconium oxide starting material, provided they can remain in the multi-layer sintered ceramic body.

[0110] As used herein, the term "sintering aid" refers to a compound that enhances densification during sintering and thus reduces porosity, such as silica (SiO2), lithium oxide (Li2O), lithium fluoride (LiF), magnesium oxide (MgO), and / or calcium oxide (CaO). Hf and Y present in the starting powder and the extent to which they remain in the sintered ceramic do not constitute sintering aids, impurities, or dopants as defined herein.

[0111] As used herein, the terms "about" and "approximate" when used in connection with a numerical value or characteristic disclosed herein allow for a variance of plus or minus 10%.

[0112] As used herein, the term "coefficient of thermal expansion (CTE)" is measured in accordance with ASTM E228-17 in the temperature range from 25°C to 200°C to 25°C to 1400°C, preferably from 25°C to 1200°C, more preferably from 25°C to 1000°C, more preferably from 25°C to 800°C, more preferably from 25°C to 600°C, more preferably from 25°C to 400°C, more preferably from 25°C to 200°C. CTE describes how the size of an object changes with temperature. Specifically, CTE measures the fractional change in size per degree change in temperature at constant pressure. To determine the coefficient at a given temperature, the volume of the material is measured at a reference temperature and the volume of the material is measured at the temperature at which it is desired to determine the CTE. Thereafter, based on the difference in volume and temperature, the fractional change is determined.

[0113] All CTE values of the present disclosure are determined in accordance with ASTM E228-17. In particular, the reference temperature used is ambient temperature, especially 25°C. Thus, if the CTE at a given temperature (i.e., 200°C) is disclosed, the CTE has been determined by comparing the volume (or linear expansion of an isotropic material) at that temperature with the volume (or linear expansion of an isotropic material) at ambient temperature (especially 25°C). In any case where there is a contradiction with respect to CTE, ASTM E228-17 shall always be the dominant disclosure. In the disclosed examples, the CTE is measured using a vertical dilatometer, specifically model L75 from Linseis Messgeraete GmbH, Selb, Germany.

[0114] During the processing of semiconductor devices, corrosion-resistant chamber components are used in etching and / or deposition chambers and are exposed to harsh corrosive and erosive environments that cause particle release into the chamber, resulting in yield loss due to wafer-level contamination. The multi-layer sintered ceramic bodies and related components fabricated therefrom disclosed herein provide improved plasma tolerance, thermal conductivity, and enhanced mechanical strength for use in semiconductor processing chambers through specific material properties and characteristics described hereinafter.

[0115] According to one embodiment, a multi-layer sintered ceramic body is disclosed herein, the multi-layer sintered ceramic body comprising at least one first layer, the at least one first layer comprising a polycrystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium oxide and zirconium oxide, wherein zirconium oxide is present in an amount of not less than 10 mol% and not more than 25 mol%; at least one second layer comprising alumina, wherein the alumina comprises at least one of stabilized zirconia (SZ) and partially stabilized zirconia (PSZ); and at least one third layer, the at least one third layer comprising multiple phases of at least YAG, alumina, and zirconium oxide, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first layer, the at least one second layer, and the at least one third layer is from 0 to 0.75×10-6 / °C (as measured according to ASTM E228-17), and wherein the at least one first layer, the at least one second layer, and the at least one third layer form an integral multi-layer sintered ceramic body.

[0116] In one embodiment, these layers exhibit a certain absolute value of the CTE difference between at least one first layer, at least one second layer, and at least one third layer, as measured according to ASTM E228-17 in a temperature range from 25 °C to 1700 °C or in a temperature range from 200 °C to 1400 °C, the amount of this absolute value being from 0 to 0.75×10-6 / °C, preferably from 0 to 0.7×10-6 / °C, preferably from 0 to 0.6×10-6 / °C, preferably from 0 to 0.5×10-6 / °C, preferably from 0 to 0.45×10-6 / °C, preferably from 0 to 0.4×10-6 / °C, preferably from 0 to 0.35×10-6 / °C, preferably from 0 to 0.3×10-6 / °C, preferably from 0 to 0.25×10-6 / °C, preferably from 0 to 0.2×10-6 / °C, preferably from 0 to 0.15×10-6 / °C, preferably from 0 to 0.1×10-6 / °C, preferably from 0 to 0.08×10-6 / °C, preferably from 0 to 0.04×10-6 / °C, and preferably from 0 to 0.02×10-6 / °C. These ranges of the absolute value of the CTE difference between at least one first layer, at least one second layer, and at least one third layer correspond to a CTE difference of at least about 10% and less, preferably 9% and less, preferably 8% and less, preferably 6% and less, preferably 4% and less, preferably 3% and less, preferably 2.5% and less, preferably 2% and less, preferably 1.5% and less, preferably 1% and less, preferably 0.5% and less, and preferably 0.25% and less (as measured relative to 100 of at least one first layer) between any one of at least one first layer, at least one second layer, and at least one third layer. When the CTE between at least one first layer 100, at least one second layer 102, and at least one third layer 103 varies within these ranges, and more specifically when the CTE between at least one first layer, at least one second layer, and at least one third layer varies within these ranges in a temperature range from ambient temperature to about 1700 °C (or as depicted in the figures, from about 200 °C to about 1400 °C) as measured according to ASTM E228-17, a pressure-assisted method as disclosed herein can be used to form an integral multi-layer sintered ceramic body, particularly an integral multi-layer sintered ceramic body having large (>100 mm to about 625 mm) dimensions, high strength, and high interlayer adhesion. Due to the isotropic properties of the ceramic material comprising at least one first layer, at least one second layer, and at least one third layer as disclosed herein, the coefficient of thermal expansion (CTE) as used herein can refer interchangeably to linear or volumetric CTE. Preferably, the CTE difference between at least one first layer, at least one second layer, and at least one third layer is minimized to reduce the interfacial stress between the layers.A CTE difference between at least one first layer, at least one second layer, and at least one third layer greater than the CTE difference disclosed herein can cause fracture and / or cracking of the multi-layer sintered ceramic body.

[0117] Reference Figure 6 , depicts a schematic diagram of a multi-layer sintered ceramic body 98 as disclosed herein, where 100 represents at least one first layer having a thickness d1, 102 shows at least one second layer 102 having a thickness d2, and 103 shows at least one third layer 103 having a thickness d3. The multi-layer sintered ceramic body 98 produced according to the method disclosed herein (depicting at least one first layer 100, where the first layer has a thickness; a second layer 102, where the second layer has a thickness; and a third layer 103, where the third layer has a thickness) preferably has a thickness of the second layer 102 that is 70% to 95%, preferably 70% to 90%, preferably 70% to 85%, preferably 80% to 95%, preferably 85% to 95% of the total thickness of the three layers 100, 102, and 103.

[0118] At least one second layer 102 provides mechanical strength as well as electrical properties of a low dielectric loss tangent (less than 7×10-4 at 1 MHz) and a high dielectric constant of about 12. Thus, in some embodiments, it may be preferred to maximize the thickness d2. To provide a combination of high mechanical strength and stiffness with machinability to form a sintered ceramic component from the multi-layer sintered body as disclosed herein, such as Figure 6The thickness d2 of at least one second layer 102 depicted therein is preferably greater than each of the thickness d1 of at least one first layer 100 and / or the thickness d3 of at least one third layer 103. The thickness d1 of at least one first layer 100 and / or the thickness d3 of at least one third layer can each be from 0.5 mm to 5 mm, preferably from 0.5 mm to 4 mm, preferably from 0.5 mm to 3 mm, preferably from 0.5 mm to 2 mm, preferably from 0.5 mm to 1 mm, preferably from 0.75 mm to 5 mm, preferably from 0.75 mm to 3 mm, preferably from 1 mm to 5 mm, preferably from 1 mm to 4 mm, preferably from 1 mm to 3 mm. The total thickness (d1 + d2 + d3) of the multi-layer sintered ceramic body as disclosed herein can be from about 5 mm to about 50 mm, preferably from about 5 mm to about 40 mm, preferably from about 5 mm to about 35 mm, preferably from about 5 mm to about 33 mm, preferably from about 5 mm to about 30 mm, preferably from about 8 mm to about 25 mm, and preferably from about 10 mm to about 20 mm. In certain embodiments where it may be desirable to minimize the thickness d1 of at least one first layer 100 and / or the thickness (d3) of at least one third layer 103, the multi-layer sintered ceramic body can be machined after sintering and / or after annealing to reduce the thickness d1 and / or d3 of layers 100 and / or 103, thereby changing the electrical properties such as dielectric loss, dielectric constant, thermal conductivity or other properties of the multi-layer sintered ceramic body 98 or a component formed therefrom.

[0119] The multi-layer sintered ceramic body disclosed herein has at least one first layer 100, where at least one first layer has a thickness; at least one second layer 102, where at least one second layer has a thickness; and at least one third layer 103, where at least one third layer has a thickness, wherein the thickness of at least one second layer 102 is 70% to 95% of the total thickness of the three layers 100, 102 and 103, preferably 70% to 90%, preferably 70% to 85%, preferably 80% to 95%, preferably 85% to 95%.

[0120] In certain embodiments, the thickness d2 of at least one second layer is 60% to 85%, preferably 60% to 80%, preferably 60% to 75%, preferably 60% to 70%, preferably 70% to 85%, preferably 75% to 85%, preferably 70% to 80%, preferably 70% to 75% of the total thickness (d1 + d2 + d3) of at least one first layer, at least one second layer, and at least one third layer. At least one first layer having a thickness d1 includes a plasma-facing surface 106 that provides corrosion resistance and erosion resistance to a halogen-based plasma. In an embodiment, the thickness d1 of at least one first layer is 0.75% to 20%, preferably 0.75% to 15%, preferably 0.75% to 12%, preferably 3% to 20%, preferably 5% to 20%, preferably 3% to 15%, preferably 5% to 12% of the total thickness (d1 + d2 + d3) of at least one first layer, at least one second layer, and at least one third layer.

[0121] Stresses generated by layers comprising materials having mismatched CTEs can affect the mechanical strength and integrity of a multi-layer sintered ceramic body. Thus, if the difference in the absolute value of the CTE between at least one first layer 100, at least one second layer 102, and at least one third layer 103 of a sintered ceramic body is too large, then during performance of the steps of the methods disclosed herein, at least one layer of the multi-layer sintered ceramic body may crack, warp, and / or fracture. Such CTE differences are important at all process temperatures, especially at elevated temperatures such as those experienced during sintering, annealing, and during cooling, where differences in CTE can generate significant interfacial stresses between the layers of the sintered body. Thus, in order to form a multi-layer monolithic sintered ceramic body having high mechanical strength, high adhesion strength between layers, and sufficient processability (without cracking or breakage), the CTE differences between at least one first layer 100, at least one second layer 102, and at least one third layer 103 of the multi-layer sintered ceramic body are preferably within the disclosed ranges and further matched as closely as possible. In a preferred embodiment, at least one first layer, at least one second layer, and at least one third layer may have corresponding CTEs that are the same or substantially the same in absolute value in the temperature range from ambient temperature (or about 200 °C as disclosed in the figures) to about 1700 °C (or at least up to 1400 °C as depicted in the figures) according to the methods disclosed. As used herein, the term "CTE matching" refers to a combination of at least one first layer 100, at least one second layer 102, and at least one third layer, the difference in whose CTEs is within the disclosed preferred range (absolute value from 0 to about 0.75×10 -6 / °C). According to one embodiment, at least one first layer 100 may comprise a polycrystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium oxide and zirconium oxide, wherein zirconium oxide is present in an amount of not less than 10 mol% ZrO2 and not more than 25 mol% ZrO2, whereby at least one first layer 100 is CTE-matched with at least one second layer 102 (comprising alumina and at least one of stabilized zirconia and partially stabilized zirconia) and at least one third layer 103 (comprising a combination of at least one first layer and at least one second layer) to form an integral multi-layer sintered ceramic body. In percentages, the combination of at least one first layer 100, at least one second layer 102, and at least one third layer 103 may have CTE values that match each other (in the temperature range disclosed herein) with a percentage of about 10% and less, preferably 9% and less, preferably 8% and less, preferably 6% and less, preferably 4% and less, preferably 3% and less, preferably 2.5% and less, preferably 2% and less, preferably 1.5% and less, preferably 1% and less, preferably 0.5% and less, and preferably 0.25% and less (as measured relative to at least one first layer 100).

[0122] It may be based on as Figure 7 depicted volume % of zirconia in alumina to select the composition of at least one second layer 102 to produce a specific CTE characteristic, Figure 7 shows exemplary CTE results of at least one second layer 102 as disclosed herein, wherein the second layer comprises zirconia in an amount of 10 volume % to 30 volume % and the balance comprises Al2O3. The amount of zirconia in at least one second layer 102 and the resulting CTE value are preferably CTE-matched with at least one first layer and at least one third layer in the temperature range corresponding to the method from ambient temperature (or 200 °C according to the drawing) to about 1700 °C (or 1400 °C according to the drawing) to fabricate the integral multi-layer sintered body as disclosed herein.

[0123] According to one embodiment, at least one second layer 102 comprises alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia, and the amount thereof by volume is 5% to 30% of the volume of the at least one second layer, preferably 5% to 25%, preferably 5% to 20%, preferably 5% to 16%, preferably 10% to 30%, preferably 16% to 30%, preferably 10% to 25%, and preferably 15% to 20% (and the balance comprises Al2O3). These volume percentages of the at least one second layer 102 correspond to weight percentages of a second powder mixture comprising zirconia (and the balance being alumina) of from about 7% to about 40%, preferably from about 7% to about 35%, preferably from about 7% to about 28%, preferably from about 7% to about 23%, preferably from about 15% to about 40%, preferably from about 23% to about 40%, preferably from about 15% to about 34%, preferably from about 21% to about 28%, and preferably about 23%. In this composition and temperature range, the coefficient of thermal expansion (CTE) of the at least one second layer 102 can vary between at least one second layer 102 comprising 5 vol% zirconia with a CTE measured at 200 °C of 6.8×10-6 / °C and at least one second layer 102 comprising about 30 vol% zirconia and having a CTE measured at 1400 °C of about 9.75×10-6 / °C. The volume amount of at least one of stabilized zirconia or partially stabilized zirconia in the at least one second layer 102 provides the ability to change the CTE to be the same or substantially the same as the CTE of the at least one first layer 100 and the at least one third layer 103 and within the disclosed CTE matching range.

[0124] Reference Figure 7 , using dilatometry performed according to ASTM E228-17 on compositions of 10 vol%, 16 vol% and 20 vol% ZrO2 (and the balance being alumina), experimental data is used to measure the coefficient of thermal expansion (CTE) of the at least one second layer 102. As measured according to ASTM E228-17, an exemplary at least one second layer 102 comprising about 16 vol% zirconia was measured to have a coefficient of thermal expansion (CTE) of 6.98×10 -6 / °C to 9.26×10 -6 / °C in the temperature range from about 200 °C to about 1400 °C. As Figure 8 shown by the x-ray diffraction results of, the at least one second layer 102 comprises at least two separate crystalline phases of zirconia and alumina (referred to herein as a composite oxide or particulate composite material or zirconia toughened alumina ZTA). Thus, CTE values are calculated for 5 vol%, 25 vol% and 30 vol% zirconia using the volume mixing rule known to those skilled in the art (as Figure 7as depicted). The CTE value of at least one second layer (not shown) containing 5 vol% zirconia typically lies between that of pure alumina and that of at least one second layer containing 10 vol% zirconia as the temperature changes. The ability to vary the CTE characteristics of at least one second layer 102 provides CTE matching between at least one second layer 102, at least one third layer 103, and at least one first layer 100, especially within the temperature range consistent with the methods and sintering temperatures disclosed herein. The selection of the composition of at least one second layer 102 and at least one third layer 103 enables the use of a variety of materials for at least one first layer 100 having the same or substantially the same CTE as the second layer 102 and the third layer 103 within the ranges disclosed herein, but is not limited thereto. In some embodiments, within the disclosed temperature range from ambient temperature to about 1700 °C (or from 200 °C to 1400 °C as shown in the figures), the CTE of at least one second layer 102 can be greater than and less than the CTE of at least one first layer, such that the CTE difference is zero within this temperature range. In other embodiments, within the disclosed temperature range (from ambient temperature to about 1700 °C as shown in the figures, or from 200 °C to 1400 °C), the CTE of at least one second layer 102 can be greater than or less than the CTE of at least one first layer 100, and thus, as measured according to ASTM E228-17 in the temperature range from 25 °C to 1700 °C or in the temperature range from 200 °C to 1400 °C, the absolute value of the coefficient of thermal expansion (CTE) difference between at least one first layer 100 and at least one second layer 102 can be from 0.003×10-6 / °C to 0.75×10-6 / °C, preferably from 0.003×10-6 / °C to 0.7×10-6 / °C, preferably from 0.003×10-6 / °C to 0.6×10-6 / °C, preferably from 0.003×10-6 / °C to 0.5×10-6 / °C, preferably from 0.003×10-6 / °C to 0.45×10-6 / °C, preferably from 0.003×10-6 / °C to 0.4×10-6 / °C, preferably from 0.003×10-6 / °C to 0.35×10-6 / °C, preferably from 0.003×10-6 / °C to 0.3×10-6 / °C, preferably from 0.003×10-6 / °C to 0.25×10-6 / °C, preferably from 0.003×10-6 / °C to 0.2×10-6 / °C, preferably from 0.003×10-6 / °C to 0.15×10-6 / °C, preferably from 0.003×10-6 / °C to 0.1×10-6 / °C, preferably from 0.003×10-6 / °C to 0.08×10-6 / °C, preferably from 0.003×10-6 / °C to 0.06×10-6 / °C, preferably from 0.003×10-6 / °C to 0.04×10-6 / °C, preferably from 0.003×10-6 / °C to 0.02×10-6 / °C, and preferably from 0.003×10-6 / °C to 0.01×10-6 / °C.

[0125] In other embodiments, at least one second layer 102 may have a CTE greater than that of at least one first layer 100 in a temperature range from about 600 °C to about 1700 °C (or up to at least 1400 °C as depicted in the figures), and a CTE less than that of at least one first layer 100 in a temperature range from ambient temperature (or up to at least 200 °C as depicted in the figures) to about 600 °C. The temperature at which the magnitude of the CTE changes between at least one first layer and at least one second layer may occur at any temperature from about 200 °C to about 800 °C. Without being bound by a particular theory, the lower CTE of at least one second layer 102 relative to at least one first layer 100 at lower temperatures (e.g., 800 °C to ambient temperature) serves to provide compression of at least one first layer 100, thereby reducing the likelihood of crack propagation, fracture, and spalling, which can lead to particle generation during use as a component in a semiconductor plasma processing chamber.

[0126] At least one third layer 103 generally has a CTE within the ranges disclosed for at least one first layer and at least one second layer. The CTE of at least one third layer 103 can be adjusted by varying the amount of zirconia to match the CTE of at least one first layer and at least one second layer. Thus, the absolute value of the difference in coefficient of thermal expansion (CTE) between at least one first layer 100, at least one second layer 102, and at least one third layer 103 can be 0 to 0.75×10−6 / °C, preferably 0 to 0.7×10−6 / °C, preferably 0 to 0.6×10−6 / °C, preferably 0 to 0.5×10−6 / °C, preferably 0 to 0.45×10−6 / °C, preferably 0 to 0.4×10−6 / °C, preferably 0 to 0.35×10−6 / °C, preferably 0 to 0.3×10−6 / °C, preferably 0 to 0.25×10−6 / °C, preferably 0 to 0.2×10−6 / °C, preferably 0 to 0.15×10−6 / °C, preferably 0 to 0.1×10−6 / °C, preferably 0 to 0.08×10−6 / °C, preferably 0 to 0.06×10−6 / °C, preferably 0 to 0.04×10−6 / °C, preferably 0 to 0.02×10−6 / °C, and preferably 0 to 0.01×10−6 / °C as measured in a temperature range from 25 °C to 1700 °C or in a temperature range from 200 °C to 1400 °C according to ASTM E228-17.

[0127] In other embodiments, the absolute value of the coefficient of thermal expansion (CTE) difference between at least one first layer 100, at least one second layer 102, and at least one third layer 103, as measured according to ASTM E228-17 in a temperature range from 25°C to 1700°C or in a temperature range from 200°C to 1400°C, can be from 0.003×10-6 / °C to 0.75×10-6 / °C, preferably from 0.003×10-6 / °C to 0.7×10-6 / °C, preferably from 0.003×10-6 / °C to 0.6×10-6 / °C, preferably from 0.003×10-6 / °C to 0.5×10-6 / °C, preferably from 0.003×10-6 / °C to 0.45×10-6 / °C, preferably from 0.003×10-6 / °C to 0.4×10-6 / °C, preferably from 0.003×10-6 / °C to 0.35×10-6 / °C, preferably from 0.003×10-6 / °C to 0.3×10-6 / °C, preferably from 0.003×10-6 / °C to 0.25×10-6 / °C, preferably from 0.003×10-6 / °C to 0.2×10-6 / °C, preferably from 0.003×10-6 / °C to 0.15×10-6 / °C, preferably from 0.003×10-6 / °C to 0.1×10-6 / °C, preferably from 0.003×10-6 / °C to 0.08×10-6 / °C, preferably from 0.003×10-6 / °C to 0.06×10-6 / °C, preferably from 0.003×10-6 / °C to 0.04×10-6 / °C, preferably from 0.003×10-6 / °C to 0.02×10-6 / °C, and preferably from 0.003×10-6 / °C to 0.01×10-6 / °C.

[0128] In contrast, Figure 4 Figure shows a material combination prepared by the same method but not meeting the CTE matching requirements as disclosed herein (and thus having a mismatch in the absolute value of the CTE difference). The figure depicts a sintered ceramic body formed of a YAG first layer and an alumina substrate (second layer) (according to the "Comparative Example" in the Examples section). As Figure 3As shown, alumina exhibits a lower CTE than any of YAG, spinel, and 80% yttria / 20% zirconia. The sintered ceramic body fractures within the alumina substrate near the interface between the layers during annealing. Fracture will occur at the weakest region in the sintered body, and fractures occurring within bulk alumina may indicate an interface strength that is approximately the same as or greater than the interface strength of the bulk alumina substrate. The location of the fracture (within alumina) represents an extremely high interface strength achieved by using the materials and methods disclosed herein (which may exceed the interface strength between the first bulk layer and the second bulk layer). The CTE difference between YAG and alumina is sufficient to cause fractures within the bulk sintered body while maintaining the integrity at the interface between the two layers. Thin film deposition and / or thin film lamination methods used to form laminates typically exhibit much lower interface strengths and accordingly fractures and / or cracking occur at the interface between the thin films (such as Figure 1 interlayer fractures or delamination depicted in the schematic of Figure 3 ). As shown in

[0129] In addition to CTE matching, the multi-layer sintered ceramic body preferably has a high thermal conductivity for use as a component in a semiconductor plasma processing chamber. Selecting a zirconia toughened alumina (ZTA) composition for use as at least one second layer 102 (and at least a portion of at least one third layer 103) will significantly affect the properties of the overall multi-layer sintered body. The high thermal conductivity of at least one second layer 102 is an important material property for effectively dissipating heat and thereby avoiding local overheating within at least one second layer during use (especially when used as a dielectric window component or an RF window component). Such local overheating can lead to cracking or fracture of the overall multi-layer sintered body. It is reported in the literature that zirconia has a lower thermal conductivity than alumina, so the amount of zirconia will affect the thermal conductivity of at least one second layer 102. Although pure alumina is known to have a high thermal conductivity, the CTE mismatch precludes its use in combination with the material used for at least one first layer 100 disclosed herein. Although there may be no practical lower limit to the minimum amount of zirconia in at least one second layer 102 for reasons of thermal conductivity, in order to provide CTE matching with at least one first layer 100 and a high thermal conductivity (about the same as that of alumina), at least one second layer 102 containing at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 5 vol% and more, up to and including 30 vol% (the balance portion containing about 70 vol% to 95 vol% of a second crystalline phase of alumina) is preferred.

[0130] In order to provide at least one second layer 102 having a thermal conductivity sufficient for high-frequency applications such as RF or dielectric window or cover components, for example, at least one second layer 102 having up to and including about 30 vol% and preferably not more than 25 vol% of zirconia in some embodiments may be preferred. A second layer 102 having more than 30 vol% of zirconia may not provide sufficient thermal conductivity for use as a component in a semiconductor plasma processing chamber that requires a high thermal conductivity. A composition of at least one second layer 102 having more than 30 vol% of zirconia can create a high thermal gradient within at least one second layer 102 and can lead to fracture and / or cracking.

[0131] Figure 7 The thermal expansion coefficient results from 200 °C to 1400 °C of at least one second layer 102 having zirconia present in an amount of 10 vol% to 30 vol% as disclosed herein are shown. The CTE values of at least one second layer (not shown) containing 5 vol% zirconia vary with temperature and generally fall between those of pure alumina and at least one second layer containing 10 vol% zirconia. At least one second layer 102 contains as Figure 8At least two separate crystalline phases of zirconia and alumina as shown, and thus the volume mixing rules known to those skilled in the art are used to calculate the CTE values for 5 vol%, 25 vol%, and 30 vol% zirconia. The CTE is shown to increase with increasing amount of zirconia by volume, as Figure 7 shown. Depending on the volume of zirconia in the ZTA (zirconia toughened alumina) of at least one second layer 102, the CTE of at least one second layer can be greater than, substantially equal to, equal to, or less than (by amounts varying within the ranges disclosed herein) the CTE of at least one first layer 100 (comprising YAG, spinel, or yttrium oxide and zirconia) that comprises the overall multi-layer sintered ceramic body. Thus, as used herein, the CTE difference generally means the absolute value of the CTE difference, unless otherwise specifically stated.

[0132] A high toughness value for at least one second layer 102 is preferred for improving processability and preventing fractures and / or cracking in the multi-layer sintered ceramic body. To enhance the toughness of at least one second layer 102 comprising alumina and zirconia, toughening and / or stabilization of at least one second layer is preferred. Without wishing to be bound by any particular theory, the toughening and stabilization mechanisms disclosed herein can be used for the purpose of stabilizing the tetragonal crystalline phase of zirconia, thereby restricting the transformation (at lower temperatures) into the monoclinic crystalline phase, which is accompanied by a large volume change of about 4.5%, such that the phase stability of tetragonal zirconia is preferred. The stabilization of tetragonal zirconia can be achieved by any stabilization method known to those skilled in the art, but is not limited thereto.

[0133] The combination of zirconia and alumina in at least one second layer can provide transformation toughening through the dispersion of tetragonal zirconia particles, at least a portion of which transform to the monoclinic form upon crack propagation. As is known to those skilled in the art, the volume expansion from tetragonal to monoclinic zirconia provides transformation or dispersion toughening in at least one second layer 102. In an embodiment, at least one second layer 102 can comprise a particulate composite of the crystalline phases of zirconia and alumina in the disclosed volumes (also referred to herein as a composite oxide or ZTA, representing a dispersion or transformation toughened ceramic). Such a toughening method can be affected by the powder particle size, shape, and location of the tetragonal and monoclinic, dispersed zirconia phases in the alumina medium.

[0134] Another stabilization method utilizes stabilizing compounds in different molar amounts that include yttrium oxide, calcium oxide, lanthanum oxide (La2O3), cerium oxide (CeO2), samarium oxide (Sm2O3), and magnesium oxide and combinations thereof to stabilize zirconia preferably in a tetragonal or cubic crystal phase (the monoclinic crystal phase of zirconia is stable at room temperature; thus, the tetragonal and cubic crystal phases are considered metastable phases when present at room temperature). The relative amounts and types of these stabilizing compounds can result in at least a second layer 102 that includes zirconia and includes at least one of fully stabilized zirconia (SZ) and partially stabilized zirconia (PSZ). Generally, the stabilizing compounds can be selected based on their valence and atomic radius relative to zirconium (Zr). Those stabilizing compounds having a larger atomic radius than zirconium are favorable for the stabilization of the tetragonal and / or cubic crystal phases. In some embodiments, yttrium oxide can be selected as a stabilizing compound for the tetragonal phase having a lower valence (+3) and a larger atomic radius (180 pm) compared to zirconia (having an atomic radius of 160 picometers (pm)). Generally, those stabilizing compounds having a lower valence state (coordination number) compared to zirconia are preferred. Without being bound by a particular theory, the use of those stabilizing compounds having a lower valence state compared to zirconia (+4) can result in the introduction of oxygen vacancies, which can increase the dielectric loss at high frequencies such as RF or microwave frequencies. Thus, in some embodiments, a stabilizing compound such as cerium oxide (CeO2) having the same valence as zirconia (+4) and a larger atomic radius (185 pm) can stabilize the tetragonal and / or cubic crystal phases without introducing oxygen vacancies. In some embodiments, a combination of at least two of these stabilizing compounds can be preferred and can be combined in any combination in the amounts disclosed herein to stabilize zirconia that includes at least a second layer 102 and / or at least a third layer 103. The stabilizing compounds can be added to at least one second powder mixture and / or third powder mixture according to the disclosed method. Table 1 lists the stabilizing compounds that result in stabilized zirconia (SZ) and / or partially stabilized zirconia (PSZ), their molar amounts, and weight percentages. Stabilizing zirconia using the disclosed stabilizing compounds can cause the CTE of at least a third layer to change and can correspondingly adjust the amount of zirconia.

[0135] Table 1

[0136]

[0137] In an embodiment, at least one second layer 102 may comprise particles or grains of zirconia (PSZ, SZ, and combinations thereof) dispersed in a host medium of alumina, wherein the at least one second layer comprises a particulate composite (composite oxide) having two separate crystal phases of alumina and zirconia. Preferably, the at least one second layer 102 does not form a solid solution. The formation of a solid solution may reduce the thermal conductivity, and thus the at least one second layer 102 comprises separate crystal phases of zirconia and alumina. Figure 8 The separate crystal phases of zirconia and alumina were depicted from the x-ray diffraction results, confirming that the at least one second layer 102 comprises separate crystal phases without forming a solid solution. X-ray diffraction for all measurements disclosed herein was performed using a PANalytical Aeris XRD model capable of identifying crystal phases to approximately + / -5%. According to an embodiment of the at least one second layer, the small amount of yttrium oxide present in Figure 8 the x-ray diffraction pattern may be caused by partial stabilization of zirconia (yttrium-partially stabilized zirconia, PYSZ).

[0138] Furthermore, using those compounds known to form glass (such as magnesium oxide, silicon dioxide, and calcium oxide) as sintering aids in the at least one second layer 102 may result in a glass phase present between the grains with low thermal conductivity, thus having an adverse effect on the thermal conductivity. Therefore, in some embodiments, preferably, as measured by the ICPMS method, the at least one second layer 102 comprises magnesium oxide and / or calcium oxide in a range of from about 2 ppm to 100 ppm, preferably from about 2 ppm to 75 ppm, preferably from about 2 ppm to 50 ppm, preferably from about 2 ppm to 25 ppm, preferably from about 2 ppm to 20 ppm, preferably from about 2 ppm to 10 ppm, preferably about 8 ppm, preferably about 2 ppm and less, relative to the mass of the at least one second layer. In additional embodiments, the at least one second layer 102 may comprise silicon dioxide in an amount of from about 14 ppm to 100 ppm, preferably from about 14 ppm to about 75 ppm, more preferably from about 14 ppm to about 50 ppm, preferably from about 14 ppm to about 30 ppm, preferably about 14 ppm and less (as measured by the ICPMS method), relative to the mass of the at least one second layer 102. The second layer 102 comprising sintering aids within the disclosed ranges may provide a multi-layer sintered ceramic body that is free or substantially free of a glass phase, thus providing a high thermal conductivity of the multi-layer sintered ceramic body. A multi-layer sintered ceramic body comprising at least one second layer 102 is disclosed herein, the at least one second layer being free or substantially free of dopants and / or sintering aids as disclosed herein.

[0139] Thermal conductivity (as the product of diffusivity, density, and known heat capacity) is calculated by performing (at ambient temperature and at 200 °C) thermal diffusivity measurements on at least one second layer 102 comprising about 16 volume % yttria partially stabilized zirconia (3 mol %) with the balance being alumina, in accordance with ASTM E1461-13. In an embodiment, at least one second layer 102 comprising about 16 volume % yttria partially stabilized zirconia is calculated to have a thermal conductivity of about 25 W / m-K at ambient temperature and about 14 W / m-K at 200 °C. Thus, at least one second layer 102 preferably comprises zirconia in an amount by volume of about 5% to about 30%, preferably about 5% to about 20%, preferably about 10% to about 20%, preferably about 15% to about 20% relative to the volume of the at least one second layer 102. At least one second layer 102 having a composition within the ranges disclosed herein provides a thermal conductivity sufficient to be used, for example, as a dielectric window, RF window, cover, and other components in a plasma processing chamber as disclosed herein that require high thermal conductivity.

[0140] To prevent local hot spots and overheating during use, especially for RF applications, low dielectric loss is preferred. For example, the dielectric loss can be affected by material properties such as particle size and the presence of impurities, sintering aids, and / or dopants. The presence of impurities and / or sintering aids and / or dopants, such as especially silica, in at least one second layer 102 can result in higher dielectric loss. The use of a starting powder with high purity / low impurity content and a method of maintaining purity results in at least one second layer 102 with high overall purity and a correspondingly low overall impurity content. Thus, in an embodiment, as measured using the ICPMS method, the at least one second layer 102 as disclosed can have a total impurity content of 5 ppm to 200 ppm, preferably 5 ppm to 150 ppm, preferably less than 100 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably 10 ppm to 100 ppm, preferably 10 ppm to 80 ppm, preferably 10 ppm to 60 ppm, preferably 10 ppm to 40 ppm, preferably 20 ppm to 80 ppm, and preferably 30 ppm to 60 ppm relative to the mass of the at least one second layer. In an embodiment, the at least one second layer 102 is formed from a powder mixture that contains silica in an amount of about 14 ppm to 100 ppm, preferably about 14 ppm to 75 ppm, preferably about 14 ppm to 50 ppm, preferably about 14 ppm to 25 ppm, preferably about 14 ppm relative to the total mass of the calcined powder mixture. In an embodiment, as measured using the ICPMS method, the at least one second layer 102 can contain magnesium oxide (MgO) in an amount of about 2 ppm to 100 ppm, preferably about 2 ppm to 75 ppm, preferably about 2 ppm to 50 ppm, preferably about 2 ppm to 25 ppm, preferably about 2 ppm to 20 ppm, preferably about 2 ppm to 10 ppm, preferably about 8 ppm and less, and preferably about 2 ppm relative to the mass of the at least one second layer 102.

[0141] For use in plasma processing chambers, especially those operating in the RF range, a multilayer sintered ceramic body 98 with low dielectric loss (tangent δ) is preferred. In an embodiment, at least one second layer 102 can have the maximum thickness (and corresponding maximum volume) of the multilayer sintered ceramic body 98, so the relevant properties of at least one second layer can greatly affect the electrical and other properties of the sintered body, such as thermal conductivity. The dielectric loss of the sintered body can be affected by the purity of at least one second layer 102, especially the silica content. Thus, at least one second layer 102 can contain magnesium oxide and / or calcium oxide in amounts of about 2 ppm to 100 ppm, preferably about 2 ppm to 75 ppm, preferably about 2 ppm to 50 ppm, preferably about 2 ppm to 25 ppm, preferably about 2 ppm to 20 ppm, preferably about 2 ppm to 10 ppm, preferably about 2 ppm, each relative to the mass of the composite oxide second layer 102. In a further embodiment, at least one second layer 102 as disclosed herein can be formed from at least one powder mixture having an Si content of about 14 ppm and greater, preferably 14 ppm to 100 ppm, preferably 14 ppm to 75 ppm, preferably 14 ppm to 50 ppm, preferably 14 ppm to 25 ppm, preferably 14 ppm to 20 ppm, preferably about 14 ppm, relative to the total mass of the second layer 102. In an embodiment, the second layer can have a total impurity content of 5 ppm to 200 ppm, preferably 5 ppm to 150 ppm, preferably less than 100 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably 10 ppm to 100 ppm, preferably 10 ppm to 80 ppm, preferably 10 ppm to 60 ppm, preferably 10 ppm to 40 ppm, preferably 20 ppm to 80 ppm, preferably 30 ppm to 60 ppm, relative to the total mass of the second layer.

[0142] The total impurity content of at least one second layer 102 containing calcium oxide, silica, and magnesium oxide in the amounts disclosed herein provides, as measured according to ASTM D150, a dielectric loss of less than 7×10 -4 at a frequency of 1 MHz at ambient temperature, as listed in Table 7 for at least one second layer 102 comprising about 16 vol% yttria partially stabilized (3 mol% yttria) zirconia with the balance being alumina. In an embodiment, at least one second layer 102 is free (0 ppm or at or below the detection limit) or substantially free (2 ppm to 5 ppm) of dopants and / or sintering aids as disclosed herein. At least one second layer 102 as disclosed herein provides a multilayer sintered ceramic body or a component made therefrom having a low dielectric loss and suitable for use as a chamber component, especially as a window or cover component for use in a high-frequency, RF plasma processing chamber.

[0143] A plasma processing chamber for manufacturing semiconductor devices is designed to accommodate substrates having an increasing diameter, which correspondingly requires large-sized chamber components. These chamber components made of the multi-layer sintered ceramic body disclosed herein can have a maximum size of, for example, 100 mm to about 625 mm, preferably 100 mm to 622 mm, preferably 200 mm to about 625 mm, preferably 300 mm to about 625 mm, preferably 400 mm to about 625 mm, preferably 500 mm to about 625 mm, preferably 300 mm to 622 mm, preferably 400 mm to 622 mm, and preferably 500 mm to 622 mm.

[0144] Many materials known to provide corrosion resistance and erosion resistance are difficult to sinter, resulting in low density and correspondingly low sintering strength, which can lead to fracture or cracking. This makes it challenging to manufacture large monolithic solid components from these corrosion-resistant materials. A high-strength material (matching the CTE of the corrosion-resistant materials as disclosed herein) is required to form at least one second layer 102, enabling the manufacture of large-sized chamber components. At least one second layer 102 provides mechanical strength and hardness to the monolithic multi-layer corrosion-resistant sintered body (and components made therefrom) as disclosed herein. At least one second layer 102 can be sintered to an extremely high density and, in an embodiment, to a fully dense body, which provides the mechanical strength and hardness necessary for manufacturing large-sized multi-layer sintered bodies having a maximum size of, for example, 100 mm to about 625 mm, preferably 100 mm to 622 mm, preferably 200 mm to about 625 mm, preferably 300 mm to about 625 mm, preferably 400 mm to about 625 mm, preferably 500 mm to about 625 mm, preferably 300 mm to 622 mm, preferably 400 mm to 622 mm, and preferably 500 mm to 622 mm. Density measurements were performed on sintered bodies having 10 vol% to 16 vol% of zirconia (and the balance comprising alumina) in accordance with ASTM B962-17, and the density of those at least one second layer having 5%, 20%, 25%, and 30% zirconia was calculated using the volume mixing rule. A theoretical density of 99% was assumed in the calculated densities. Table 2 lists the densities of at least one second layer containing zirconia and alumina crystal phases as disclosed herein.

[0145] Table 2

[0146] Volume % ZrO2 Volume % Al2O3 Average density (g / cc) % Theoretical density % Volume porosity 5 95 4.04 >99 <1 10 90 4.19 100 0 12 88 4.23 99.9 0.12 12 88 4.22 99.8 0.21 12 88 4.20 99.2 0.83 16 84 4.32 100 0 20 80 4.36 >99 <1 25 75 4.46 >99 <1 30 70 4.57 >99 <1

[0147] The theoretical density of zirconia is reported to be 6.09 g / cc, while the theoretical density of alumina is reported to be 3.98 g / cc. Calculate the theoretical density of at least one second layer 102 according to the volume mixing rules known to those skilled in the art (using these density values and the volume fractions of the respective crystal phases of zirconia and alumina). For the embodiments of at least one second layer 102 disclosed in Table 2, extremely high densities (99% to 100% of the theoretical density) were measured. As measured according to ASTM B962-17, at least one second layer 102 containing zirconia in an amount of about 16 volume % (and the balance being alumina) as disclosed herein was measured to have a density of about 4.32 g / cc. These high densities provide sufficient mechanical strength and hardness (Young's modulus) to form a monolithic multi-layer sintered body of large size (up to and including a maximum size of about 625 mm).

[0148] In a four-point flexure test according to ASTM standard C 1161-3, "Standard Test Method for Flexural Strength of Advanced Ceramics at Ambient Temperature", test at least one second layer 102 containing zirconia in an amount of about 16 volume % (and the balance being alumina) as disclosed herein to determine the flexural strength. The four-point bend test is superior to the three-point bend test because it exposes a larger volume of the sample to a uniform maximum stress and thus produces a more representative strength of the material being tested. The three-point bend test exposes a relatively small volume of the sample to the maximum stress, and thus, the reported three-point flexure test strength values tend to be higher. Therefore, due to the significant variations in their measurement setups and methods, comparing the three-point and four-point flexure tests presents a challenge. Using ASTM standard C 1161-3, extremely high strength values were achieved in a four-point bend configuration for at least one second layer 102 containing 16 volume % zirconia. Table 3 lists the flexural strength (modulus of rupture, MOR) and other material properties of at least one layer 102 containing about 16% partially stabilized ZrO2 and the balance being alumina.

[0149] During use in a semiconductor reactor under vacuum conditions, a corrosion-resistant multi-layer component fabricated from a multi-layer sintered ceramic body as disclosed herein can withstand flexural stresses in excess of 500 mm across the component dimensions. The properties of high strength and increased hardness / Young's modulus may be necessary for materials to be used as components as disclosed herein in large-scale etching and / or deposition chambers. The flexural strength of 98% dense alumina is reported to be about 375 MPa, and the hardness (elastic modulus / Young's modulus) is reported to be about 350 GPa (Coorstek Advanced Alumina Data Sheet, available online). At least one second layer 102 as disclosed herein can provide mechanical strength and hardness / Young's modulus that is approximately the same as or exceeds that of alumina while providing the desired CTE match with at least one first layer 100 and at least one third layer 103. The use of at least one second layer 102 as disclosed herein can significantly enhance the flexural strength and stiffness of the overall multi-layer component fabricated from the multi-layer sintered ceramic body such that it is possible to fabricate large (>100 mm to about 625 mm and larger in size) components having high strength, high hardness, and resistance to halogen-based corrosion and erosion that are necessary for use as components in semiconductor plasma processing chambers.

[0150] At least one first layer 100 provides a chemically inert, plasma-facing surface 106 that is resistant to the corrosive action of halogen process gases and the erosive action of plasma ion bombardment (inert gases such as argon and other process gases known in the art can generally be used), while at least one second layer 102 provides mechanical strength to the multi-layer corrosion-resistant sintered body as disclosed herein. At least one second layer 102 can be sintered to an extremely high density and, in embodiments, to a fully dense body, which provides the mechanical strength necessary to fabricate multi-layer sintered bodies of large dimensions such as 100 mm to about 625 mm in diameter, preferably between 200 mm and 625 mm, preferably between 250 mm and about 625 mm, preferably between 300 mm and about 625 mm, more preferably between 350 mm and about 625 mm, more preferably between 400 mm and about 625 mm, more preferably between 450 mm and about 625 mm, more preferably between 500 mm and about 625 mm. Table 3 lists the properties of at least one second layer 102 that contains 16 vol% partially stabilized zirconia and the balance is alumina.

[0151] Table 3

[0152]

[0153] Now refer to Figure 6Embodiments are disclosed of a multi-layer sintered ceramic body 98 comprising at least one third layer 103. The at least one third layer 103 comprises a polycrystalline phase having at least one of YAG, alumina, and zirconia. The zirconia can include at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia.

[0154] In an embodiment, the at least one third layer 103 comprises, by area, greater than 50% to 90%, preferably greater than 50% to 80%, preferably greater than 50% to 60%, and more preferably about 51% to 55% of YAG relative to the area of an exemplary polished surface of the at least one third layer. Area measurements are completed using backscattered detection images from SEM, which are imported into ImageJ software, after which the respective phases of YAG and alumina / zirconia are measured for their surface area percentage within the entire exemplary image area. The at least one third layer 103 of the multi-layer sintered ceramic body can form a single-piece body and thus comprises, throughout, at least the crystalline phases of YAG, zirconia, and alumina made according to the processes disclosed herein. In other words, the structure measured on the surface represents the structure within the volume of the at least one third layer of the body. Thus, the at least one third layer of the multi-layer sintered ceramic body can comprise the same relative amounts of the crystalline phases of YAG, zirconia, and alumina on the surface and throughout the volume of the sintered body.

[0155] In Figure 26 a) and Figure 26 the 1000× SEM micrographs of b) depict the multiphase structure of the at least one third layer 103. Figure 26 a) shows the microstructure of the at least one third layer 103, which comprises large (maximum size of about 80 μm to about 200 μm) regions (white / light gray regions) of the YAG phase and an alumina phase (black regions throughout) having a zirconia phase (small size, about 10 μm diameter white regions within the alumina phase) dispersed therein. The microstructure of Figure 26 a) can be achieved by dry mixing the powders of alumina, yttrium oxide, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia for about 16 hours without using a grinding / mixing medium to form a third powder mixture according to the embodiments disclosed herein. The absence of a grinding medium and the dry mixing conditions can contribute to the microstructure as Figure 26 depicted in a).

[0156] Figure 26b) shows 1000× and 5000× microstructures (insets) of at least one third layer 103, which comprises a finely dispersed (maximum size of about 5 μm to about 20 μm) YAG phase (white / light gray regions) and an alumina phase (black regions) with a zirconia phase (small size, white regions of about 3 μm diameter within the alumina phase) dispersed therein. It can be formed by the following method Figure 26 the microstructure of b): forming a 40 wt% ethanol slurry of a powder comprising alumina, yttrium oxide, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia to form a third powder mixture according to an embodiment as disclosed herein. Alumina media is added in an amount of about 100% loading relative to the weight of the powder, and the powder is tumbled and milled for 20 hours. The high media loading and extended milling time can contribute to the finely dispersed and highly uniform microstructure as Figure 26 depicted in b).

[0157] At least one third layer 103 also provides improved machinability and CTE matching (within the range as disclosed herein) to at least one first layer 100 and at least one second layer 102. According to Figure 22 a), the light gray / white regions (containing YAG) and the alumina / zirconia regions (depicted as dark gray or black with white regions therein) each form regions with a size of about 100 μm and larger, as shown in the SEM depicting the multiphase third layer 103. Multiple SEM images are analyzed using ImageJ to determine the area percentage of each phase constituting the multiphase layer 103. Using the Figure 26 SEM images of a) (and other images taken at the same magnification of 500×), it can be seen that the multi-layer sintered body comprises at least one third layer 103, and the at least one third layer comprises an area measurement of about 51% to about 63%, preferably about 51% to about 60%, preferably about 55% to about 60%, and preferably about 60% of the YAG phase based on the alumina-rich phase (containing YAG), and the balance comprises alumina and zirconia (wherein the zirconia comprises at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia). The multiphase structure having regions containing YAG and regions containing alumina and zirconia can provide improved fracture toughness and crack growth resistance by deflecting cracks along the interfaces between these regions and thereby increasing the crack length. In addition, at least one third layer 103 can reduce the size and frequency of defects that can be formed during machining, thereby maintaining mechanical strength and toughness by absorbing the energy generated during machining within the multiphase, at least one third layer 103.

[0158] In an embodiment, at least one third phase comprises a zirconia toughened alumina (ZTA) phase, the ZTA phase comprising at least one of unstabilized zirconia, partially stabilized zirconia, or stabilized zirconia in an amount of about 16 volume % and the balance being alumina.

[0159] In some embodiments (as depicted in Figure 26 ), at least one third layer 103 comprises a YAG phase (white / light gray regions) in an area (and thus volume) amount of greater than 50% to about 55%, an alumina phase (black / grey) in an amount of about 45% to less than 50%, and a zirconia phase (white regions within the black / grey) dispersed within the alumina phase, wherein the zirconia comprises about 16 volume % of 3 mol % yttria partially stabilized zirconia.

[0160] At least one third layer 103 also provides improved uniformity during sintering by combining yttria, zirconia, and alumina powders to form a third powder mixture having sintering characteristics similar to at least one first powder mixture. The third powder mixture can provide more uniform heat transfer within the powder mixture during sintering according to the methods disclosed herein, thereby providing more uniform sintering characteristics (such as the sintering temperature and densification rate of the respective layers).

[0161] In Figure 22 a) and Figure 22 b), a second interface 105 between at least one third layer 103 and at least one second layer 102 is depicted. As shown, the second interface 105 (which is described in more detail herein) can provide enhanced toughness between at least one third layer 103 and at least one second layer 102. This improved toughness can be achieved by a number of factors such as the multiphase nature of the second interface 105 (which can provide an increased area between the phases to deflect crack propagation) and an interlocking effect provided by the morphology and non-linearity of the multiple phases of the second interface 105. The mixing between the powder mixtures forming at least one third layer 103 and at least one second layer 102 provides the second interface 105, which in some embodiments may not have a clearly defined boundary between the third layer 103 and the second layer 102. The second interface 105 can include a diffusion boundary in some embodiments, and thus, properties such as composition, strength, fracture toughness, etc. throughout the second interface 105 can have gradients. In other embodiments, the second interface 105 provides a different non-linear boundary between at least one second layer 102 and at least one third layer 103. The various powder combining methods disclosed herein for at least one third powder mixture can produce as Figure 22At least one second interface 105 depicted in b). In an embodiment, at least one second layer and at least one third layer may be in contact to form the second interface 105, and thus the second layer and the third layer are adjacent. In other embodiments, circuits, heating elements, RF coils / antennas, etc. may be disposed between the second layer and the third layer according to the needs of a particular component application, and regardless of these features, the first layer and the second layer may be adjacent or substantially adjacent.

[0162] In a preferred embodiment, the compositions are selected for at least one third layer 103, at least one first layer 100, and at least one second layer 102, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) of at least one first layer, at least one second layer, and at least one third layer is 0 to 0.75×10-6 / °C, preferably 0 to 0.7×10-6 / °C, preferably 0 to 0.6×10-6 / °C, preferably 0 to 0.5×10-6 / °C, preferably 0 to 0.45×10-6 / °C, preferably 0 to 0.4×10-6 / °C, preferably 0 to 0.35×10-6 / °C, preferably 0 to 0.3×10-6 / °C, preferably 0 to 0.25×10-6 / °C, preferably 0 to 0.2×10-6 / °C, preferably 0 to 0.15×10-6 / °C, preferably 0 to 0.1×10-6 / °C, preferably 0 to 0.08×10-6 / °C, preferably 0 to 0.04×10-6 / °C, and preferably 0 to 0.02×10-6 / °C as measured in the temperature range of 25°C to 1700°C or in the temperature range of 200°C to 1400°C according to ASTM E228-17. CTE matching between at least one first layer 100, at least one second layer 102, and at least one third layer 103 may be provided in the temperature range from ambient temperature to about 1700°C according to the method disclosed herein. The selection of these materials providing this CTE difference may reduce the interfacial stress on the non-linear interface 104 and the second interface 105, thereby improving the adhesion between the layers of the multi-layer sintered ceramic body and the components formed therefrom.

[0163] According to one embodiment, there is disclosed herein an integral multi-layer sintered ceramic body comprising at least one first layer 100 comprising at least one ceramic material having polycrystalline YAG; at least one second layer 102 comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia; and at least one third layer 103 comprising a plurality of phases selected from the group consisting of YAG, alumina, and zirconia, wherein the zirconia comprises at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between at least one first layer, at least one second layer, and at least one third layer, as measured according to ASTM E228-17 in the temperature range from 25°C to 1700°C or in the temperature range from 200°C to 1400°C, is from 0 to 0.75×10-6 / °C, preferably from 0 to 0.7×10-6 / °C, preferably from 0 to 0.6×10-6 / °C, preferably from 0 to 0.5×10-6 / °C, preferably from 0 to 0.45×10-6 / °C, preferably from 0 to 0.4×10-6 / °C, preferably from 0 to 0.35×10-6 / °C, preferably from 0 to 0.3×10-6 / °C, preferably from 0 to 0.25×10-6 / °C, preferably from 0 to 0.2×10-6 / °C, preferably from 0 to 0.15×10-6 / °C, preferably from 0 to 0.1×10-6 / °C, preferably from 0 to 0.08×10-6 / °C, preferably from 0 to 0.04×10-6 / °C, and preferably from 0 to 0.02×10-6 / °C, wherein at least one first layer, at least one second layer, and at least one third layer form an integral multi-layer sintered ceramic body. These ranges of the absolute value of the CTE difference between at least one first layer comprising polycrystalline YAG and at least one second layer and at least one third layer correspond to a CTE difference of at least one first layer, at least one second layer, and at least one third layer of about 10% and less, preferably 9% and less, preferably 8% and less, preferably 6% and less, preferably 4% and less, preferably 3% and less, preferably 2.5% and less, preferably 2% and less, preferably 1.5% and less, preferably 1% and less, preferably 0.5% and less, and preferably 0.25% and less by percentage between any of at least one first layer, at least one second layer, and at least one third layer (as measured relative to at least one first layer 100 comprising polycrystalline YAG).

[0164] In a temperature range from ambient temperature (or at least from 200 °C as depicted in the figures) to about 1700 °C (or at least to 1400 °C as depicted in the figures), at least one first layer, at least one second layer, and at least one third layer are CTE - matched within the disclosed range to form an integral multi - layer sintered ceramic body. In an embodiment, at least one first layer 100 may further comprise at least one crystalline phase selected from the group consisting of YAP (yttrium aluminum perovskite), YAM (yttrium aluminum monoclinic phase), yttrium oxide, alumina, and combinations thereof, as determined by x - ray diffraction, SEM imaging, and ImageJ analysis, and the at least one crystalline phase is present in an amount of less than 5%, preferably less than 3%, and more preferably less than 1% by volume of at least one first layer 100 each. Each of the crystalline phases of YAG, YAP, and YAM is preferably polycrystalline. Figure 9 a), Figure 9 b) and Figure 9c ) show CTE measurements of at least one first layer and at least one second layer of exemplary materials for forming an integral multi - layer sintered ceramic body according to an embodiment in a temperature range from ambient temperature (or at least from 200 °C as depicted in the figures) to about 1700 °C (or at least to 1400 °C as depicted in the figures). All CTE measurements as disclosed herein are performed according to ASTM E228 - 17 in a temperature range from 25 °C to 1700 °C or in a temperature range from 200 °C to 1400 °C. CTE measurements are made on exemplary bulk materials. Figure 9 a) depicts a polycrystalline YAG first layer 100 (solid line) and a second layer (ZTA, dashed line) 102, where the second layer contains at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 10 vol% and the balance (90 vol%) is alumina, relative to the total volume of at least one second layer 102. Figure 9 b) depicts a polycrystalline YAG first layer 100 (solid line) and a second layer (ZTA, dashed line) 102, where the second layer contains zirconia in an amount of about 20 vol% and the balance (80 vol%) is alumina, relative to the total volume of at least one second layer. Figure 9c ) depicts at least one first layer 100 comprising polycrystalline YAG and at least one second layer 102 that contains zirconia in an amount of about 16 vol% (and the balance is alumina) relative to the total volume of at least one second layer.

[0165] In one embodiment, the compositional range of at least one second layer 102 (about 5 vol% to about 30 vol% zirconia with the balance alumina) may be suitable for CTE matching and CTE matching within a percentage range to at least one first layer 100 comprising polycrystalline YAG. Thus, a multi-layer sintered ceramic body 98 is disclosed herein that includes at least one second layer 102 and at least one first layer 100 having polycrystalline YAG, the at least one second layer comprising about 5 vol% to about 30 vol%, preferably about 10 vol% to about 30 vol%, preferably about 5 vol% to about 20 vol%, preferably about 10 vol% to about 20 vol% alumina and at least one of stabilized zirconia and partially stabilized zirconia, based on the volume of the at least one second layer. In a preferred embodiment, in order to more closely match the CTE of the at least one polycrystalline YAG first layer 100, the at least one second layer 102 may include at least one of partially stabilized zirconia and stabilized zirconia in an amount by volume of about 13% to about 19%, preferably about 14% to about 18%, preferably about 15% to about 17%, more preferably about 16 vol% (with the balance alumina), based on the volume of the at least one second layer 102. These compositional ranges of the at least one second layer 102 are about 0.4×10 -6 / °C and less, preferably 0.3×10 -6 / °C and less, preferably 0.25×10 -6 / °C and less, preferably about 0.2×10 -6 / °C and less, preferably 0.15×10 -6 / °C and less, preferably 0.1×10 -6a quantity of 0.1×10-6 / °C and less, preferably 0.08×10-6 / °C and less, preferably 0.06×10-6 / °C and less, preferably 0.04×10-6 / °C and less, preferably 0.02×10-6 / °C and less, and preferably 0.01×10-6 / °C and less provides a CTE match with the at least one first layer 100 of YAG. As a percentage relative to the at least one first layer, the CTE difference (between any of the first, second, and third layers according to one embodiment) can be 5% and less, preferably 4% and less, preferably 3% and less, preferably 2.5% and less, preferably 2% and less, preferably 1.5% and less, preferably 1% and less, preferably 0.5% and less, preferably 0.25% and less, and preferably 0.1% and less (as measured relative to the at least one first layer 100). According to the methods and stable compounds disclosed herein, the zirconia of the at least one second layer can include at least one of stabilized zirconia and partially stabilized zirconia. An integral multi-layer sintered body having a maximum dimension of about 100 mm to about 625 mm has been formed, the integral multi-layer sintered body having at least one first layer 100 comprising polycrystalline YAG and at least one second layer 102 comprising about 16 vol% partially stabilized zirconia.

[0166] To provide corrosion and erosion resistance suitable for use as a component in a plasma processing chamber, a polycrystalline, integral multi-layer ceramic body having at least one first layer 100 comprising high-phase purity polycrystalline YAG (>90 vol%) is preferred. However, the formation of substantially phase-pure YAG requires careful compositional and processing control to maintain stoichiometry and thus form a sintered ceramic body comprising phase-pure YAG (composed of 37.5 + / - 0.1 mol% yttrium oxide and 62.5 + / - 0.1 mol% aluminum oxide). Other crystalline phases can typically be present, such as alumina, yttrium oxide, YAP, (YAlO3; yttrium aluminum perovskite phase) and YAM (Y4Al2O9; yttrium aluminum monoclinic phase) and combinations thereof. As a guide, Figure 10 a yttrium oxide / aluminum oxide binary phase diagram is depicted. The horizontal axis corresponds to the mixture ratio of yttrium oxide and aluminum oxide in mole percentage, while the vertical axis is the temperature in degrees Celsius. The left side of the horizontal axis corresponds to 100% alumina, while the right side corresponds to 100% yttrium oxide. Figure 10 The phase diagram shows the regions of the yttrium aluminum phases in which YAG, YAP, and YAM are formed and the conditions of mole composition and temperature necessary to produce these forms.

[0167] The crystal phase and image-based porosity of at least one first layer 100 containing YAG of a multilayer ceramic sintered body according to the embodiments disclosed herein are measured using a combination of X-ray diffraction (XRD), SEM imaging, and ImageJ image processing software. XRD is performed using a PANalytical Aeris XRD model capable of identifying crystal phases to approximately + / - 5 vol%. Figure 13 The X-ray diffraction results are depicted, confirming the formation of highly phase-pure polycrystalline YAG constituting at least one first layer 100. No other phases were identified within the detection limit of XRD. According to known phase diagrams, YAG exists as a linear compound, and thus the formation of phase-pure YAG poses challenges and requires careful composition and process control. Such phase-pure YAG is disclosed in International Patent Application No. PCT / US20 / 60918, filed November 17, 2020, which is incorporated herein by reference. The at least one first layer 100 of YAG according to one embodiment may, in some embodiments, contain an excess of alumina and / or an excess of yttrium oxide and may be substantially free or free of dopants and / or substantially free or free of sintering aids as disclosed herein. In other embodiments, the first layer containing YAG may contain sintering aids and / or dopants in the amounts disclosed herein. In an embodiment, the polycrystalline YAG first layer 100 is substantially free or free of dopants and may contain sintering aids in the amounts disclosed herein. The XRD of at least one first layer 100 of the multilayer ceramic sintered body as disclosed herein can measure up to and including approximately 95 vol% phase purity. Thus, in the embodiment depicted by the xrd results as Figure 13 described, at least one first layer 100 of the overall multilayer sintered ceramic body contains at least approximately 95 vol% of the YAG phase.

[0168] To more precisely determine the phase purity, up to and including approximately 99.8 vol%, SEM images are taken using the backscattered detection (BSD) method known to those skilled in the art. Using BSD, the YAG phase appears gray, the alumina phase appears black, the yttrium oxide phase appears white, and the porous portions (if any) also appear black. For the polycrystalline YAG sintered ceramic body according to the embodiments disclosed herein, images are taken at 5000x using the BSD method to identify the YAG, alumina, and yttrium oxide phases, and any porous portions present, as Figure 11 depicted in a).

[0169] To distinguish between the black regions containing alumina and the black regions containing porous portions, the BSD image is set to a black and white threshold when using ImageJ processing software to highlight the black regions in the BSD image that may contain porous portions or alumina, as Figure 11depicted for the same region in b). ImageJ, developed by the National Institutes of Health (NIH) in the United States, is a Java-based public domain image processing and analysis program for scientific multi-dimensional images for image processing. The BSD detector used for the measurements disclosed herein also has the ability to measure topographical features, thereby highlighting any deviations in the surface topography, such as surface porous portions. Using the topographical mode of the BSD detector, as Figure 11 depicted in a), a topographical image was taken at 5000× across the surface of the same region of the polycrystalline YAG sintered ceramic body according to Example 7, and Figure 12 the topographical image is shown in a). After threshold conversion of the topographical image in ImageJ, as Figure 12 shown in b), the regions containing surface porous portions were highlighted. Thereafter, from Figure 12 the area containing alumina and / or porous portions in the BSD image of a), the area containing surface porous portions in the Figure 12 topographical image of b) was subtracted to obtain the area % of the alumina phase contained in the polycrystalline YAG sintered ceramic body according to the embodiments disclosed herein, thereby obtaining the volume %. At least one first layer 100 of the multi-layer sintered ceramic body 98 disclosed herein may have porous portions and / or alumina phase on the surface and throughout the body. Thus, in an embodiment, the multi-layer sintered ceramic body may comprise a monolithic body that comprises YAG made according to the process disclosed herein and further comprises an alumina phase and porous portions distributed throughout the body. In other words, the structure measured on the surface (e.g., the plasma-facing surface 106) represents the structure within the volume of the bulk multi-layer sintered ceramic body that comprises YAG and in embodiments also comprises alumina. The combination of these analytical tools of multiple SEM imaging modes and ImageJ analysis can provide a determination of the phase purity with a confidence of about + / - 0.1 volume %. Using the disclosed method, the polycrystalline YAG sintered ceramic body according to Example 7 was measured to contain about 0.1 volume % to about 0.2 volume % of alumina phase, about 0.1 volume % to about 0.2 volume % of porous portions, and about 99.6 volume % to about 99.8 volume % of YAG phase. Considering measurement differences, the polycrystalline YAG sintered ceramic body may contain a YAG phase in an amount of 99.4 volume % to 99.8 volume %, and may also contain a porous portion in an amount of 0.1 volume % to 0.3 volume % and an alumina in an amount of 0.1 volume % to about 0.3 volume %.

[0170] Thus, a multi-layer sintered ceramic body having at least one first layer 100 can be formed using the materials and methods disclosed herein, where the at least one first layer 100 contains a YAG phase in an amount of 90 vol% to 99.9 vol%, preferably 90 vol% to 99.8 vol%, preferably 90 vol% to 99.7 vol%, preferably 90 vol% to 99.6 vol%, preferably 93 vol% to 99.8 vol%, preferably 93 vol% to 99.7 vol%, and preferably 93 vol% to 99.6 vol%, each based on the volume of the at least one first layer 100.

[0171] To evaluate the grain size of the at least one first layer 100 containing polycrystalline YAG, linear intercept grain size measurements were performed according to the Heyn linear intercept procedure described in ASTM standard E112 - 2010, "Standard Test Method for Determining Average Grain Size". Grain size measurements were made on an exemplary plasma-facing surface 106 (as listed in Table 4), and an average grain size of 1.1 μm to 6.3 μm was measured over 25 repetitions. The maximum and minimum grain sizes of 2 μm to 7.7 μm were also measured on the exemplary plasma-facing surface 106 of the at least one first layer 100 containing YAG. The overall multi-layer sintered ceramic body can have a plasma-facing surface 106 with a grain size such that, for example, the maximum grain size is about 8 μm or less, preferably the maximum grain size is 6 μm or less. In some embodiments, the overall multi-layer sintered ceramic body can have a plasma-facing surface 106 with an average grain size of 0.4 μm to 6.5 μm, preferably 0.4 μm to 5 μm, preferably 0.4 μm to 3 μm, preferably 0.8 μm to 6.5 μm, preferably 0.8 μm to 5 μm, preferably 0.8 μm to 3 μm, preferably 1 μm to 7 μm, preferably 1 μm to 6.5 μm.

[0172] Table 4

[0173]

[0174] To meet the requirements for corrosion resistance and erosion resistance of components used in semiconductor processing chambers, a multi-layer sintered ceramic body preferably including at least one first layer 100 is provided, where the at least one first layer has a low porosity on the plasma-facing surface 106 and / or within the layer 100. Porous portions can act as sites for initiating corrosion and erosion, and thus it is preferred that there are few porous portions, pores, or voids within the at least one first layer 100 and / or on the plasma-facing surface 106 of the first layer 100 of the multi-layer sintered body. The at least one first layer disclosed herein can have very small pores on the surface and throughout. Preferably, the at least one first layer 100 including at least one crystal phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium oxide and zirconium oxide prepared according to the methods disclosed herein is thus a monolithic layer with pores uniformly distributed throughout. In other words, the pores or voids or porosity measured on the plasma-facing surface 106 can represent the pores or voids or porosity within the body of the at least one first layer 100.

[0175] The porosity level on the sample surface is measured by using SEM images obtained from a Phenom XL scanning electron microscope at a magnification of 5000x. The images are input into ImageJ software for analysis. ImageJ is developed by the National Institutes of Health (NIH) and is a Java-based public domain image processing and analysis program for processing scientific multi-dimensional images.

[0176] The pore size and the total area containing porous portions are measured on 7 SEM images using the ImageJ software method disclosed herein. The images are taken at 5000×, and each image has a total area of approximately 53.7 μm × 53.7 μm, corresponding to a single image measurement area of approximately 2885 μm 2 .

[0177] Figure 14 The porosity results measured on an exemplary plasma-facing surface 106 of the at least one first layer 100 containing YAG are shown, with the total pore area (μm 2 ) depicted on the vertical axis and the pore size in micrometers represented on the horizontal axis. The measurements are made on 7 images taken at 5000×, each image having an area of 53.7 μm × 53.7 μm, and the total measurement area is approximately 2885 μm 2 . The total area including porous portions in any of the 7 images is measured to be from approximately 0.015 μm 2 to approximately 0.3 μm 2 , preferably from approximately 0.015 μm 2 to approximately 0.2 μm 2 , and preferably from approximately 0.015 μm 2 to approximately 0.15 μm2 The maximum pore diameter on the plasma-facing surface 106 of at least one first layer 100 containing YAG was measured to be 0.7 μm or less, and the maximum area containing the porous portion was found to be about 0.3 μm 2 or less. No pores with a pore diameter greater than 0.7 μm were measured on seven images analyzed within the plasma-facing surface 106 of at least one first layer 100 of polycrystalline YAG.

[0178] Figure 15 Depicts the cumulative partial area including the porosity (cumulative pore area) in an area measured in mm 2 counting and containing pores in μm 2 counting, expressed as the cumulative pore area (in μm Figure 14 for a given pore diameter for the seven images (from the plasma-facing surface 106) referenced in 2 / mm 2 counting). Using the SEM images and ImageJ image processing method disclosed herein, the porosity (in μm 2 counting) within each image was measured and normalized across the total image area measured (in mm 2 counting) to calculate the cumulative pore area. At least one first layer 100 containing YAG as disclosed herein contains from about 2 μm 2 / mm 2 to about 800 μm 2 / mm 2 , preferably from about 2 μm 2 / mm 2 to about 600 μm 2 / mm 2 , preferably from about 2 μm 2 / mm 2 to about 400 μm 2 / mm 2 , preferably from about 2 μm 2 / mm 2 to about 300 μm 2 / mm 2The cumulative pore area, as measured using SEM and image processing methods as disclosed herein. No pores with a pore diameter greater than 0.6 μm were measured on 7 images analyzed within the plasma-facing surface 106 of at least one first layer 100 of YAG in the multi-layer sintered ceramic body. Thus, in 7 images each having an area of approximately 54 μm × 54 μm, the multi-layer sintered ceramic body disclosed herein has at least one first layer 100 having a plasma-facing surface 106 that includes a porosity with a very low (less than 0.1% by area) area percentage corresponding to pore diameters less than 1 μm, thereby providing a corrosion-resistant and erosion-resistant plasma-facing surface 106 for the multi-layer sintered ceramic body for a plasma processing chamber.

[0179] Figure 16 a) shows a 5000× SEM image that shows a high-density sintered microstructure after a thermal etching process of the plasma-facing surface 106 of at least one first layer 100 containing a polycrystalline YAG phase. A very fine-scale porosity with few pores is depicted on the plasma-facing surface 106 of at least one first layer 100 of YAG. An almost completely dense microstructure is depicted, with a minimum porosity and pore diameters of about 1 μm and smaller being visible. The multi-layer sintered ceramic body according to one embodiment includes at least one first layer 100 containing polycrystalline YAG, the at least one first layer having a plasma-facing surface 106 that includes pores, where the pores have an approximate pore diameter of 5 μm and smaller, with sub-micron scale pore diameters ranging from about 0.1 μm to about 5 μm, preferably from about 0.1 μm to about 4 μm, preferably from about 0.1 μm to about 3 μm, preferably from about 0.1 μm to about 2 μm, and preferably from about 0.1 μm to about 1 μm. In this embodiment, the at least one first layer 100 of the multi-layer sintered ceramic body 98 containing YAG formed from the materials and processes may include pores, as measured using SEM and image processing methods as disclosed herein, with a maximum pore size of 0.1 μm to 5 μm, preferably 0.1 μm to 4 μm, preferably 0.1 μm to 3 μm, preferably 0.1 μm to 2 μm, and 0.1 μm to 1 μm. Approximately 22 pores were counted on the 54 μm × 54 μm plasma-facing surface 106.

[0180] Figure 16 b) For Figure 15 each of the 7 SEM images measured, the sum of the total surface area containing pores or porosity (in % of surface area) is depicted on the vertical axis, and the horizontal axis represents the corresponding pore diameter for a given pore area % in microns. Within a given image, the total surface area containing porosity and the total image measurement area are used to calculate the pore area %. As Figure 16As depicted, the measurements in the 7 SEM images correspond to at least a first layer 100 having a plasma-facing surface 106 that includes YAG, as measured from the SEM images and using the ImageJ software and methods disclosed herein. The plasma-facing surface includes a porosity in an amount of 0.0005% to 2%, preferably 0.0005% to 1%, preferably 0.0005% to 0.5%, preferably 0.0005% to 0.05%, preferably 0.0005% to 0.03%, preferably 0.0005% to 0.005%, preferably 0.0005% to 0.003%, preferably 0.0005% to 0.001%, preferably 0.005% to 2%, preferably 0.05% to 2%, preferably 0.5% to 2%, preferably 0.005% to 2%, preferably 0.005% to 1%, preferably 0.05% to 2%, preferably 0.05% to 1%, and preferably 0.5% to 2% by percentage of the total area. Thus, in an image of approximately 54 μm × 54 μm, the multi-layer sintered ceramic body disclosed herein includes a plasma-facing surface 106 that includes a very low (less than 1% by total area) percentage of porosity, thereby providing a corrosion-resistant and erosion-resistant surface for the multi-layer sintered ceramic body 98 of a plasma processing chamber.

[0181] The small pore / void maximum size and the minimum porosity % area of at least a first layer 100 of the multi-layer sintered body can achieve particle generation and corrosion and erosion reduction as required for use in a semiconductor reactor. This minimum porosity corresponds to a high density, which also provides corrosion-resistant and erosion-resistant properties, enabling them to be used as components in semiconductor etching and deposition applications.

[0182] Due to differences in the density of the layers, density measurements of the multi-layer body have proven challenging. Density measurements of a multi-layer sintered ceramic body (as disclosed in Example 4) are performed by dividing a sample cut from the full thickness of the multi-layer sintered body into its first and second layers and measuring the density of these layers individually. Measurements are made according to the Archimedes immersion method of ASTM B962-17, and for at least one first layer 100 of polycrystalline YAG, a density of 4.55 g / cc to 4.57 g / cc, preferably about 4.56 g / cc, is measured. The reported density value is the average of 5 measurements, and the standard deviation of the measured values (using known standards) is about 0.002. The density of a commercially available bulk YAG single crystal sample is measured using the method disclosed herein. An Archimedes density of 4.56 g / cc is obtained in 5 measurements, and this value is taken as the theoretical density of YAG as used herein. Thus, the theoretical density of at least one first layer 100 of the overall multi-layer sintered ceramic body according to one embodiment, which contains YAG, is 98.5% to 100%, preferably 99% to 100%, preferably 99.5% to 100%, preferably 99.7% to 100%, and preferably about 100% of the YAG theoretical density. The density of at least one second layer 102, which contains at least one of about 16 volume % stabilized zirconia and partially stabilized zirconia (with the balance being alumina), is measured according to the Archimedes immersion method of ASTM B962-17, and a density of about 4.32 g / cc is calculated. The volume mixing rules known in the art are used to calculate the theoretical density of at least one second layer containing alumina and at least one of about 16 volume % stabilized zirconia and partially stabilized zirconia, and a density of 4.31 g / cc to 4.33 g / cc, preferably about 4.32 g / cc, is measured and taken as the theoretical density of at least one second layer 102. Thus, the theoretical density percentage of at least one second layer 102 of the multi-layer sintered ceramic body (containing about 16 volume % zirconia with the balance being alumina) is 98% to 100%, preferably 99% to 100%, preferably 99.5% to 100%, preferably about 100% of the theoretical density. The overall multi-layer sintered ceramic body disclosed according to this embodiment has at least one first layer and at least one second layer, and the theoretical density % (also expressed as relative density, RD) of each is greater than 98%, preferably 98% to 100%, preferably 99% to 100%, preferably 99.5% to 100%, preferably about 100% of the theoretical density of the overall multi-layer sintered ceramic body.

[0183] The relative density (RD) of a given material is defined as the ratio of the measured density of a sample to the theoretical density of the same material, as shown in the following formula. The volume porosity (Vp) is calculated from the density measurement values as follows:

[0184]

[0185] Where ρ_sample is the (Archimedes) density measured according to ASTM B962-17, r_theory is the theoretical density as disclosed herein, and RD is the relative fractional density. Using this calculation, the volume porosity (Vp) level by percentage is calculated from the measured density values of each of at least one first layer containing YAG and at least one second layer containing alumina and about 16 vol% of partially stabilized zirconia of the multilayer ceramic sintered body according to Example 4 and the embodiments as disclosed herein, and is 0.04% to 2%, preferably 0.04% to 1%, preferably 0.04% to 0.8%, preferably 0.04% to 0.6%, preferably 0.04% to 0.5%, and preferably 0.04% to 0.4%.

[0186] The extremely high density of at least one first layer containing polycrystalline YAG (see, for example, Example 4) enables at least one plasma-facing surface 106 to be polished to a very low surface roughness Sa and a low peak-to-valley Sz. Polishing is performed using methods known to those skilled in the art, and the plasma-facing surface 106 of at least one first layer 100 containing polycrystalline YAG is measured to have an average surface roughness Sa of 8 nm and an average peak-to-valley Sz of 0.14 μm using the measurement method according to ISO standard 25178-2-2012 as disclosed herein. The average value of the measured values is taken over 10 repetitions. The plasma-facing surface 106 of at least one first layer 100 containing polycrystalline YAG is measured to have a maximum surface roughness Sa of 10 nm and a maximum peak-to-valley Sz of 0.21 μm. The plasma-facing surface 106 of at least one first layer 100 containing polycrystalline YAG is measured to have a minimum surface roughness Sa of 5 nm and a minimum peak-to-valley Sz of 0.057 μm. The disclosed surface characteristics of the highly dense at least one first layer containing YAG provide enhanced tolerance to corrosion and erosion, thereby providing a reduction in particle generation during use as a component in a semiconductor plasma processing chamber.

[0187] Laminates common in the art (including, for example, tape-cast and spray-dried layers) typically have a laminate material or layer exposed to plasma processing, and the laminate material or layer has a lower density than that disclosed herein and thus may not be polished to the very low surface roughness as disclosed herein. Therefore, these laminate materials or layers may not provide sufficient tolerance to the corrosive and erosive effects of the harsh plasmas used during semiconductor processing, resulting in particles being released into the plasma chamber during use.

[0188] The high density of at least one first layer of polycrystalline YAG enables a high hardness value of the plasma-facing surface 106 of the at least one first layer, and the high hardness value can provide tolerance to the erosive effect of ion bombardment used during typical plasma processes. Erosion or spalling can be caused by ion bombardment of the component or layer surface by using an inert plasma gas such as Ar. Those materials with high hardness values are preferably used as the material of the component because of their increased hardness value, which provides greater tolerance to ion bombardment and thus greater tolerance to erosion. Therefore, Vickers hardness measurements are performed on the exemplary plasma-facing surface 106 of at least one first layer 100 containing polycrystalline YAG according to ASTM standard C1327, "Standard Test Method for Vickers Indentation Hardness of Advanced Ceramics". The test equipment used for all hardness measurements is a Wilson microhardness tester, model VH1202. For the plasma-facing surface 106 of at least one first layer 100 of the multi-layer sintered ceramic body 98 as disclosed herein, the measured hardness values are at least 1200 HV, preferably at least 1400 HV, preferably at least 1800 HV, preferably at least 2000 HV, 1300 HV to 1600 HV, 1300 HV to 1500 HV, 1300 HV to 1450 HV, 1300 HV to 1400 HV, 1400 HV to 1600 HV, 1450 HV to 1600 HV, 1450 HV to 1550 HV. The measured values obtained using the Vickers hardness method known in the art are converted to SI units of GPa. The measured hardness values are 12.75 GPa to 15.69 GPa, 12.75 GPa to 14.71 GPa, 12.75 GPa to 14.22 GPa, 12.75 GPa to 13.73 GPa, 13.73 GPa to 15.69 GPa, 14.22 GPa to 15.69 GPa, preferably 14.22 GPa to 15.20 GPa. These high hardness values can contribute to enhancing the resistance to ion bombardment during semiconductor etching processes and reducing erosion during use, thus providing an extended component life when machining the multi-layer sintered ceramic body into a multi-layer sintered ceramic component with fine-scale features. Table 5 lists the hardness values of the multi-layer ceramic sintered body as disclosed herein. The average value is reported in eight test repetitions using a 2 kgf load cell / applied load for samples A, C, and B and a 0.025 kgf load for sample D.

[0189] Table 5

[0190] Sample Average value (GPa) Standard deviation Maximum value (GPa) Minimum value (GPa) A 13.47 0.69 14.7 12.4 B 14.14 0.58 15.0 13.2 C 14.5 0.4 16.1 14.5 D 14.8 1.0 16.0 12.7

[0191] In one embodiment, the average hardness of the sintered ceramic body disclosed herein, as measured according to ASTM standard C1327, is from 13.0 GPa to 16.0 GPa calculated from eight test replicates with an applied load of 0.2 kgf. In another embodiment, the average hardness of the sintered ceramic body disclosed herein, as measured according to ASTM standard C1327, is from about 13.5 GPa to 15 GPa calculated from eight test replicates with an applied load of 0.2 kgf. In other embodiments, the average hardness of the sintered ceramic body is from about 13.8 GPa to 15.8 GPa calculated from eight test replicates with an applied load of 0.025 kgf.

[0192] The surface roughness of the plasma-facing surface 106 of at least one first layer can affect the performance in a semiconductor processing chamber. Surface roughness measurements are performed using a Keyence 3D laser scanning confocal digital microscope model VK-X250X under environmental conditions of a class 1 cleanroom. The microscope is located on a TMC tabletop CSP passive tabletop isolator with a natural frequency of 2.8 Hz. This non-contact system uses a laser beam of light and an optical sensor to analyze the surface by reflected light intensity. The surface roughness parameters Sa, Sdr, and Sz are well-known in the art and are described, for example, in ISO standard 25178-2-2012. Section 4.17 of the ISO standard describes surface roughness Sa, section 4.1.6 describes Sz, and section 4.3.2 describes Sdr. ISO 25178 Surface texture (areal roughness measurement) is a collection of international standards related to surface roughness analysis compatible with this microscope. Sa represents the average roughness value calculated over a user-defined area (scaled-limited surface arithmetic mean height) on the surface of the multi-layer sintered ceramic body. Sz represents the maximum peak-to-valley distance (scaled-limited surface maximum peak-to-valley height) across a user-defined area of the multi-layer sintered ceramic body surface. Sdr is a calculated value defined as the "unrolled interfacial area ratio" and is an expression of the ratio by which the actual surface area increases over the surface area of a perfectly flat surface. The Sdr of a flat surface is assigned a value of zero, and this value increases with the slope of the surface. The larger the value, the more the surface area increases. This allows for a numerical comparison of the degree of surface area increase of the sample. This value represents the additional surface area created by the texture or surface features compared to a planar area.

[0193] The surface of the sample was laser scanned at 50X magnification using a confocal microscope to capture a detailed image of the sample. Parameters Sa (arithmetic mean height), Sz (maximum height), Ra (line roughness), and Sdr (developed interfacial area) were measured on selected areas of the polished surface (plasma-facing surface 106) of at least one layer 100 of the multi-layer sintered ceramic body. These parameters were obtained on the profiles of 7 sub-blocks. According to ISO specification 4288: Geometrical Product Specifications (GPS) - Surface texture: Profile method - Rules and procedures for the assessment of surface texture, the λchi (λ) representing the measurement sampling length or area was adjusted such that the line readings were limited to the measurements from 5 out of the 7 middle blocks. Surface areas were selected within the polished surface of the sample used for measurement. Areas that best represent the typical sample surface were selected and used to calculate Ra, Sdr, Sa, and Sz.

[0194] In one embodiment where the plasma-facing surface 106 of at least one first layer contains YAG, surface roughness measurements were carried out in accordance with ISO standard 25178-2-2012, and the Sa values on the surface were measured to be from 0.0005 μm to 2 μm, preferably from 0.0005 μm to 1.5 μm, preferably from 0.0005 μm to 1 μm, preferably from 0.0005 μm to 0.75 μm, preferably from 0.0005 μm to 0.5 μm, preferably from 0.0005 μm to 0.25 μm, preferably from 0.0005 μm to 0.125 μm, preferably from 0.0005 μm to 0.075 μm, preferably from 0.0005 μm to 0.050 μm, preferably from 0.0005 μm to 0.025 μm, preferably from 0.0005 μm to 0.020 μm, preferably from 0.0005 μm to 0.015 μm, preferably from 0.0005 μm to 0.010 μm, preferably from 0.001 μm to 0.030 μm, preferably from 0.001 μm to 0.020 μm and preferably from 0.001 μm to 0.010 μm. Table 6 below lists the Sa, Sz, and Sdr values of at least one first layer 100 according to the embodiments disclosed herein, the at least one first layer including the plasma-facing surface 106 containing YAG.

[0195] Table 6

[0196]

[0197]

[0198] Thus, at least one first layer 100 of the multilayer sintered ceramic body according to the disclosed embodiments (and as listed in Table 6) containing YAG may have a plasma-facing surface 106, as measured according to ISO standard 25178-2-2012, with a surface roughness Sa of the plasma-facing surface being from 0.0005 μm to 2 μm, preferably from 0.0005 μm to 1.5 μm, preferably from 0.0005 μm to 1 μm, preferably from 0.0005 μm to 0.75 μm, preferably from 0.0005 μm to 0.5 μm, preferably from 0.0005 μm to 0.25 μm, preferably from 0.0005 μm to 0.125 μm, preferably from 0.0005 μm to 0.075 μm, preferably from 0.0005 μm to 0.050 μm, preferably from 0.0005 μm to 0.025 μm, preferably from 0.0005 μm to 0.020 μm, preferably from 0.0005 μm to 0.015 μm, preferably from 0.0005 μm to 0.010 μm, preferably from 0.001 μm to 0.030 μm, preferably from 0.001 μm to 0.020 μm and preferably from 0.001 μm to 0.010 μm.

[0199] According to Table 6, at least one first layer 100 of the multilayer sintered ceramic body according to the embodiments disclosed herein containing YAG may have a plasma-facing surface 106, as measured according to ISO standard 25178-2-2012, with a peak-to-valley height Sz of the plasma-facing surface being from 0.3 μm to 5 μm, preferably from 0.3 μm to 4 μm, preferably from 0.3 μm to 3 μm, preferably from 0.3 μm to 2 μm, preferably from 0.3 μm to 1 μm, preferably from 0.65 μm to 5 μm, preferably from 1 μm to 5 μm, preferably from 2 μm to 5 μm, preferably from 0.35 μm to 3 μm and preferably from 0.5 μm to 1 μm.

[0200] According to Table 6, at least one first layer 100 of the multilayer sintered ceramic body according to the embodiments disclosed herein containing YAG may have a plasma-facing surface 106, as measured according to ISO standard 25178-2-2012, with a developed interfacial area Sdr of the plasma-facing surface being 5×10 -5 to 550×10 -5 preferably 30×10 -5 to 400×10 -5 preferably 30×10 -5 to 200×10 -5 and preferably 40×10 -5 to 100×10 -5 .

[0201] To evaluate the performance in halogen-based plasma applications, etching was performed on a sintered ceramic body prepared according to an embodiment as described below, the sintered ceramic body including at least a first layer 100 containing YAG.

[0202] To evaluate the etching performance, a polished ceramic sample having a plasma-facing surface of a first layer of YAG with dimensions of 6 mm × 6 mm × 2 mm was mounted onto a c-plane sapphire wafer using a silicone-based thermal compound. The area of each part was blocked from exposure to the etching process by bonding a 5 mm × 5 mm square sapphire ceramic to the sample surface.

[0203] The dry etching process was performed using an industry-standard Plasma-Therm Versaline DESC PDC deep silicon etcher. The etching was completed using a 2-step process with a total duration of 6 hours. The etching method was carried out at a pressure of 10 mTorr, a bias voltage of 600 V, and an ICP power of 2000 W. The etching method was divided into a first etching step at a CF4 flow rate of 90 standard cubic centimeters per minute (sccm), an oxygen flow rate of 30 sccm, and an argon flow rate of 20 sccm, and a second etching step at an oxygen flow rate of 100 sccm and an argon flow rate of 20 sccm, where each of the first etching step and the second etching step was carried out for 300 seconds and repeated for a combined duration of 6 hours. The etching conditions selected here to evaluate the sample performance were such that the disclosed materials were subjected to extreme etching conditions to distinguish the performance. After the etching procedure was completed, the surface roughness parameters Sa, Sz, and Sdr were measured using the method disclosed herein. Table 7 lists the results after etching (using the 2-step process disclosed herein) on various samples having a plasma-facing surface 106 of at least a first layer 100 containing YAG.

[0204] Table 7

[0205]

[0206] Exemplary plasma-facing surfaces 106 of at least a first layer 100 containing YAG were made with an excess of alumina (Samples 311 and 322), zirconia doping (Sample 298), stoichiometric YAG (Samples 454 and 223), and a reduced relative density (RD) (Sample 454-1). As listed in Table 7, the process conditions (Process) are listed as the temperature T (°C), pressure P (MPa), and time t (minutes) used to prepare each of the individual samples according to the method disclosed herein. Where applicable, annealing was carried out in air at 1400 °C for 8 hours.

[0207] In one embodiment, the present disclosure relates to a multi-layer sintered ceramic body and / or a component made therefrom, the multi-layer sintered ceramic body having at least one first layer 100 comprising YAG, the at least one first layer having a plasma-facing surface 106 that provides an arithmetic mean height Sa of less than 15 nm, more preferably less than 13 nm, more preferably less than 10 nm, more preferably less than 8 nm, and more preferably less than 5 nm and not exceeding a specific value in the unetched area before an etching or deposition process in accordance with Section 4.1.7 of ISO standard 25178-2-2012.

[0208] In one embodiment, the present disclosure relates to a multi-layer sintered ceramic body and / or a component made therefrom, the multi-layer sintered ceramic body having at least one first layer 100 comprising polycrystalline YAG, the at least one first layer having a plasma-facing surface 106 that provides a maximum height Sz of less than 5.0 μm, more preferably less than 4.0 μm, most preferably less than 3.5 μm, more preferably less than 2.5 μm, more preferably less than 2 μm, and more preferably less than 1.5 μm and not exceeding a specific value before an etching or deposition process in accordance with ISO standard 25178-2-2012.

[0209] In one embodiment, the present disclosure relates to a multi-layer sintered ceramic body and / or a component made therefrom, the multi-layer sintered ceramic body having at least one first layer 100 comprising polycrystalline YAG, the at least one first layer having a plasma-facing surface 106 that provides a developed interface area Sdr of less than 1500×10 -5 、more preferably less than 1200×10 -5 、more preferably less than 1000×10 -5 、more preferably less than 800×10 -5 、more preferably less than 600×10 -5 and more preferably less than 400×10 -5 and not exceeding a specific value before an etching or deposition process in accordance with Section 4.1.7 of ISO standard 25178-2-2012.

[0210] In one embodiment, the present disclosure relates to a multi-layer sintered ceramic body and / or a component made therefrom, the multi-layer sintered ceramic body having at least one first layer comprising polycrystalline YAG, the at least one first layer having a plasma-facing surface 106 that provides an arithmetic mean height Sa of from 0.0005 μm to 2 μm, preferably from 0.0005 μm to 1.5 μm, preferably from 0.0005 μm to 1 μm, preferably from 0.0005 μm to 0.75 μm, preferably from 0.0005 μm to 0.5 μm, preferably from 0.0005 μm to 0.25 μm, preferably from 0.0005 μm to 0.125 μm, preferably from 0.0005 μm to 0.075 μm, preferably from 0.0005 μm to 0.050 μm, preferably from 0.0005 μm to 0.025 μm, preferably from 0.0005 μm to 0.020 μm, preferably from 0.0005 μm to 0.015 μm, preferably from 0.0005 μm to 0.010 μm, preferably from 0.001 μm to 0.030 μm, preferably from 0.001 μm to 0.020 μm, preferably from 0.001 μm to 0.010 μm and preferably about 0.008 μm and not exceeding a specific value after an etching or deposition process as disclosed herein in accordance with section 4.1.7 of ISO standard 25178-2-2012.

[0211] In one embodiment, the present disclosure relates to a multi-layer sintered ceramic body and / or a component made therefrom, the multi-layer sintered ceramic body having at least one first layer comprising polycrystalline YAG, the at least one first layer having a plasma-facing surface 106 that provides a maximum height Sz of less than 3.8 μm, preferably less than 2.8 μm, preferably less than 2.5 μm, preferably from 0.1 μm to 2.5 μm, preferably from 0.1 μm to 1.5 μm, preferably from 0.1 μm to 1.0 μm, preferably from 0.1 μm to 0.5 μm and preferably about 0.1 μm to 0.3 μm and not exceeding a specific value after an etching or deposition process as disclosed herein in accordance with section 4.1.7 of ISO standard 25178-2-2012.

[0212] In one embodiment, the present disclosure relates to a multi-layer sintered ceramic body and / or a component made therefrom, the multi-layer sintered ceramic body having at least one first layer comprising polycrystalline YAG, the at least one first layer having a surface roughness less than 3000×10 -5 、more preferably less than 2500×10 -5 、more preferably less than 2000×10 -5 、more preferably less than 1500×10 -5 、more preferably less than 1000×10 -5And more preferably a plasma-facing surface 106 having an expanded interface area Sdr of less than 800×10-5 and not exceeding a specific value. By using the above-described multi-layer sintered ceramic body according to the embodiments disclosed herein, a material with significant corrosion and erosion resistance is provided, which allows continuous and long-term use as a component in etching and deposition processes. This corrosion and erosion resistant material minimizes particle generation through improved surface characteristics as disclosed herein, thereby providing improved performance during use and reducing contamination of semiconductor substrates during processing.

[0213] The starting powders and powder mixtures of extremely high purity for preparing at least one first layer 100 as disclosed herein can provide corrosion and erosion resistance, enabling use as components in semiconductor etching and deposition applications. This high purity provides a chemically inert, plasma-facing surface 106 (as used herein, the term inert is intended to mean chemically inactive), which can prevent the plasma-facing surface 106 of at least one first layer 100 from being roughened by halogen-based gaseous substances, which otherwise can chemically attack and etch or erode by ion bombardment those materials made from powders and powder mixtures of lower purity. Impurities and contaminants within at least one first layer 100 act as sites for initiating corrosion and erosion, and thus high purity (and correspondingly low impurity content, expressed in ppm of contaminants) is preferred within at least one first layer 100 of the multi-layer corrosion-resistant sintered ceramic body, particularly on the plasma-facing surface 106. Table 9 lists the impurities of an exemplary powder mixture according to one embodiment, the exemplary powder mixture being sintered to form at least one first layer 100, which at least one first layer comprises substantially phase-pure polycrystalline YAG.

[0214] According to the disclosure herein, a multi-layer sintered ceramic body having a plasma-facing surface 106 of at least one first layer comprising an amount of yttrium aluminum garnet (YAG) phase greater than 90 volume % can be formed by in-situ reactive sintering during a sintering step through a combination of characteristics of the particle size distribution, purity, and / or surface area of the powder mixture as disclosed herein. In an embodiment, the powder mixture comprises crystalline powders of yttrium oxide and aluminum oxide. In other embodiments, in addition to the crystalline powders of yttrium oxide and aluminum oxide, the powder mixture can also be calcined and comprise less than about 10 volume % of YAG, preferably less than 8 volume % of YAG, and preferably less than 5 volume % of YAG; in other embodiments, powder mixtures free or substantially free of a YAG phase (comprising crystalline powders of yttrium oxide and aluminum oxide) are disclosed herein. In other embodiments, it can be preferred that the powder mixture has a specific surface area greater than 2m 2 / g. In other embodiments, it can be preferred that the powder mixture is free of a specific surface area of about 2m 2 / g and greater YAG phases in order to form at least a first layer of a multi-layer sintered ceramic body comprising YAG by an in-situ, reactive phase sintering process as disclosed herein. All purity measurements disclosed herein are measured above the reporting limit for a particular element and are accomplished using ICP-MS (Inductively Coupled Plasma Mass Spectrometry) from an Agilent 7900 ICP-MS model G8403. Liquid samples are introduced into the ICP-MS in the form of a fine aerosol which is ionized in the plasma discharge and subsequently separated using a quadrupole mass analyzer known to those skilled in the art. The detection limit for identifying the presence of lighter elements using the ICP-MS method as disclosed herein is higher than the reporting limit for heavier elements. In other words, heavier elements such as Sc and greater are detected with a higher precision (e.g., as low as 0.06 ppm) compared to those lighter elements such as from Li to Al (e.g., detected with a precision as low as 0.7 ppm). Thus, the impurity content of those powders containing lighter elements such as from Li to Al can be determined to be about 0.7 ppm and greater, and the impurity content of heavier elements from Sc (scandium) to U (uranium) can be determined to be about 0.06 ppm and greater. Using the ICPMS method as disclosed herein, silica can be detected in amounts as low as about 14 ppm, while amounts of K (potassium) and Ca (calcium) of 1.4 ppm and greater can be identified. Iron can be detected precisely in amounts as low as 0.14 ppm and greater. The total impurity content as disclosed herein does not include silica.

[0215] As measured using the ICPMS method, the plasma-facing surface 106 of at least a first layer 100 comprising polycrystalline YAG can have a total impurity content of less than 100 ppm, preferably less than 75 ppm, less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably less than 10 ppm, preferably less than 8 ppm, preferably less than 5 ppm, preferably 5 ppm to 30 ppm, preferably 5 ppm to 20 ppm, relative to the total mass of at least a first layer comprising polycrystalline YAG. The total impurity content as disclosed herein does not include Si in the form of silica.

[0216] The detection limit for identifying the presence of lighter elements using the ICP-MS method as disclosed herein is higher than the reporting limit for heavier elements. In other words, heavier elements such as Sc and higher are detected with higher precision (e.g., as low as 0.06 ppm) compared to lighter elements such as those from Li to Al (e.g., detected with a precision as low as 0.7 ppm). Thus, the impurity content of powders containing lighter elements such as those from Li to Al can be determined to be about 0.7 ppm and greater, and the impurity content of heavier elements from Sc (scandium) to U (uranium) can be determined to be about 0.06 ppm and greater. Using the ICPMS method as disclosed herein, amounts of silica as low as about 14 ppm can be detected, while amounts of K (potassium) and Ca (calcium) of 1.4 ppm and greater can be identified. Iron can be detected precisely at amounts as low as 0.14 ppm.

[0217] Known sintering aids such as SiO2, MgO, CaO, Li2O, and LiF promote densification, and LiF in particular is known to promote grain growth, thereby increasing the grain size in YAG and spinel. However, these sintering aids can reduce corrosion resistance, strength, and performance in etching and deposition applications. Thus, in some embodiments, at least one first layer 100 of a multi-layer sintered ceramic body as disclosed herein can be formed from at least one powder mixture having a calcium oxide, magnesium oxide, lithium oxide, and / or lithium fluoride content of about 2 ppm or less, each relative to the total mass of the powder mixture. The high purity of the powder mixture (which can be calcined and then sintered using the methods disclosed herein) is thus transferred to the multi-layer sintered ceramic body. In embodiments as disclosed herein, for example, the multi-layer sintered ceramic body can have at least one first layer 100 that comprises at least one crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium oxide and zirconium oxide, wherein each of the at least one first layer 100 comprises silica in an amount of from 14 ppm to 100 ppm, preferably from 14 ppm to 75 ppm, preferably from 14 ppm to 50 ppm, preferably from 14 ppm to 25 ppm, preferably from 14 ppm to 20 ppm, preferably about 14 ppm, each relative to the mass of the at least one first layer 100. In other embodiments, each of the at least one first layer 100 can comprise at least one of magnesium oxide, lithium oxide / lithium fluoride, and / or calcium oxide in an amount of from about 2 ppm to 100 ppm, preferably from about 2 ppm to 75 ppm, preferably from about 2 ppm to 50 ppm, preferably from about 2 ppm to 25 ppm, preferably from about 2 ppm to 20 ppm, preferably from about 2 ppm to 10 ppm, each relative to the mass of the at least one first layer 100. To increase strength and provide chemical inertness in at least one first layer 100 that comprises at least one crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and zirconium oxide and aluminum oxide, it is preferred that each of the at least one first layer 100 does not comprise Li or LiF in an amount greater than about 2 ppm, each relative to the mass of the at least one first layer 100. Thus, in additional embodiments, each of the at least one first layer 100 that comprises at least one crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and zirconium oxide and aluminum oxide can comprise lithium fluoride, calcium oxide, and / or magnesium oxide in an amount of from about 2 ppm to 100 ppm, preferably from about 2 ppm to 75 ppm, preferably from about 2 ppm to 50 ppm, preferably from about 2 ppm to 25 ppm, preferably from about 2 ppm to 20 ppm, each relative to the mass of the at least one first layer 100.

[0218] In a preferred embodiment, each of at least one first layer comprising polycrystalline YAG can have a purity of 99.99% and higher, preferably 99.995% and higher, relative to a material having 100% purity, as measured using the ICPMS method as disclosed herein.

[0219] In an embodiment, each of at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium oxide and zirconium oxide may comprise Si in the form of silica in an amount of 14 ppm to 100 ppm, preferably 14 ppm to 75 ppm, preferably 14 ppm to 50 ppm, preferably 14 ppm to 25 ppm, preferably 14 ppm to 20 ppm, and preferably about 14 ppm, each relative to the total mass of the at least one first layer.

[0220] In an embodiment of the multi-layer sintered ceramic body disclosed herein, each of at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium oxide and zirconium oxide can be made with an optional dopant such as a rare earth oxide selected from the group consisting of Sc, La, Er, Ce, Cr, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu and their oxides and combinations, the amount of the dopant being ≥ 0.002 wt%, preferably ≥ 0.0035 wt%, preferably ≥ 0.005 wt%, and preferably ≥ 0.0075 wt%, and the dopant can be added to the starting powder or powder mixture in step a, b, or c.

[0221] In an embodiment of the multi-layer sintered ceramic body disclosed herein, at least one first layer 100 of the aforementioned ceramic sintered body can be made with an optional dopant such as a rare earth oxide selected from the group consisting of Sc, La, Er, Ce, Cr, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Tm, Yb, and Lu and their oxides and combinations, the amount of the dopant being ≤ 0.05 wt%, preferably ≤ 0.03 wt%, preferably ≤ 0.01 wt%, and preferably 0.002 wt% to 0.02 wt%, and the dopant can be added to the starting powder or powder mixture in step a, b, or c.

[0222] In an embodiment of the multilayer sintered ceramic body as disclosed herein, at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium and zirconium oxides can be made without the foregoing dopants. Specifically, for semiconductor chamber applications that require chemical inertness and combined high strength with corrosion and erosion resistance, each of at least one first layer 100 of the multilayer sintered ceramic body comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium and zirconium oxides can be free or substantially free of dopants. Thus, in certain embodiments, the multilayer sintered ceramic body having at least one first layer 100 comprising at least one polycrystalline ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttrium and zirconium oxides is substantially free or free of at least one or all of the foregoing dopants.

[0223] According to some embodiments, an excess of yttrium oxide and / or alumina within the polycrystalline YAG layer 100 is not considered a dopant or a sintering aid as long as they can remain in at least one first layer. The high purity and corresponding low impurities of the plasma-facing surface 106 of the at least one first layer disclosed enable the particle generation and corrosion and erosion reduction required for use in a semiconductor reactor. For at least one first layer 100 comprising polycrystalline YAG, a purity of, for example, 99.99% and higher, preferably 99.995% and higher, preferably 99.999% and higher, preferably 99.9995% and higher, preferably about 99.9999% can be measured.

[0224] The dielectric loss / tanδ of at least one first layer 100 and at least one second layer 102 of polycrystalline YAG are listed in Table 8 below. The high purity of the corresponding layers constituting the multilayer sintered ceramic body provides a low loss tangent of 5.5×10 -3 and less at 1 MHz and less than 1×10 -4 at 1 GHz for at least one first layer comprising YAG and less than 0.0007 for at least one second layer comprising alumina and about 16 vol% of partially stabilized zirconia. Measurements are performed on exemplary solid bodies of each material.

[0225] Table 8

[0226] Material Frequency Dielectric constant Loss tangent YAG 1 MHz 11.56 <0.0001 YAG 1 MHz 11.65 0.0055 YAG 1 GHz 11.03 <0.0001 YAG 1 GHz 11.06 <0.0001 Aluminum oxide 16 volume % zirconia 1 MHz 12 <0.0007

[0227] However, these corrosion- and erosion-resistant materials pose challenges to sintering to the high densities required for use in semiconductor etching and deposition chambers. Thus, pressure-assisted sintering methods are generally required, and in preferred embodiments, pressure- and current-assisted sintering methods are required.

[0228] According to another embodiment, there is disclosed herein a monolithic multi-layer sintered ceramic body comprising at least one first layer 100, the at least one first layer comprising magnesium aluminate spinel; at least one second layer 102, the at least one second layer comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia; and at least one third layer 103, the at least one third layer comprising a multiphase layer containing at least YAG, alumina and zirconia, wherein the zirconia comprises at least one of unstabilized zirconia, stabilized zirconia and partially stabilized zirconia, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between the at least one first layer, the at least one second layer and the at least one third layer, as measured according to ASTM E228-17 in the temperature range from 25 °C to 1700 °C or in the temperature range from 200 °C to 1400 °C, is from 0 to 0.75×10-6 / °C, preferably from 0 to 0.7×10-6 / °C, preferably from 0 to 0.6×10-6 / °C, preferably from 0 to 0.5×10-6 / °C, preferably from 0 to 0.45×10-6 / °C, preferably from 0 to 0.4×10-6 / °C, preferably from 0 to 0.35×10-6 / °C, preferably from 0 to 0.3×10-6 / °C, preferably from 0 to 0.25×10-6 / °C, preferably from 0 to 0.2×10-6 / °C, preferably from 0 to 0.15×10-6 / °C, preferably from 0 to 0.1×10-6 / °C, preferably from 0 to 0.08×10-6 / °C, preferably from 0 to 0.04×10-6 / °C, and preferably from 0 to 0.02×10-6 / °C. These ranges of the absolute value of the CTE difference between the at least one first layer containing magnesium aluminate spinel and the at least one second layer and the at least one third layer correspond to a CTE difference of at least 9% and less, preferably 7% and less, preferably 5% and less, preferably 3% and less, preferably 2% and less, preferably 1.5% and less, preferably 1% and less, preferably 0.5% and less, and preferably 0.1% and less (as measured relative to the at least one first layer 100 containing magnesium aluminate spinel) by percentage between any of the at least one first layer, the at least one second layer and the at least one third layer. In the temperature range from ambient temperature (or at least from 200 °C as depicted in the drawings) to about 1700 °C (or at least to 1400 °C as depicted in the drawings), the at least one first layer, the at least one second layer and the at least one third layer are CTE-matched within the disclosed ranges to form a monolithic multi-layer sintered ceramic body.

[0229] Figure 17 a), Figure 17 b) and Figure 17c) shows the CTE measurements of exemplary materials for forming at least a first layer and at least a second layer of a monolithic multi-layer sintered ceramic body in the temperature range from ambient temperature (or at least from 200 °C as depicted in the figures) to about 1700 °C (or at least to 1400 °C as depicted in the figures). All CTE measurements disclosed herein are conducted in accordance with ASTM E228-17. CTE measurements are made on the exemplary bulk materials. Figure 17 a) depicts a first layer 100 of magnesium aluminate spinel and a second layer 102 comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 25 vol%. Figure 17 b) depicts a first layer of spinel and a second layer 102 comprising alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 16 vol% zirconia and the balance is alumina. Figure 17 c) depicts the CTE measurements of at least a first layer 100 of magnesium aluminate spinel and at least a second layer 102 comprising alumina and zirconia in the temperature range from 200 °C to 1400 °C, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia in an amount of about 20 vol% zirconia and the balance is alumina. The composition of the at least one second layer 102 and at least one third layer 103 of ZTA can be varied to match the CTE of the at least one first layer 100 comprising spinel. The composition range of the at least one second layer 102 comprising zirconia and alumina (16 vol% to 25 vol% zirconia and the balance is alumina) can be suitable for CTE matching with the at least one first layer 100 comprising spinel. Thus, a multi-layer sintered ceramic body is disclosed herein, the multi-layer sintered ceramic body comprising at least a second layer, the at least one second layer comprising from about 16 vol% to about 25 vol% zirconia (and the balance is alumina); at least one first layer 100, the at least one first layer comprising magnesium aluminate spinel; and at least one third layer, the at least one third layer having a CTE that matches the CTE of the at least one first layer and the at least one second layer. To more closely match the CTE of the spinel first layer 100, second layer 102, and third layer 103 according to one embodiment, the second layer 102 comprises from about 15% to about 25%, preferably from about 18% to about 20%, more preferably about 20% zirconia by volume (and the balance is alumina). These composition ranges of the at least one second layer 102 can be in the range of about 0.45×10 -6 / °C and less, preferably about 0.4×10 -6 / °C and less, preferably about 0.3×10 -6 / °C and less, preferably about 0.25×10 -6 / °C and less, preferably about 0.2×10 -6 / °C and less, preferably 0.15×10 -6 / °C and less, preferably 0.1×10 -6 / °C and less, preferably 0.08×10-6 / °C and less, preferably 0.06×10-6 / °C and less, preferably 0.04×10-6 / °C and less, preferably 0.02×10-6 / °C and less, and preferably 0.01×10-6 / °C and less amounts provide a CTE match with at least one first layer 100 of spinel. As a percentage relative to at least one first layer, the CTE difference (between any of the first, second, and third layers according to one embodiment) can be 6% and less, preferably 5% and less, preferably 4% and less, preferably 3% and less, preferably 2% and less, preferably 1.5% and less, preferably 1% and less, preferably 0.5% and less, and preferably 0.25% and less (as measured relative to at least one first layer 100 containing spinel). According to the methods and stable compounds disclosed herein, the zirconia can be at least one of stabilized zirconia and partially stabilized zirconia. The CTE variation between at least one second layer 102 (containing zirconia and alumina), at least one first layer (containing magnesium aluminate spinel), and at least one third layer (containing a combination of the first and second layers) is within the disclosed range for successfully fabricating the monolithic multi-layer sintered ceramic body disclosed herein.

[0230] Figure 18 Depicts the x-ray diffraction results of a calcined powder mixture (calcined at 850°C for 4 hours) of magnesia and alumina (with a small amount of spinel phase formed) that forms at least one first layer 100 containing the magnesium aluminate spinel phase MgAl2O4 in batches (upon sintering) according to an embodiment of the monolithic multi-layer sintered ceramic body disclosed herein. The spinel phase is formed from a powder mixture of starting powders containing magnesia and alumina through an in-situ reactive sintering step. In some preferred embodiments, at least one first layer 100 containing spinel is substantially free or free of dopants, and substantially free or free of sintering aids, and substantially free or free of LiF. In other embodiments, the spinel first layer can contain sintering aids in the amounts disclosed herein (in addition to magnesia, which is the main component of the spinel).

[0231] Figure 19A 1000× SEM image of a high-density sintered microstructure of at least a first layer 100 comprising magnesium aluminate spinel, according to one embodiment disclosed herein, is shown. The at least a first layer 100 comprising spinel is free or substantially free of dopants, sintering aids, and LiF as disclosed herein. An almost completely dense microstructure with minimal porosity is depicted.

[0232] According to this embodiment where at least a first layer comprises spinel, a Sa of about 5 nm to about 20 nm can be measured across the surface using the surface roughness measurement method disclosed herein.

[0233] According to another embodiment, there is disclosed herein a monolithic multi-layer sintered ceramic body comprising at least one first layer comprising at least one polycrystalline ceramic material containing yttrium oxide and zirconium oxide, wherein zirconium oxide is present in an amount of not less than 10 mol% and not more than 25 mol%; at least one second layer 102 comprising alumina and zirconium oxide, wherein the zirconium oxide comprises at least one of stabilized zirconia and partially stabilized zirconia; and at least one third layer 103 comprising multiple phases of at least YAG, alumina and zirconium oxide, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between at least one first layer, at least one second layer and at least one third layer is from 0 to 0.75×10-6 / °C, preferably from 0 to 0.7×10-6 / °C, preferably from 0 to 0.6×10-6 / °C, preferably from 0 to 0.5×10-6 / °C, preferably from 0 to 0.45×10-6 / °C, preferably from 0 to 0.4×10-6 / °C, preferably from 0 to 0.35×10-6 / °C, preferably from 0 to 0.3×10-6 / °C, preferably from 0 to 0.25×10-6 / °C, preferably from 0 to 0.2×10-6 / °C, preferably from 0 to 0.15×10-6 / °C, preferably from 0 to 0.1×10-6 / °C, preferably from 0 to 0.08×10-6 / °C, preferably from 0 to 0.06×10-6 / °C, preferably from 0 to 0.04×10-6 / °C, preferably from 0 to 0.02×10-6 / °C, preferably from 0 to 0.01×10-6 / °C, as measured in the temperature range from 25°C to 1700°C or in the temperature range from 200°C to 1400°C according to ASTM E228-17. These ranges of the absolute value of the CTE difference between at least one first layer (wherein zirconium oxide is present in an amount of not less than 10 mol% and not more than 25 mol%) containing yttrium oxide and zirconium oxide and the second and third layers correspond to a CTE difference of at least one first layer, at least one second layer and at least one third layer of 8% or less, preferably 6.5% or less, preferably 5% or less, preferably 4% or less, preferably 3% or less, preferably 2% or less, preferably 1% or less, preferably 0.5% or less, and preferably 0.1% or less by percentage between any of at least one first layer, at least one second layer and at least one third layer (as measured relative to at least one first layer 100). In the temperature range from ambient temperature (or at least from 200°C as depicted in the drawings) to about 1700°C (or at least to 1400°C as depicted in the drawings), at least one first layer, at least one second layer and at least one third layer are CTE-matched within the disclosed ranges to form a monolithic multi-layer sintered ceramic body.

[0234] Figure 20 a), Figure 20 b) and Figure 20c) shows CTE measurements of exemplary materials for forming at least a first layer and at least a second layer of an integral multi-layer sintered ceramic body in the temperature range from ambient temperature (or at least from 200 °C as depicted in the figures) to about 1700 °C (or at least to 1400 °C as depicted in the figures). All CTE measurements disclosed herein are performed in accordance with ASTM E228-17. CTE measurements are made on the exemplary bulk materials. Figure 20 a) depicts at least a first layer 100 comprising about 20 mol% zirconia and the balance yttria, and at least a second layer 102 having 16 vol% zirconia and the balance alumina. Figure 20 b) depicts at least a first layer 100 comprising about 20 mol% zirconia and the balance yttria, and at least a second layer 102 having at least one of about 20 vol% partially stabilized zirconia and stabilized zirconia and the balance alumina. Figure 20 c) depicts at least a first layer 100 comprising about 25 mol% zirconia and the balance yttria, and at least a second layer 102 comprising about 25 vol% zirconia (relative to the volume of the at least one second layer) and the balance alumina. Variations of this embodiment may include at least a first layer 100 comprising at least one crystalline phase of a ceramic material, the at least one crystalline phase comprising yttria and zirconia, wherein zirconia is present in an amount of not less than 10 mol% ZrO2 and not greater than 25 mol% ZrO2, preferably not less than 12 mol% and not greater than 23 mol% ZrO2, preferably not less than 15 mol% and not greater than 25 mol% ZrO2, preferably not less than 18 mol% and not greater than 25 mol% ZrO2, preferably not less than 10 mol% and not greater than 23 mol% ZrO2, preferably not less than 10 mol% and not greater than 20 mol% ZrO2, preferably not less than 15 mol% and preferably not greater than 23 mol% ZrO2, and the balance comprises Y2O3. These compositions of the at least a first layer 100 may be combined with the compositions of the at least a second layer 102 and at least a third layer 103 as disclosed herein, wherein the at least a second layer and the at least a third layer have a suitable composition (of zirconia and alumina) to match the CTE of the at least a first layer 100 comprising at least one crystalline phase of yttria and zirconia. In an embodiment, the at least a first layer 100 may comprise at least one crystalline phase of yttria and zirconia selected from the group consisting of a C-type solid solution, or a combination of a fluorite solid solution and a C-type solid solution, or comprising Zr3Y4O 12A group consisting of a compound phase and a C-type solid solution. The C-type solid solution refers to a yttrium rare earth oxide type solid solution. These crystal phases are consistent with the disclosed composition ranges reported in the "phase relations in the yttrium-rich part of the yttrium-zirconium oxide system" (J. Mater. Sci 12 (1977) 311-316, H.G. Scott). In one embodiment, the CTE of at least one first layer 100 (comprising 10 mol% to 25 mol% zirconium oxide and the balance being yttrium oxide) can be matched with the CTE of at least one second layer 102 comprising about 16 vol% to about 25 vol% zirconium oxide (relative to the volume of the at least one second layer) and the balance being alumina. In this embodiment, the CTE of at least one first layer 100 (comprising 10 mol% to 25 mol% zirconium oxide and the balance being yttrium oxide) can be matched with the CTE of at least one second layer 102 comprising at least one of partially stabilized zirconia and stabilized zirconia in an amount of about 16 vol% to about 25 vol% and the balance being alumina. Accordingly, a multi-layer sintered ceramic body 98 is disclosed herein, which comprises at least one second layer 102 comprising at least one of partially stabilized zirconia and stabilized zirconia in an amount of about 16 vol% to about 25 vol% (and the balance being alumina); and at least one first layer 100 comprising 10 mol% to 25 mol% zirconium oxide and the balance being yttrium oxide. In a preferred embodiment, in order to more closely match the CTE of at least one first layer 100 (comprising 10 mol% to 25 mol% zirconium oxide and the balance being yttrium oxide) and at least one second layer 102 (comprising alumina and at least one of partially stabilized zirconia and stabilized zirconia), the volume amount of zirconia comprised in each of the at least one second layer relative to the volume of the at least one second layer 102 is about 16% to about 25%, preferably about 20% to about 25%, preferably about 22% to about 25%, more preferably about 20% of at least one of partially stabilized zirconia and stabilized zirconia (and the balance being alumina). These composition ranges of the at least one second layer 102 are from about 0.55×10 -6 / °C and less, preferably 0.5×10 -6 / °C and less, preferably about 0.4×10 -6 / °C and less, preferably about 0.3×10 -6 / °C and less, preferably about 0.2×10 -6 / °C and less, preferably 0.15×10 -6 / °C and lesser amounts provide a CTE match with at least one first layer 100 (comprising 10 mole % to 25 mole % zirconia and the balance yttria). According to the methods and stable compounds disclosed herein, the zirconia constituting at least one second layer 102 can be at least one of stabilized zirconia and partially stabilized zirconia.

[0235] In an embodiment, at least one first layer 100 comprising at least one crystalline phase of yttria and zirconia is substantially free or free of dopants and / or substantially free or free of sintering aids, wherein zirconia is present in an amount of not less than 10 mole % ZrO2 and not greater than 25 mole % ZrO2. In other embodiments, at least one first layer 100 comprising at least one crystalline phase of yttria and zirconia in the amounts disclosed can comprise sintering aids and / or dopants in the amounts disclosed herein. The zirconia starting powder comprising at least one first phase 100 containing the disclosed amounts of yttria and zirconia can comprise at least one selected from the group consisting of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia.

[0236] Figure 21 a) shows an SEM image showing a non-linear interface 104 of an overall multi-layer sintered ceramic body 98 according to one embodiment, wherein at least one first layer 100 comprises at least one crystalline phase of a ceramic material comprising yttria and zirconia, wherein zirconia is present in an amount of about 20 mole %, and the balance is yttria. In certain embodiments, the zirconia of at least one first layer can be partially stabilized zirconia and comprise about 3 mole % yttria as a stabilizing compound. In other embodiments, the zirconia of at least one first layer can comprise at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. In an embodiment, at least one first layer 100 can include a reaction layer 108 adjacent to at least one second layer 102, wherein at least one second layer 102 and the reaction layer 108 form a non-linear interface 104 between these layers. As Figure 21 visible in the SEM results, the reaction layer 108 is highly dense and has minimal porosity. As measured from SEM imaging, the reaction layer 108 can have a thickness of 10 μm to 30 μm, preferably 15 μm to 30 μm, preferably 20 μm to 30 μm, preferably 25 μm to 30 μm, preferably about 20 μm. The adhesion strength of the non-linear interface 104 can be enhanced by the reaction layer 108. In an embodiment, the reaction layer 108 can comprise at least one crystalline phase selected from the group consisting of YAG, YAP, YAM, cubic crystalline phases (solid solutions comprising at least two of yttria, alumina, and zirconia), and cubic fluorite crystalline phases (solid solutions comprising at least two of yttria, alumina, and zirconia) and combinations thereof. Figure 21b) depicts a high-density sintered microstructure of the plasma-facing surface 106 of at least one first layer 100 containing approximately 20 mol% zirconia and the balance being yttria. An almost fully dense microstructure with minimal porosity is depicted.

[0237] According to one embodiment where the at least one first layer comprises a solid solution of 80 mol% yttria and 20 mol% zirconia, an average Ra of 10 nm to 25 nm was measured in 5 measurements.

[0238] As is known to those skilled in the art, multi-layer sintered bodies are typically formed from prefabricated layers or tapes that are laminated and co-sintered or laminated or deposited onto a sintered substrate and sintered. However, due to insufficient interfacial adhesion between the layers, these multi-layer laminates often suffer delamination at the interfaces between the layers, resulting in spalling and particle release during use in semiconductor reactors. Typically, the interfaces of these laminates are linear and thus do not provide the advantages of the interlocking, increased adhesion / bonding strength of the non-linear interface 104 and enhanced toughness of the multi-phase secondary interface 105 unique to the integral multi-layer sintered ceramic body disclosed herein.

[0239] Disclosed herein is a multi-layer sintered ceramic body comprising at least one first layer 100 and at least one second layer 102, the at least one first layer and the at least one second layer being adjacent and bounded by a non-linear interface 104, as Figure 22 a) and Figure 22 b) are depicted in the schematic diagrams. Also as Figure 22 a) and Figure 22 b) depict, a non-linear interface 105 is between the adjacent layers 102 and 103. As shown, the non-linear interface 104 (described in more detail herein) can provide enhanced adhesion between the at least one first layer 100 and the at least one second layer 102. This improved adhesion can be achieved by a number of factors, including increased interface length and associated increased interface area, curvature (T), the arithmetic mean of the interface (the distance of the interface from the mean interface line), non-linearity, and the interlocking effect provided by the morphology of the interface 104.

[0240] The interfaces of these layers typically have curvatures and non-linear interfaces such that the interface layer typically meanders between at least one first layer and a second layer and between at least one second layer and at least one third layer. The calculated curvature as disclosed herein can be between 1.2 and 2.2, particularly between 1.4 and 2.0. The measurement for determining the curvature is described below and is based on the increase in the interface length relative to the linear distance of the interface layer. Accordingly, a multi-layer sintered ceramic body is disclosed herein having an interface defined by at least one second layer and at least one first layer and intervening between at least one second layer and at least one third layer, wherein the interface length is increased by 20% to 70%, preferably 20% to 60%, preferably 20% to 40%, preferably 30% to 80%, preferably 40% to 80%, preferably 50% to 70%.

[0241] Accordingly, at least one second layer and at least one first layer and at least one third layer and at least one second layer can be in contact with each other at the interface, and the interface area is commensurate with the maximum dimension of the multi-layer sintered ceramic body along the interface layer.

[0242] For an integral multi-layer sintered body having a maximum dimension of 100 mm to about 625 mm, considering the curvature of at least 1.2 mentioned above, at least one second layer and at least one first layer are in contact with each other at the non-linear interface, which has an area of at least 113 cm 2 and preferably at least 452 cm 2 and preferably at least 1,018 cm 2 and preferably at least 1,810 cm 2 .

[0243] For an integral multi-layer sintered body having a maximum dimension of 100 mm to about 625 mm, considering the curvature of at least 1.4 mentioned above, at least one second layer and at least one first layer are in contact with each other at the non-linear interface, which has an area of at least 153 cm 2 and preferably at least 616 cm 2 and preferably at least 1,386 cm 2 and preferably at least 2,464 cm 2 .

[0244] For an integral multi-layer sintered body having a maximum dimension of 100 mm to about 625 mm, considering the curvature of at most 2.2 mentioned above, at least one second layer and at least one first layer are in contact with each other at the non-linear interface, which has an area of at most 15,085 cm 2 and preferably at most 14,850 cm 2 and preferably at most 14,128 cm 2 and preferably at most 9,802 cm2 , preferably at most 6,083 cm 2 , preferably at most 3,421 cm 2 and preferably at most 1,520 cm 2 in area.

[0245] For a monolithic multilayer sintered body having a maximum dimension of 100 mm to about 625 mm, taking into account the curvature of at most 2.0 mentioned above, at least one second layer and at least one first layer are in contact with each other at a non-linear interface having at most 12,468 cm 2 , preferably at most 12,272 cm 2 , preferably at most 11,676 cm 2 , preferably at most 7,852 cm 2 , preferably at most 5,028 cm 2 , preferably at most 2,828 cm 2 and preferably at most 1,256 cm 2 in area.

[0246] For a monolithic multilayer sintered body having a maximum dimension of 100 mm to about 625 mm, taking into account the curvature of at least 1.2 mentioned above, at least one second layer and at least one first layer are in contact with each other at a non-linear interface having 113 cm 2 to about 4,488 cm 2 , preferably 113 cm 2 to about 4,418 cm 2 , preferably 113 cm 2 to 4,204 cm 2 , preferably 113 cm 2 to 2,827 cm 2 , preferably 113 cm 2 to 1,918 cm 2 , preferably 113 cm 2 to 1,018 cm 2 , preferably 113 cm 2 to 452 cm 2 , preferably 452 cm 2 to about 4,488 cm 2 , preferably 452 cm 2 to about 4,418 cm 2 , preferably 452 cm 2 to 4,203 cm 2 , preferably 452 cm 2 to 2,827 cm 2 , preferably 452 cm 2 to 1,810 cm 2, preferably 1,018 cm 2 to about 4,418 cm 2 , and preferably 1,810 cm 2 to 4,376 cm 2 in area.

[0247] For a monolithic multilayer sintered body having a maximum dimension of 100 mm to about 625 mm, taking into account the above-mentioned curvature of at least 1.4, at least one second layer and at least one first layer are in contact with each other at a non-linear interface having 153 cm 2 to about 6,110 cm 2 , preferably 153 cm 2 to about 6,013 cm 2 , preferably 153 cm 2 to 5,722 cm 2 , preferably 153 cm 2 to 3,847 cm 2 , preferably 153 cm 2 to 2,464 cm 2 , preferably 153 cm 2 to 1,386 cm 2 , preferably 153 cm 2 to 616 cm 2 , preferably 616 cm 2 to about 6,110 cm 2 , preferably 616 cm 2 to about 6,013 cm 2 , preferably 616 cm 2 to 5,722 cm 2 , preferably 616 cm 2 to 3,847 cm 2 , preferably 616 cm 2 to 2,464 cm 2 , preferably 1,386 cm 2 to about 6,013 cm 2 , and preferably 2,464 cm 2 to 5,957 cm 2 in area.

[0248] For a monolithic multilayer sintered body having a maximum dimension of 100 mm to about 625 mm, taking into account the above-mentioned curvature of at most 2.2, at least one second layer and at least one first layer are in contact with each other at a non-linear interface having 378 cm 2 to about 15,085 cm 2 , preferably 378 cm 2 to about 14,850 cm 2, preferably 378 cm 2 to 14,128 cm 2 , preferably 378 cm 2 to 9,502 cm 2 , preferably 378 cm 2 to 6,083 cm 2 , preferably 378 cm 2 to 3,421 cm 2 , preferably 378 cm 2 to 1,520 cm 2 , preferably 1,520 cm 2 to approximately 15,085 cm 2 , preferably 1,520 cm 2 to approximately 14,850 cm 2 , preferably 1,520 cm 2 to 14,128 cm 2 , preferably 1,520 cm 2 to 9,502 cm 2 , preferably 1,1520 cm 2 to 6,083 cm 2 , preferably 3,421 cm 2 to approximately 14,850 cm 2 , and preferably 6,083 cm 2 to 14,710 cm 2 of area.

[0249] For a monolithic multi-layer sintered body having a maximum dimension of 100 mm to approximately 625 mm, taking into account the curvature of up to 2.0 mentioned above, at least one second layer and at least one first layer are in contact with each other at a non-linear interface having 312 cm 2 to approximately 12,468 cm 2 , preferably 312 cm 2 to approximately 12,272 cm 2 , preferably 312 cm 2 to 11,676 cm 2 , preferably 312 cm 2 to 7,852 cm 2 , preferably 312 cm 2 to 5,028 cm 2 , preferably 312 cm 2 to 2,828 cm 2 , preferably 312 cm 2 to 1,256 cm 2 , preferably 1,256 cm 2 to approximately 12,468 cm 2 , preferably 1,256 cm2 to about 12,272 cm 2 , preferably 1,256 cm 2 to 11,676 cm 2 , preferably 1,256 cm 2 to 7,652 cm 2 , preferably 1,256 cm 2 to 5,028 cm 2 , preferably 2,828 cm 2 to about 12,272 cm 2 , and preferably 5,028 cm 2 to 7,294 cm 2 in area.

[0250] Figure 24 a) and Figure 24 b) show SEM images depicting the features of an interface 104 between at least one first layer 100 and at least one second layer 102, where the straight-line distance (L) between the ends is about 54 μm, and the interface length or curve (C) measured along the interface 104 is about 90 μm, as Figure 24 depicted in the exemplary image of b). Using the calculations disclosed herein, the curvature according to Figure 24 b) is about 1.7. Nine SEM images were measured using the ImageJ software analysis disclosed herein. The average interface length was measured to be about 90 μm, indicating that the interface length (C) increased by about 66% relative to the linear distance (L). Accordingly, a multi-layer sintered ceramic body is disclosed herein that has an interface 104 defined by at least one second layer and at least one first layer, where the interface length is increased by 20% to 70%, preferably 20% to 60%, preferably 20% to 40%, preferably 30% to 80%, preferably 40% to 80%, preferably 50% to 70%. Correspondingly, at least one second layer 102 and at least one first layer 100 may be in contact with each other at the interface, and the interface area is commensurate with the maximum dimension of the multi-layer sintered ceramic body. In some embodiments, for an integral multi-layer sintered body having a maximum dimension of 100 mm to about 625 mm, at least one second layer 102 and at least one first layer 100 are in contact with each other at a non-linear interface 104 that has about 3,117 cm 2 , preferably about 3,068 cm 2 and less, preferably 2,919 cm 2 and less, preferably 78 cm 2 to about 3,117 cm 2 , preferably 78 cm 2 to about 3,068 cm 2 , preferably 78 cm 2 to 2,919 cm2 , preferably 78 cm 2 to 1,963 cm 2 , preferably 78 cm 2 to 1,257 cm 2 , preferably 78 cm 2 to 707 cm 2 , preferably 78 cm 2 to 314 cm 2 , preferably 314 cm 2 to approximately 3,117 cm 2 , preferably 314 cm 2 to approximately 3,068 cm 2 , preferably 314 cm 2 to 2,919 cm 2 , preferably 314 cm 2 to 1,963 cm 2 , preferably 314 cm 2 to 1,257 cm 2 , preferably 707 cm 2 to approximately 3,068 cm 2 , and preferably 1257 cm 2 to 3,039 cm 2 The area is. In an embodiment, preferably the first layer and the second layer are in direct contact to form a non-linear interface 104, and thus at least one first layer and at least one second layer are adjacent layers. In other embodiments, a circuit, a heating element, an RF coil / RF antenna, etc. may be disposed between the first layer and the second layer according to the needs of a particular component application, and regardless of these features, at least a portion of the first layer and the second layer may be adjacent or substantially adjacent. This increased interface length and interface area will enhance the adhesion at the non-linear interface 104 between at least one first layer 100 and at least one second layer 102.

[0251] Referring again to Figure 24 b), the width of the interface layer as shown in the figure is generally from 1 μm to 200 μm, particularly from 5 μm to 100 μm, more particularly from 10 μm to 50 μm, and even more particularly from 20 μm to 30 μm.

[0252] The volume of the first layer over the width of the above interface layer has pores with a maximum size less than 5 μm, particularly less than 3 μm, especially less than 1 μm.

[0253] The volume of the first layer over the width of the above interface layer particularly only has pores with a maximum size less than 5 μm, particularly less than 3 μm, especially less than 1 μm.

[0254] The volume of at least the first layer in the width as disclosed herein has such a structure that less than 0.2%, more preferably less than 0.15%, and most preferably less than 0.1% of the volume is occupied by the above pores.

[0255] The volume of the second layer in the width of the above interface layer has pores with a maximum size of less than 5 μm, especially less than 3 μm, and particularly less than 1 μm.

[0256] The volume of the second layer in the width of the above interface layer especially only has pores with a maximum size of less than 5 μm, especially less than 3 μm, and particularly less than 1 μm.

[0257] The volume of at least the second layer in the width as disclosed herein has such a structure that less than 0.2%, more preferably less than 0.15%, and most preferably less than 0.1% of the volume is occupied by the above pores.

[0258] Figure 23 a) shows a 500× SEM micrograph of the non-linear interface 104 of a multi-layer sintered ceramic body, where the non-linear interface 104 defined by at least one second layer 102 and at least one first layer 100 is an irregular, non-linear boundary that can include a retrograde angle in the embodiment. In Figure 23 a) In some embodiments depicted, the interface can include at least one dovetail structure and / or at least a part of the dovetail structure. In other embodiments, at least a part of the interface can include a trapezoidal shape. The curvature (T) as disclosed herein is mathematically defined as the ratio of the length C of the curve (interface) to the linear distance L between its ends, whereby T = C / L. Figure 23 The image in a) has a measured curvature of 2.7. As measured using the SEM and image processing methods as disclosed herein (measured within ImageJ software), the non-linear interface 104 as disclosed herein can have a curvature T greater than 1.02 to about 1.5, preferably greater than 1.02 to about 2.0, preferably greater than 1.02 to about 2.5, preferably greater than 1.02 to about 3.0, preferably 1.1 to about 3.0, preferably 1.3 to about 3, and preferably 1.5 to 2.7.

[0259] A straight interface (such as in the typical case of a laminate material and structure of a pre-sintered body with multiple layers applied thereon) has a curvature of about 1 to 1.02. The increased curvature of the interface 104 of the multi-layer body as disclosed herein provides an interlocking effect between the layers, thereby increasing the adhesion strength and enabling the formation of an inseparable integral multi-layer ceramic sintered body.

[0260] Figure 23 b) depicts the average interface line (IL) of the non-linear interface 104 calculated by the SEM and image processing methods. The Figure 23The exemplary SEM image of (b) is imported into ImageJ software, and a linear equation of the average interface line (IL) is obtained using the x / y coordinates corresponding to the points along the interface, as Figure 23 shown in (b), and the non-linear interface 104 is characterized by the distance of the non-linear interface 104 from the average interface line (IL). The variation in the distance (D) of the interface 104 from the average interface line (IL) is from 10 μm to 100 μm, preferably from 20 μm to 100 μm, preferably from 30 μm to 100 μm, preferably from 40 μm to 100 μm, 50 μm to 100 μm, preferably from 25 μm to 85 μm, as measured using SEM and image processing. Increasing the distance (D) from the average interface line (IL) can help enhance the adhesion and interlocking effects of the multi-layer sintered ceramic body as disclosed herein.

[0261] These reverse or retrograde angles, features, and structures can provide an anchoring effect, thereby increasing the interfacial tensile strength and adhesion across the interface 104 defined by at least one second layer 102 and at least one first layer 100.

[0262] In comparison, FIG. 5 depicts the interface of a prior art sample, where it is possible that the first sintered layer or substrate B is first formed to form a solid body, then layer D is deposited on substrate B, and the two are bonded over time, temperature, and pressure. It is evident that there is a substantially linear interface with no retrograde or interface angles and minimal or no increase in the interface length. The curvature measurement values are calculated as disclosed herein (using the image depicted in FIG. 5), whereby the length (C) of the curve (interface) and the linear distance L between its ends are measured from the SEM image imported into the ImageJ image processing software as disclosed herein. It is calculated that the curvature (T) of the prior art laminate is less than about 1.02. Thus, the interfaces of the embodiments of multi-layer bodies known in the art do not provide the beneficial features of enhanced interlayer adhesion and interlocking effects of the overall multi-layer sintered ceramic body as disclosed herein. The bright region (the middle-right region of the image) depicted in FIG. 5 corresponds to the metal layer.

[0263] As depicted in the prior art laminate of FIG. 5, there is a significant grain size variation between layer B and layer D. Layer B has large grains of approximately 20 μm to 30 μm, which may indicate a large amount of thermal history, such as multiple sintering processes. Layer D has grains of approximately 2 μm to 5 μm, which indicates much less grain growth typically caused by thermal history and sintering. This grain size difference may indicate the lamination or deposition process, whereby layer D has been deposited or laminated on layer B and subsequently sintered to form the laminate material or laminate.

[0264] The high density required for Layer B (to impart mechanical strength, high Young's modulus, and other properties) requires an extended sintering time and high temperature, resulting in excessive grain growth. Subsequently, Layer D is bonded to Substrate B at a lower temperature for a shorter duration, such that Layer D may not experience the excessive grain growth of Substrate B. This produces a layered structure with a significant difference in grain size. (The grain size is measured using, for example, the Heyn line intercept method known to those skilled in the art), and the measured grain sizes of Substrate B and Layer D are approximately 12 μm and 4 μm, respectively. This grain size difference can cause inconsistencies in properties (such as mechanical strength, Young's modulus, dielectric loss, and other properties) between the two bodies, which can lead to fracture and / or cracking.

[0265] In contrast, grain size measurements were performed on a multi-layer sintered ceramic body of an embodiment, which included: at least one first layer containing YAG and at least one second layer containing alumina, wherein the alumina contained at least one of stabilized zirconia and partially stabilized zirconia present in an amount of approximately 16 vol%. The measured grain sizes of the at least one YAG first layer and the at least one second layer were approximately 0.78 μm and 0.74 μm, respectively. These differences may be within the measurement accuracy range, and thus the multi-layer sintered ceramic body as disclosed herein may include at least one first layer and at least one second layer containing grains, wherein these grains have the same size or substantially the same size between the at least one first layer 100 and the at least one second layer 102.

[0266] The number of grains in contact across the interface can also play a role in the adhesion and strength characteristics of the non-linear interface 104. The number of grains across the interface length is counted to obtain the number of grains per μm. Figure 25 a) shows the number of grains per unit interface length (in μm) of the interface defined by the at least one first layer 100 and the at least one second layer 102 on 10 images, where a smaller number of grains per micron is preferred. In an embodiment, for a multi-layer sintered ceramic body comprising YAG as the at least one first layer 100 and a second layer having approximately 16 vol% zirconia in an alumina medium, the number of grains per μm includes 0.2 to 0.8 grains / μm, preferably 0.3 to 0.6 grains / μm, preferably 0.4 to 0.55 grains / μm, and preferably an average of approximately 0.5 grains per μm. Figure 25b) depicts the ratio of the interface length (also defined as C, the length of the curve / interface) in the disclosed image region to the linear measurement L (the linear distance between the endpoints of C), which is approximately 54 μm in 10 SEM images, and is defined herein as the tortuosity T. As measured using SEM and image processing methods, the non-linear interface 104 can have a tortuosity (T) greater than 1.02 to 3, preferably 1.1 to 3, preferably 1.2 to 3, preferably 1.3 to 3, preferably 1.3 to 2.7, and preferably an average tortuosity of about 1.7. A higher ratio of the interface length C to the linear interface length L (or tortuosity, T) is preferred to increase the adhesion strength between at least one first layer 100 and at least one second layer 102.

[0267] As described, the non-linear interface 104 can provide enhanced adhesion strength between at least one first layer 100 and at least one second layer 102. This improved adhesion strength can be achieved through an increased interface length, an increased distance from the interface line, and an interlocking effect between at least one first layer 100 and at least one second layer 102 as measured by the tortuosity T.

[0268] Now refer to Figure 26 a) and Figure 26 b), which show SEM micrographs of the microstructure of at least one third layer 103. In an embodiment, at least one third layer 103 comprises multiple phases of a ceramic material, the multiple phases comprising at least one of YAG, alumina, and unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. The multiphase structure of at least one third layer 103 can provide toughening through the interface between at least two phases, which can facilitate preferential crack propagation along an increased distance along the interface. Figure 26 a) and Figure 26 a) and b) depict large regions containing YAG and ZTA (zirconia toughened alumina), each region constituting approximately 50 area % as measured using SEM images and ImageJ software.

[0269] Preferably, a CTE match within the disclosed range is provided between at least one first layer, at least one second layer, and at least one third layer within a temperature range from ambient temperature (or at least from 200 °C as depicted in the figures) to about 1700 °C (or at least to 1400 °C as depicted in the figures) according to the method disclosed herein. Selecting materials that provide the disclosed CTE differences for the respective at least one first layer, at least one second layer, and at least one third layer can reduce the interface stresses on the non-linear interface 104 and the second interface 105, thereby improving the adhesion and strength between at least one first layer 100, at least one second layer 102, and at least one third layer 103.

[0270] In order to form a plasma processing chamber component from the disclosed multi-layer sintered ceramic body, the multi-layer sintered ceramic body can be subjected to machining, drilling, surface grinding, lapping, polishing and other processes as needed to form a multi-layer sintered component with desired through holes, surface finish and dimensional tolerances according to the component design, such as Figure 27 Schematically depicted in . Figure 27 1 shows an exemplary embodiment of a multilayer sintered ceramic body and a multilayer sintered ceramic component made therefrom. Through holes 112 may be formed through at least one first layer 100, at least one second layer 102, and at least one third layer 103 by any number of machining, grinding, and / or drilling processes as known to those skilled in the art. A multilayer sintered ceramic component formed from a sintered body as disclosed herein may have any number of through holes 112. Figure 27 a), Figure 27 b) and Figure 27 c), the through hole 112 may include a sidewall 110, wherein the sidewall 110 includes at least a portion of a crystalline phase of a ceramic material selected from the group consisting of YAG, magnesium aluminate spinel, and yttria and zirconium oxide, wherein the zirconium oxide is present in an amount of not less than 10 mol% and not more than 25 mol%. In some embodiments, the thickness of the at least one second layer 102 is maximized, and the thickness of the at least one first layer 100 and / or the at least one third layer 103 is minimized, each reaching a range of about 0.5 mm to 3 mm, preferably 0.5 mm to 1.5 mm. By maximizing the thickness of the at least one second layer 102, corrosion resistance and machinability are provided, plus the preferred characteristics of high mechanical strength, high thermal conductivity, high dielectric constant and low dielectric loss. The at least one second layer 102 made within the disclosed composition range can provide the aforementioned preferred characteristics required for high frequency chamber applications. The combination of high strength, corrosion resistance, low dielectric loss, and thermal conductivity of the multilayer sintered ceramic body as disclosed herein makes the multilayer sintered ceramic body 98 particularly suitable as a material for making dielectric windows or RF windows and many other components used in semiconductor plasma processing chambers. These include windows, covers, dielectric windows, RF windows, rings, focus rings, process rings, deposition rings, nozzles, injectors, gas injectors, showerheads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESCs), and positioning plates.

[0271] However, these necessary grinding and polishing processes always produce defects, such as cracks and / or microcracks (those cracks that are not easily visible to the eye) or sub-surface defects in the sintered ceramic parts. Figure 6The particle release from the plasma-facing surface 106 of the at least one first layer 100 depicted into the chamber is minimized, preferably minimizing the generation of surface defects and / or subsurface defects during machining. These surface defects and / or subsurface defects can cause microcracking on the plasma-facing surface 106 of the first layer 100 on a scale that is not easily visibly apparent, which can subsequently cause particle release from the plasma-facing surface 106 of the at least one first layer 100 into the plasma processing chamber. Additionally, depending on the relationship between the material type itself (in this case brittle, non-metallic ceramic), the crack or defect size (caused by machining), and the applied stress (remaining after machining, and / or due to the CTE difference between the layers, and / or occurring during use as a sintered ceramic component), the large presence of defects in the second layer 102 can lead to the fracture of the sintered body at a strength lower than the typical value of the material. This relationship between the material, crack size, and stress is based on fracture mechanics as reported by A.A. Griffith in “The phenomena of rupture and flow in solids” Phil. Trans. Roy. Soc. London, Vol. 221, pp. 582 - 593, January 1, 1921.

[0272] The residual stress remaining in the sintered body can be caused by the CTE difference between the layers, which can manifest during the heating, sintering, annealing, and cooling steps used to form the multi-layer sintered ceramic body herein. Therefore, it is preferred to minimize these internal stresses caused by the CTE difference of the subject materials by providing those materials with CTE matching (within the disclosed range) in the temperature range from ambient temperature to the sintering and annealing temperatures as disclosed herein, from ambient temperature (or at least from 200 °C as shown in the figures) to about 1700 °C (or at least to about 1400 °C as shown in the figures) as the layers.

[0273] If the CTE difference between any of the at least one first layer 100, at least one second layer 102, and / or at least one third layer 103 of the multi-layer sintered ceramic body is greater than 0.75×10 -6 / °C, then during the machining or drilling steps, greater stresses caused by CTE mismatch can be applied to at least one first layer and can result in surface or subsurface damage in the form of microcracking in at least one first layer 100. This damage to at least one first layer can lead to spalling and / or increased erosion of the layer, as well as subsequent release of particles from the plasma-facing surface 106 into the plasma processing chamber during use. Thus, to form a multi-layer sintered ceramic body having high strength, sufficient processability, and minimal surface damage to at least one first layer from machining, the CTE difference between at least one first layer 100, at least one second layer 102, and at least one third layer 103 of the multi-layer sintered ceramic body is preferably within the disclosed ranges and preferably the CTEs are matched as closely as possible, including a value of zero (wherein the CTEs are measured to be substantially identical over a temperature range from ambient temperature (or about 200 °C as depicted in the figures) to about 1700 °C according to the disclosed method). As used herein, the term "CTE matching" means that over a temperature range from ambient temperature to a sintering temperature of about 1700 °C and less, their respective CTE values differ (in absolute value) by 0 to 0.75×10 -6 and less for a combination of at least one first layer 100, at least one third layer 103, and at least one second layer 102.

[0274] Thus, in an embodiment, it is preferred that those materials be selected for the first, second, and third layers, wherein the amount of the absolute value of the difference in the coefficient of thermal expansion (CTE) of the first, second, and third layers, as measured according to ASTM E228-17 over a temperature range of 25 °C to 1700 °C or over a temperature range of 200 °C to 1400 °C, is from about 0 to less than 0.75×10-6 / °C, preferably 0 to 0.7×10 -6 / °C, preferably 0 to 0.6×10 -6 / °C, preferably 0 to 0.5×10 -6 / °C, preferably 0 to 0.45×10 -6 / °C, preferably 0 to 0.4×10 -6 / °C, preferably 0 to 0.35×10 -6 / °C, preferably 0 to 0.3×10 -6 / °C, preferably 0 to 0.25×10 -6 / °C, preferably 0 to 0.2×10 -6 / °C, preferably 0 to 0.15×10 -6 / °C, preferably 0 to 0.1×10 -6 / °C, preferably 0 to 0.08×10 -6 / °C, preferably 0 to 0.06×10 -6 / °C, preferably 0 to 0.04×10 -6 / °C, preferably 0 to 0.02×10-6 / °C, and preferably 0 to 0.01×10-6 / °C.

[0275] In embodiments where the CTEs of each of the first, second, and third layers do not cross each other within the disclosed temperature range (i.e., the absolute value of the CTE difference is non-zero within this temperature range), such as measured according to ASTM E228-17 in the temperature range of 25°C to 1700°C or in the temperature range of 200°C to 1400°C, the amount of the absolute value of the coefficient of thermal expansion (CTE) difference between the first, second, and third layers can be about 0.003×10 -6 / °C to less than 0.75×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.7×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.6×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.5×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.45×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.4×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.35×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.3×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.25×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.2×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.15×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.1×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.08×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.06×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.04×10 -6 / °C, preferably 0.003×10 -6 / °C to 0.02×10 -6 / °C, and preferably 0.003×10-6 / °C to 0.01×10 -6 / °C.

[0276] The disclosed range of the absolute value of the difference in coefficient of thermal expansion between at least one first layer, at least one second layer, and at least one third layer is preferably maintained within a certain temperature range according to the method disclosed herein. The desired range of the absolute value of the difference in coefficient of thermal expansion between the first, second, and third layers is preferably in the temperature range from ambient temperature (or at least from 200 °C as depicted in the drawings) to about 1700 °C (or at least to about 1400 °C as depicted in the drawings), preferably 200 °C to 1400 °C, and is preferably maintained within the sintering temperature range of 1000 °C to 1700 °C and / or the annealing temperature range of 900 °C to 1800 °C.

[0277] The use of the CTE-matched multi-layer sintered ceramic body disclosed herein can reduce the stress on at least one first layer 100 (thereby reducing the likelihood of particle generation in the plasma processing chamber) and improve machinability (by reducing subsurface and / or surface damage) by providing symmetric balance and matching CTE on either side of at least one second layer 102 via at least one third layer 103. Additionally, the composition of at least one second layer 102 can be selected to match the CTE of at least one first layer 100 and / or at least one third layer 103 within the disclosed range.

[0278] This reduced stress between and within the layers can reduce the impact of surface and subsurface damage during machining, thereby reducing particle generation from the plasma-facing surface 106 of at least one first layer 100 while improving the overall strength and machinability of the multi-layer ceramic sintered body (and components manufactured therefrom) disclosed herein.

[0279] When the absolute value of the CTE between any of these layers changes within these ranges, a multi-layer sintered ceramic body having high strength, improved machinability, and reduced surface and subsurface defects can be formed using the pressure-assisted method disclosed herein, particularly for multi-layer sintered ceramic bodies of large (>100 mm) size.

[0280] Equipment / Spark plasma sintering tool

[0281] The equipment for preparing the multi-layer sintered ceramic body disclosed herein is preferably a spark plasma sintering (SPS) tool, which includes: a die, the die includes side walls, the side walls include inner walls and outer walls, wherein the inner wall has a diameter defining an internal volume capable of receiving at least one ceramic powder (or at least one powder mixture, as the case may be); and an upper punch and a lower punch operably coupled to the die, wherein each of the upper punch and the lower punch has an outer wall, and the diameter defined by the outer wall is smaller than the diameter of the inner wall of the die, whereby when at least one of the upper punch and the lower punch moves within the internal volume of the die, a gap is generated between each of the upper punch and the lower punch and the inner wall of the die, wherein the gap is 10 μm to 100 μm wide, and at least one powder mixture has a specific surface area (SSA) of 1 m 2 / g to 10 m 2 / g as measured according to ASTM C1274.

[0282] As Figure 28 depicted, the pressure-assisted sintering process (and in the preferred embodiment, the pressure and current-assisted sintering process, such as SPS) disclosed herein provides for the preparation of an integral multi-layer sintered ceramic body 98 from at least three layers of powder mixtures (powder compacts) disposed in a tool set without the use of dopants and / or sintering aids. The layers of the powder mixture (depicted in Figure 28 as 100a corresponding to at least one first layer 100, 102a corresponding to at least one second layer 102, and 103a corresponding to at least one third layer 103, thus forming a powder compact) form an integral multi-layer sintered body 98 (upon in-situ sintering), and then these layers are respectively formed into at least one first layer 100, at least one second layer 102, and at least one third layer 103 of the sintered body (without forming thin films, tapes, or green compacts common in the art). In some embodiments, the deposition order of at least one of the first powder mixture and the third powder mixture can be reversed. In an embodiment, at least one of the powder mixtures can be calcined, and in other embodiments, all of the powder mixtures can be calcined. Compared with Figure 1 and Figure 2 , the pressure-assisted method produces a high-density integral multi-layer sintered ceramic body without the need to match the sintering rate of the pressureless method known to those skilled in the art. The absolute value of the CTE difference between at least one first layer 100, at least one second layer 102, and at least one third layer 103 of the multi-layer sintered body is preferably within the range disclosed herein to avoid cracking and fracture caused by CTE mismatch outside the disclosed range (which may experience cracking and fracture during sintering and during other thermal offsets such as annealing, etc.), as Figure 4 depicted.

[0283] Figure 29Depicts an SPS tool 1 having a simplified die / punch arrangement for sintering ceramic powders and / or powder mixtures. Generally, the die / punch arrangement is within a vacuum chamber (not shown), as would be recognized by one of ordinary skill in the art. Referring Figure 29 , the spark plasma sintering tool 1 includes a die system 2, the die system including side walls, the side walls including an inner wall 8 having a diameter defining an internal volume capable of receiving a ceramic powder or powder mixture 5.

[0284] Still referring Figure 29 , the spark plasma sintering tool 1 includes an upper punch 4 and a lower punch 4' operably coupled to the die system 2, wherein each of the upper punch 4 and the lower punch 4' has an outer wall 11 defining a diameter smaller than the diameter of the inner wall 8 of the die system 2, whereby when at least one of the upper punch 4 and the lower punch 4' moves within the internal volume of the die system 2, a gap 3 is created between each of the upper punch 4 and the lower punch 4' and the inner wall 8 of the die system 2.

[0285] The die system 2 and the upper punch 4 and lower punch 4' may comprise at least one graphite material. In certain embodiments, the graphite materials disclosed herein may comprise at least one isotropic graphite material. In other embodiments, the graphite materials disclosed herein may comprise at least one reinforced graphite material, such as a carbon-carbon composite, and graphite materials including fibers, particles, or sheets or meshes or other conductive materials such as layers of carbon within a matrix of an isotropic graphite material. In other embodiments, the die and the upper and lower punches may include a combination of these isotropic and reinforced graphite materials.

[0286] The graphite material for some or all of the components of the tool such as the die 6 and the punches 4 and 4' may comprise a porous graphite material, which exhibits a porosity of about 5% to about 20%, about 5% to about 17%, about 5% to about 13%, about 5% to about 10%, 5% to about 8%, about 8% to about 20%, about 12% to 20%, about 15% to about 20%, about 11% to about 20%, about 5% to 15%, 6% to about 13% and preferably about 7% to about 12%.

[0287] Preferably, the average pore diameter (pore size) of the graphite material is from 0.4 μm to 5.0 μm, preferably from 1.0 μm to 4.0 μm, and includes pores having a surface pore diameter of at most 30 μm, preferably at most 20 μm, preferably at most 10 μm. More preferably, pores having a surface pore diameter of 10 μm to 30 μm may be present.

[0288] The average grain size of the graphite material for tools as disclosed herein can be < 0.05 mm, preferably < 0.04 mm, preferably < 0.03 mm, preferably < 0.028 mm, preferably < 0.025 mm, preferably < 0.02 mm, preferably < 0.018 mm, preferably < 0.015 mm, and preferably < 0.010 mm.

[0289] The average grain size of the graphite material for tools as disclosed herein can be > 0.001 mm, preferably > 0.003 mm, preferably > 0.006 mm, preferably > 0.008 mm, preferably > 0.010 mm, preferably > 0.012 mm, preferably > 0.014 mm, preferably > 0.020 mm, preferably > 0.025 mm, and preferably > 0.030 mm.

[0290] The density of the graphite material for tools as disclosed herein can be ≥ 1.45 g / cm 3 , preferably ≥ 1.50 g / cm 3 , preferably ≥ 1.55 g / cm 3 , preferably ≥ 1.60 g / cm 3 , preferably ≥ 1.65 g / cm 3 , preferably ≥ 1.70 g / cm 3 , and preferably ≥ 1.75 g / cm 3 .

[0291] The density of the graphite material for tools as disclosed herein can be ≤ 2.0 g / cm 3 , preferably 1.90 g / cm 3 , preferably ≤ 1.85 g / cm 3 and preferably ≤ 1.80 g / cm 3 .

[0292] In an embodiment, the coefficient of thermal expansion (CTE) of the graphite material in the temperature range from about 400 °C to about 1400 °C is ≥ 3.3×10 -6 / °C, ≥ 3.5×10 -6 / °C, ≥ 3.7×10 -6 / °C, ≥ 4.0×10- 6 / °C, ≥ 4.2×10 -6 / °C, ≥ 4.4×10 -6 / °C, ≥ 4.6×10 -6 / °C, ≥ 4.8×10 -6 / °C.

[0293] In an embodiment, the coefficient of thermal expansion (CTE) of the graphite material in the temperature range from about 400 °C to 1400 °C can be ≤ 7.2×10 -6 / °C, preferably ≤ 7.0×10 -6 / °C, preferably ≤ 6.0×10 -6 / °C, preferably ≤ 5.0×10 -6 / °C, preferably ≤ 4.8×10 -6 / °C, and preferably ≤ 4.6×10 -6 / °C.

[0294] Table 9 lists the properties of exemplary graphite materials as disclosed herein.

[0295] Table 9

[0296] Property Range Density (g / cc) 1.45 to 2.0 Average grain size (μm) 1 to <50 Resistivity (Ohm-cm) 0.001 to 0.003 Flexural strength (MPa) 40-160 Compressive strength (MPa) 80-260 <![CDATA[CTE(x10 -6 / C), at 400 °C to 1400 °C]]> 3.3 to 7 Porosity % 5 to 20 Average pore diameter (μm) 0.4 to 5 Thermal K (W / mK) 40-130 Shore hardness (HSD) 55 to 59 Tensile strength (MPa) 25 to 30 Elastic modulus (GPa) 9 to 11 Impurities / ash (ppm) 3 to 500

[0297] The die system 2 includes a die 6 and optionally but preferably at least one conductive foil 7 located on the inner wall of the die, as shown in the embodiments of Figure 25 a) to Figure 25 c). The number of conductive foils on the inner wall of the die is not limited, and 1, 2, 3, 4, 5, 6, 7, 8, 9, or 10 conductive foils can be provided as circumferential gaskets between the die 6 and each of the upper punch 4 and the lower punch 4'. Thus, the inner wall 8 of the die system 2 (including at least one conductive foil, if present) and the outer wall 11 of each of the upper punch and the lower punch define a gap 3. The at least one conductive foil 7 can comprise graphite, niobium, nickel, molybdenum, platinum, and other malleable conductive materials and combinations thereof that are stable within the temperature range according to the methods disclosed herein.

[0298] In certain embodiments, the conductive foil can comprise a flexible and compressible graphite foil having one or more of the following characteristics as disclosed herein:

[0299] · The carbon content is greater than 99 wt%, preferably greater than 99.2 wt%, more preferably greater than 99.4 wt%, more preferably greater than 99.6 wt%, more preferably greater than 99.8 wt%, more preferably greater than 99.9 wt%, more preferably greater than 99.99 wt%, and more preferably greater than 99.999 wt%;

[0300] · The impurities are less than 500 ppm, preferably less than 400 ppm, more preferably less than 300 ppm, more preferably less than 200 ppm, more preferably less than 100 ppm, more preferably less than 50 ppm, more preferably less than 10 ppm, more preferably less than 5 ppm, and more preferably less than 3 ppm;

[0301] · The tensile strength of the graphite foil ranges from 4.0 MPa to 6.0 MPa, preferably from 4.2 MPa to 5.8 MPa, more preferably 4.4 MPa or 5.6 MPa; and / or

[0302] · The bulk density of the graphite foil preferably ranges from 1.0 g / cc to 1.2 g / cc, preferably from 1.02 g / cc to 1.18 g / cc, more preferably from 1.04 g / cc to 1.16 g / cc, and even more preferably from 1.06 g / cc to 1.16 g / cc.

[0303] In an embodiment, at least one foil typically comprises graphite. In certain embodiments, at least one foil that is part of a die system can include a circumferential gasket between the surface of the die and each of the upper and lower punches.

[0304] The graphite foil can improve the temperature distribution of the powder during sintering. Table 10 lists the properties of exemplary graphite foils according to embodiments disclosed herein.

[0305] Table 10

[0306] Thickness (mm) 0.030 to 0.260 <![CDATA[Density (Mg / m 3 )]]> 0.5 to 2 Tensile strength (MPa) 4.9-6.3 Resistivity (μOhm-m; 25 °C) (parallel to surface) 5 to 10 Resistivity (μOhm-m; 25 °C) (perpendicular to surface) 900 to 1100 CTE (×10-6 / °C; parallel to surface), at 350 °C to 500 °C 5 to 5.5 CTE (perpendicular to surface), at 350 °C to 500 °C <![CDATA[2×10 -4 > Compressibility (%) 40-50 Recovery rate (%) 10 to 20 Thermal conductivity (W / mK, at 25 °C; parallel to surface) 175 to 225 Thermal conductivity (W / mK, at 25 °C; perpendicular to the surface) ~5 Impurities / Ash (wt%) <0.5

[0307] Now referring to FIGS. 30a), Figure 25 b) and 30c), an SPS tool set of an embodiment with a graphite foil arrangement is shown. At least one ceramic powder (or powder mixture) 5 is disposed between at least one of the upper punch 4 and the lower punch 4', and a gap 3 is shown between the outer walls 11 of each of the upper and lower punches and the inner wall 8 of the die system 2. FIGS. 30a), 30b) and 30c) respectively depict 1 to 3 layers of conductive foil 7 and the die 6 that are part of the die system 2. Thus, the gap extends from the inner wall 8 of the die system 2 to the outer walls 11 of each of the upper and lower punches. The gap distance is arranged such that the powder can degas before and / or during heating and sintering, while also maintaining ohmic contact between the punch and the die to improve the temperature distribution on the ceramic powder or powder mixture during heating and sintering.

[0308] The thickness of the graphite foil 7 can be, for example, from 0.025 mm to 0.260 mm, preferably from 0.025 mm to 0.200 mm, preferably from 0.025 mm to 0.175 mm, preferably from 0.025 mm to 0.150 mm, preferably from 0.025 mm to 0.125 mm, preferably from 0.035 mm to 0.200 mm, preferably from 0.045 mm to 0.200 mm, and preferably from 0.055 mm to 0.200 mm.

[0309] The distance of the gap 3 is measured from the inner-facing surface of the foil 7 closest to the upper punch 4 and the lower punch 4' to the outer wall 11 of each of the upper and lower punches. The preferred range of the distance of the gap 3 is preferably from 10 μm to 100 μm, from 10 μm to 70 μm, preferably from 10 μm to 60 μm, preferably from 10 μm to 50 μm, preferably from 30 μm to 70 μm, preferably from 20 μm to 60 μm, and preferably from 30 μm to 60 μm.

[0310] In addition, the width of the gap 3 between the inner wall 8 of the die system 2 and the outer wall 11 of each of the upper punch 4 and the lower punch 4' can be determined by those skilled in the art, so as to fully promote powder degassing during the preheating, heating, and sintering processes on the one hand, and achieve sufficient electrical contact for Joule or resistive heating to achieve sintering on the other hand. If the distance of the gap 3 is less than 10 μm, the force required to move at least one of the upper and lower punches within the internal volume of the die system and thus assemble the tool set may damage the tool set. In addition, a gap 3 less than 10 μm may not allow adsorbed gases, organic substances, moisture, etc. in the powder 5 to escape, which will prolong the processing time during the manufacturing process and may result in residual pores in the resulting sintered ceramic body, thereby reducing the density. If the width of the gap 3 is greater than 70 μm when sintering the ceramic powder or powder mixture, local overheating may occur, resulting in a thermal gradient within the tool set during sintering. Therefore, in order to form a large-sized (with a maximum size of up to about 625 mm) multi-layer sintered ceramic body (such as the multi-layer sintered ceramic body disclosed herein), a gap of 10 μm to 100 μm is preferred. Therefore, in some embodiments, when sintering the sintered ceramic powder or powder mixture, the distance of the gap 3 between the inner wall 8 of the die system 2 and the outer wall 11 of each of the upper and lower punches is preferably from 10 μm to 100 μm, from 10 μm to 70 μm, preferably from 10 μm to 60 μm, preferably from 10 μm to 50 μm, preferably from 10 μm to 40 μm, preferably from 20 μm to 70 μm, preferably from 30 μm to 70 μm, preferably from 40 μm to 70 μm, preferably from 50 μm to 70 μm, preferably from 30 μm to 60 μm.

[0311] These thermal gradients can result in low overall or bulk density and high density variations, as well as brittle and easily cracked sintered ceramic bodies. Thus, when sintering ceramic powders or powder mixtures as disclosed herein, the distance of the gap 3 between the inner wall 8 of the die system 2 and the outer walls 11 of each of the upper and lower punches is from 10 μm to 100 μm, from 10 μm to 70 μm, preferably from 10 μm to 60 μm, preferably from 10 μm to 40 μm, preferably from 20 μm to 70 μm, preferably from 40 μm to 70 μm, preferably from 50 μm to 70 μm, preferably from 30 μm to 70 μm, preferably from 40 μm to 60 μm. Without being bound by a particular theory, it is believed that during the sintering process, the gap distance between the inner wall 8 of the die system 2 and the outer walls 11 of each of the upper and lower punches facilitates powder degassing of organics, moisture, adsorbed molecules, etc. during the sintering process. This results in a sintered ceramic body (such as the multi-layer body disclosed herein) having large dimensions and having a high density, low volume porosity, and improved mechanical properties, such that the body can be easily handled and machined into a chamber component of a predetermined form without breakage. The multi-layer sintered ceramic body prepared as disclosed herein can have dimensions ranging from 100 mm to about 625 mm with respect to the maximum dimension 100 of the multi-layer sintered ceramic body 98.

[0312] In practice, the upper punch 4 and the lower punch 4' are not always perfectly aligned about the central axis. FIGS. 31a) and 31b) are plan views of the tool set 1, showing the alignment of the upper punch 4 and the lower punch 4', the gap 3, any number of conductive foils 7, and the die system 2 about the central axis 9. In the embodiment depicted in FIG. 31a), the gap can be axisymmetric about the central axis 9. In other embodiments depicted in FIG. 31b), the gap can be asymmetric about the central axis 9. In the depicted axisymmetric and asymmetric embodiments, when sintering ceramic powders or powder mixtures to form a multi-layer sintered ceramic body as disclosed herein, the gap 3 can extend between 10 μm and 100 μm.

[0313] The gap asymmetry performance can be measured by performing an absolute radial CTE deviation analysis over a certain temperature range. For example, Figure 32 shows the radial deviation of the average CTE of two isotropic graphite materials (A and B) used as punches and dies of the device disclosed herein at 1200 °C. Figure 32 shows that for a material that successfully maintains the required gap over a large temperature range, from, for example, room temperature to 2000 °C, the maximum change in the radial deviation in the x-y plane cannot be > 0.3 × 10-6. Material B exhibits unacceptable CTE expansion in the x-y plane, while material A exhibits acceptable CTE expansion over the entire temperature range.

[0314] The advantages of the design of a specific tool set used according to one embodiment can produce an overall technical effect to provide a very high purity, relatively large multi-layer sintered ceramic body with high and uniform density and low volume porosity, and thereby reduce the tendency to crack in the sintering process according to the present disclosure, especially in the SPS process. Accordingly, all features disclosed with respect to the tool set are also applicable to multi-layer sintered ceramic body products having dimensions greater than 100 mm and up to and including approximately 625 mm.

[0315] By using a tool set as disclosed herein, a more uniform temperature distribution can be achieved in the ceramic powder or powder mixture 5 to be sintered, and a sintered ceramic body can be prepared, especially a sintered ceramic body of large size (maximum dimension exceeding, for example, 100 mm and / or 200 mm, up to approximately 625 mm and larger), which has a very high density (theoretical density of the specified material > 98%) and enhanced interlayer adhesion, thereby reducing the tendency to crack. The term "uniform" means that the material or system has substantially the same properties at every point; it is homogeneous and without irregularities. Accordingly, a "uniform temperature distribution" means that the temperature distribution is spatially uniform and does not have a significant gradient, i.e., there is a substantially uniform temperature regardless of the position of the ceramic powder or powder mixture 5 in the horizontal x-y plane.

[0316] The disclosed tool set may also include spacer elements, shims, liners, and other tool set components. Generally, such components are made of at least one graphite material having the properties as disclosed herein.

[0317] As Figure 33 shown, embodiments of the technology as disclosed herein can be used as components in a plasma processing system 9500, which can be configured for a semiconductor etching process, also referred to as an "etch processing system". The etch processing system 9500 in the embodiments can include a remote plasma region. The remote plasma region can include a remote RF source / match network 9502, which is also referred to as a remote plasma source ("RPS").

[0318] The etching system 9500 may include a vacuum chamber 9550 having a corrosion-resistant chamber liner (not shown), a vacuum source, and a chuck or electrostatic chuck ("ESC") 9509 on which a wafer 50 (also referred to as a substrate) is supported. A retainer ring or electrode cover 9514, a top shield ring 9512, and a shield ring 9513 surround the wafer 50 and the chuck 9509. A top plate / window / cover 9507 forms the upper wall of the vacuum chamber 9550. A showerhead 9517 forms or is mounted below the upper wall of the vacuum chamber 9650. The top plate / window / cover 9507 (which may include an RF window or a dielectric window), a gas distribution system 9506, a showerhead 9517, a retainer ring or electrode cover 9514, a top shield ring 9512, a shield ring 9513, a chamber liner (not shown), and the chuck or electrostatic chuck (ESC) 9508 and the chuck 9509 may be at least partially made of an embodiment of a multi-layer sintered ceramic body as disclosed herein.

[0319] A portion of the surface of the showerhead 9517 may be covered by a shield ring 9712. Some portions of the surface of the showerhead 9517, particularly the radial sides of the surface of the showerhead 9517, may be covered by a top shield ring 9710. The shield ring 9712, the showerhead 9517, and the top shield ring 9710 may be at least partially made of an embodiment of a multi-layer sintered ceramic body as disclosed herein.

[0320] A remote plasma source 9502 is disposed outside the window 9507 of the chamber 9550 for receiving a wafer 50 to be processed. The remote plasma region may be in fluid communication with the vacuum chamber 9550 through a gas delivery system 9506. In the chamber 9550, an active plasma may be generated by supplying a process gas to the chamber 9550 and supplying high-frequency power to the plasma source 9502. By using the active plasma so generated, a predetermined plasma process is performed on the wafer 50. A planar antenna having a predetermined pattern is widely used as the high-frequency antenna of the etching system 9500.

[0321] As Figure 34As shown, embodiments of the technology disclosed herein can be used as components in a plasma processing system 9600, which can be configured for semiconductor deposition processes, also referred to as "deposition processing systems". Deposition processing system 9600 includes a vacuum chamber 9650, a vacuum source, and a positioning disk 9609 on which a wafer 50 (also referred to as a semiconductor substrate) is supported. The processing system may also include a nozzle or injector 9614 that is in fluid communication with a gas delivery system 9616 for supplying process gas to the interior of the vacuum chamber 9650. The top wall 9700 of the chamber 9650 may include a central opening configured to receive a central gas injector (also referred to as a nozzle) 9614. In certain embodiments, the top wall 9700 of the chamber may include an RF or dielectric window configured with a central opening to accommodate the injector 9614. An RF energy source excites the process gas into a plasma state to process the substrate 50. Embodiments of the top wall including the RF or dielectric window 9700, the gas delivery system 9616, and the central gas injector 9614 may be made in whole or in part from embodiments of the multilayer sintered ceramic body disclosed herein.

[0322] Deposition processing system 9600 may also include an electrostatic chuck 9608 that is designed to hold the wafer 50. The chuck 9608 may include a positioning disk 9609 for supporting the wafer 50. Portions of the support surface of the positioning disk 9609 may be covered with a deposition ring 9615. Other names for the deposition ring 9615 such as deposition shield or deposition ring assembly are considered synonymous and may be used interchangeably herein. The deposition ring 9615 may be made in whole or in part from embodiments of the multilayer sintered ceramic body disclosed herein.

[0323] The positioning disk 9609 may be formed in whole or in part from embodiments of the multilayer sintered ceramic body disclosed herein and may have a clamping electrode disposed within the positioning disk near the support surface of the positioning disk 9609 to electrostatically hold the wafer 50 when the wafer 50 is disposed on the positioning disk 9609. The chuck 9608 may include: a base 9611 having an annulus extending to support the positioning disk 9609; and a shaft 9610 disposed between the base and the positioning disk to support the positioning disk above the base such that a gap is formed between the positioning disk 9609 and the base 9610, wherein the shaft 9610 supports the positioning disk near the peripheral edge of the positioning disk 9609. The chuck 9608, the positioning disk 9609, and the deposition ring 9615 may be made in whole or in part from embodiments of the monolithic multilayer sintered ceramic body disclosed herein.

[0324] Preparation method

[0325] The preparation of a multi-layer sintered ceramic body can be achieved by using pressure-assisted sintering, such as spark plasma sintering (SPS), also known as field-assisted sintering technology (FAST) or direct current sintering (DCS). These direct current sintering and related techniques use direct current to heat a conductive die structure or tool set, thereby heating the material to be sintered. This heating method allows for the application of very high heating and cooling rates, thereby enhancing the densification mechanism rather than the diffusion mechanism that promotes grain growth, which can help prepare a ceramic sintered body with a very fine grain size and transfer the inherent properties of the original powder to a nearly or fully dense product. The direct current pressure-assisted method disclosed herein uses preferably non-pulsed, continuous direct current to heat the disclosed tool set.

[0326] The preparation of a multi-layer sintered ceramic body as disclosed herein can also be achieved by using a pressure-assisted sintering method such as uniaxial hot pressing, whereby the die structure or tool set is heated by an externally applied heat source such as induction heating.

[0327] A multi-layer sintered ceramic body is prepared according to the following general process steps: a) combining at least two powders selected from the group consisting of yttrium oxide, alumina, magnesia, and at least one zirconia (wherein the at least one zirconia is selected from the group consisting of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia) and combinations thereof to prepare a first powder mixture; b) combining alumina powder with at least one of partially stabilized zirconia powder and stabilized zirconia powder to prepare a second powder mixture; c) combining yttrium oxide powder, alumina powder with at least one of unstabilized zirconia powder, partially stabilized zirconia powder, and stabilized zirconia powder to prepare a third powder mixture; d) calcining at least one of the first powder mixture, the second powder mixture, and the third powder mixture by applying heat to raise the temperature of at least one of them to a calcination temperature and maintaining the calcination temperature to form at least one of a first calcined powder mixture, a second calcined powder mixture, and a third calcined powder mixture; e) separately disposing at least one of the first powder mixture, the second powder mixture, and the third powder mixture within a volume defined by a tool set of a sintering apparatus to form at least one layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third powder mixture, and creating a vacuum condition within the volume, wherein the tool set includes a die, the die includes side walls, the side walls include an inner wall and an outer wall, wherein the inner wall has a diameter defining an internal volume capable of receiving at least one powder; and an upper punch and a lower punch operably coupled to the die, wherein each of the upper punch and the lower punch has an outer wall, the outer wall defining a diameter smaller than the diameter of the inner wall of the die, whereby when at least one of the upper punch and the lower punch moves within the internal volume of the die, a gap is defined between each of the upper punch and the lower punch and the inner wall of the die, wherein the gap is 10 μm to 100 μm wide; f) applying pressure and sintering the layers of the first powder mixture, the second powder mixture, and the third powder mixture while heating to a sintering temperature to form a multi-layer sintered ceramic body, wherein at least one layer of the first powder mixture forms at least one first layer, at least one layer of the second powder mixture forms at least one second layer, and at least one layer of the third powder mixture forms at least one third layer;and g) reducing the temperature of the multi-layer sintered ceramic body, wherein at least one first layer comprises at least one polycrystalline ceramic material selected from the group consisting of (i) YAG, (ii) magnesium aluminate spinel, and (iii) yttrium oxide and zirconium oxide, wherein zirconium oxide is present in an amount of not less than 10 mol% ZrO2 and not more than 25 mol% ZrO2, preferably not less than 12 mol% and not more than 25 mol% ZrO2, preferably not less than 15 mol% and not more than 25 mol% ZrO2, preferably not less than 18 mol% and not more than 25 mol% ZrO2, preferably not less than 10 mol% and not more than 23 mol% ZrO2, preferably not less than 10 mol% and not more than 20 mol% ZrO2, preferably not less than 15 mol% and not more than 23 mol% ZrO2 (and the balance comprises Y2O3), and at least one second layer comprises alumina and zirconium oxide, wherein the zirconium oxide comprises at least one of stabilized zirconium oxide and partially stabilized zirconium oxide, and at least one third layer comprises at least one selected from the group consisting of yttrium oxide, alumina, and zirconium oxide, wherein the zirconium oxide comprises at least one of unstabilized zirconium oxide, stabilized zirconium oxide, and partially stabilized zirconium oxide, wherein at least one second layer is disposed between at least one first layer and at least one third layer, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between any of at least one first layer, at least one second layer, and at least one third layer, as measured according to ASTM E228-17, is from 0 to 0.75×10-6 / °C, and wherein at least one first layer, at least one second layer, and at least one third layer form an integral sintered ceramic body. In a preferred embodiment, according to steps a), b), and c), the powders selected from the group consisting of yttrium oxide, alumina, and magnesia and at least one selected from the group consisting of unstabilized zirconium oxide, partially stabilized zirconium oxide, and stabilized zirconium oxide each have a specific surface area of about 18 m; 2 / g or less, preferably about 1 m 2 / g to about 18 m 2 / g. Preferably, the first powder mixture, the second powder mixture, and the third powder mixture have a total impurity content of 200 ppm or less, as measured relative to the mass of the first powder mixture, the second powder mixture, and the third powder mixture.

[0328] At least one second powder mixture comprises alumina and zirconia, wherein the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia. At least one second powder mixture comprises alumina in an amount by weight of from 60% to 92.5%, preferably 75% to 85%, preferably about 77%, relative to the weight of the at least one second powder mixture. At least one second powder mixture comprises zirconia (to include stabilizers to form at least one of stabilized zirconia and partially stabilized zirconia) in an amount by weight of from 7.5% to 40%, preferably 15% to 25%, preferably about 23%, relative to the weight of the at least one second powder mixture. Upon sintering, these compositional ranges of the at least one second powder mixture correspond to at least one second layer 102 that comprises zirconia in an amount, respectively, by volume of from 5% to 30%, preferably 10% to 30%, preferably 15% to 30%, preferably 20% to 30%, preferably 12% to 25%, preferably 15% to 25%, preferably 17% to 25%, preferably 10% to 22%, preferably 10% to 20%, preferably 10% to 17%, preferably 15% to 21%, preferably 16% to 20%, and preferably about 16% by volume (upon sintering) (and the balance comprises alumina) relative to the volume of the at least one second layer 102. These volume amounts of zirconia can be measured using a combination of SEM imaging and ImageJ analysis software according to the methods disclosed herein.

[0329] At least one third powder mixture comprises at least one selected from the group consisting of yttrium oxide, alumina, and zirconia, wherein the zirconia comprises at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. At least one third powder mixture comprises yttrium oxide in an amount by weight of 1% to 57%, preferably 3% to 57%, preferably 5% to 57%, preferably 1% to 40%, preferably 1% to 30%, preferably 3% to 30%, preferably 5% to 30%, preferably 5% to 15%, and preferably about 6% relative to the weight of the at least one third powder mixture. At least one third powder mixture comprises alumina in an amount by weight of 43% to 92.5%, preferably 65% to 75%, preferably about 73% relative to the weight of the at least one third powder mixture. At least one third powder mixture comprises zirconia (including stabilizers, forming stabilized zirconia and / or unstabilized zirconia where applicable) in an amount by weight of about 0.4% to 40%, preferably 4% to 40%, preferably 15% to 40%, preferably 15% to 25%, preferably about 21% relative to the weight of the at least one third powder mixture. Upon sintering, these compositional ranges of the at least one third powder mixture can correspond to an exemplary SEM image of at least a third layer 103 of a multiphase structure comprising YAG, zirconia, and alumina, as Figure 26 a) and Figure 26 b) depicted. In a preferred embodiment, at least one third powder mixture comprises an amount of zirconia (upon sintering) for at least a third layer to comprise ZrO2 in an amount of about 5 vol% to about 30 vol%, preferably 5 vol% to 25 vol%, preferably 5 vol% to 20 vol%, preferably 5 vol% to 16 vol%, preferably 10 vol% to 30 vol%, preferably 15 vol% to 30 vol%, preferably 20 vol% to 30 vol%, and preferably 15 vol% to 20 vol% relative to the volume of the at least a third layer 103 (and the balance comprises Y2O3 and Al2O3).

[0330] The following additional steps are optional; h) optionally annealing the multi-layer sintered ceramic body by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature; i) lowering the temperature of the annealed multi-layer sintered ceramic body; and j) machining the multi-layer sintered ceramic body or the annealed multi-layer sintered ceramic body to form a multi-layer sintered ceramic component in the shape of a window, cover, dielectric window, RF window, ring, focusing ring, machining ring, deposition ring, nozzle, injector, gas injector, showerhead, gas distribution plate, diffuser, ion suppressor element, chuck, electrostatic wafer chuck (ESC), and positioning disk.

[0331] In some embodiments, an optional annealing step may be performed. Optionally, annealing is performed by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature, performing the annealing, and reducing the temperature of the sintered and annealed multi-layer sintered ceramic body to ambient temperature by removing the heat source applied to the body and removing the multi-layer sintered ceramic body.

[0332] The above-described features of the corrosion-resistant multi-layer sintered ceramic body according to one embodiment are achieved in part by adjusting the purity and specific surface area (SSA) of the first powder mixture, the second powder mixture, and the third powder mixture, the pressure of the first mixture, the second mixture, and the third mixture, the temperature of the first powder mixture, the second powder mixture, and the third powder mixture, the sintering duration of the first powder mixture, the second powder mixture, and the third powder mixture, the temperature of the multi-layer sintered ceramic body during the optional annealing step, and the duration of the optional annealing step.

[0333] Disclosed is a method for preparing a multi-layer sintered ceramic body, the method comprising the following steps: a) combining at least two powders selected from the group consisting of yttrium oxide, alumina, magnesia, and at least one zirconia (the at least one zirconia being selected from the group consisting of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia) and combinations thereof to prepare a first powder mixture; b) combining alumina powder with at least one of partially stabilized zirconia powder and stabilized zirconia powder to prepare a second powder mixture; c) combining yttrium oxide powder, alumina powder with at least one of unstabilized zirconia powder, partially stabilized zirconia powder, and stabilized zirconia powder to prepare a third powder mixture; d) calcining at least one of these powder mixtures by applying heat to raise the temperature of the first powder mixture, the second powder mixture, and the third powder mixture to a calcination temperature and maintaining the calcination temperature to form at least one of a first calcined powder mixture, a second calcined powder mixture, and a third calcined powder mixture; e) separately disposing the first powder mixture, the second powder mixture, and the third powder mixture within a volume defined by a set of tools of a sintering apparatus to form at least one layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third powder mixture, and creating a vacuum condition within the volume, wherein the set of tools includes a die, the die including sidewalls, the sidewalls including an inner wall and an outer wall, wherein the inner wall has a diameter defining an internal volume capable of receiving at least one powder; and an upper punch and a lower punch operably coupled to the die, wherein each of the upper punch and the lower punch has an outer wall, the outer wall defining a diameter smaller than the diameter of the inner wall of the die, whereby when at least one of the upper punch and the lower punch moves within the internal volume of the die, a gap is defined between each of the upper punch and the lower punch and the inner wall of the die, wherein the gap is 10 μm to 100 μm wide; f) applying pressure and sintering at least one layer of the first powder mixture, the second powder mixture, and the third powder mixture while heating to a sintering temperature to form a multi-layer sintered ceramic body, wherein at least one layer of the first powder mixture forms at least one first layer upon sintering, at least one layer of the second powder mixture forms at least one second layer, and at least one layer of the third powder mixture forms at least one third layer;and g) reducing the temperature of a multi-layer sintered ceramic body, wherein the first layer comprises at least one crystalline phase of a ceramic material selected from the group consisting of (i) YAG, (ii) magnesium aluminate spinel, and (iii) yttrium oxide and zirconium oxide, wherein the zirconium oxide is present in an amount of not less than 10 mol% ZrO2 and not more than 25 mol% ZrO2, preferably not less than 12 mol% and not more than 25 mol% ZrO2, preferably not less than 15 mol% and not more than 25 mol% ZrO2, preferably not less than 18 mol% and not more than 25 mol% ZrO2, preferably not less than 10 mol% and not more than 23 mol% ZrO2, preferably not less than 10 mol% and not more than 20 mol% ZrO2, and preferably not less than 15 mol% and not more than 23 mol% ZrO2. At least one second layer comprises alumina and zirconium oxide, wherein the zirconium oxide comprises at least one of unstabilized zirconium oxide, stabilized zirconium oxide, and partially stabilized zirconium oxide, wherein at least one second layer is disposed between at least one first layer and at least one third layer, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between any one of at least one first layer, at least one second layer, and at least one third layer is 0 to 0.75×10-6 / °C as measured according to ASTM E228-17, wherein at least one first layer, at least one second layer, and at least one third layer form an integral sintered ceramic body. In a preferred embodiment, the powders selected from the group consisting of yttrium oxide, alumina, and magnesia and at least one of the group consisting of unstabilized zirconium oxide, partially stabilized zirconium oxide, and stabilized zirconium oxide each have a specific surface area of about 18 m 2 / g and less, preferably about 1 m 2 / g to about 18 m 2 / g. In a further preferred embodiment, the at least one first powder mixture, second powder mixture, and third powder mixture (or the calcined powder mixture, as the case may be) each have a specific surface area of about 18 m 2 / g and less, preferably 1 m 2 / g to 18 m 2 / g as measured according to ASTM C1274. Preferably, the first powder mixture, second powder mixture, and third powder mixture have a total impurity content of 200 ppm and less as measured relative to the mass of the first powder mixture, second powder mixture, and third powder mixture.

[0334] The following additional steps are optional; h) optionally annealing the multi-layer sintered ceramic body by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature; i) lowering the temperature of the annealed multi-layer sintered ceramic body; and j) machining the multi-layer sintered ceramic body or the annealed multi-layer sintered ceramic body to form a multi-layer sintered ceramic component in the shape of a window, a cover, a dielectric window, an RF window, a ring, a focusing ring, a processing ring, a deposition ring, a nozzle, an injector, a gas injector, a showerhead, a gas distribution plate, a diffuser, an ion suppressor element, a chuck, an electrostatic wafer chuck (ESC), and a positioning disk for use in a plasma processing chamber.

[0335] Step a) of the method as disclosed herein includes combining at least two powders selected from the group consisting of yttrium oxide, alumina, magnesia, and zirconia (wherein the zirconia is selected from at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia) to prepare a first powder mixture; proportionally combining and mixing the starting powder materials comprising the first powder mixture such that the at least one first powder mixture forms at least one first layer comprising at least one crystal phase of a ceramic material upon sintering, the ceramic material comprising YAG, magnesium aluminate spinel, or comprising yttrium oxide and zirconia, wherein the zirconia is present in an amount of not less than 10 mol% ZrO2 and not more than 25 mol% ZrO2 and the balance comprises Y2O3. The powders selected for forming the at least one first powder mixture are preferably commercially available powders of high purity (>99.99%). However, other oxide powders, such as those produced by chemical synthesis processes and related methods, may be used provided that the high purity requirements are met.

[0336] The particle size of the starting powder, the powder mixture, and the calcined powder mixture can be measured using a Horiba model LA-960 laser scattering particle size distribution analyzer capable of measuring particle sizes from 10 nm to 5 mm. The specific surface area (SSA) of the starting powder, the powder mixture, and the calcined powder mixture can be measured using a Horiba BET surface area analyzer model SA-9601, which is capable of measuring from 0.01 m 2 / g to 2000 m 2The specific surface area of / g has an accuracy of 10% and lower for most samples. The Agilent 7900 ICP-MS model G8403, which can analyze lighter elements (such as Sc and smaller atomic numbers) to about 1.4 ppm and heavier elements (such as atomic numbers higher than Sc) to about 0.14 ppm, can be used to measure the purity of the starting powder, powder mixture, and calcined powder mixture using ICP-MS measurements. Purity is reported herein as a percentage relative to 100% purity, where 100% purity represents a material that contains only the expected components without impurities, dopants, sintering aids, etc. The impurity content is reported herein in ppm relative to the total mass of the material being evaluated. Silicon dioxide is not disclosed in the purity and impurity reports and can be measured in an amount of about 14 ppm using the ICP-MS method disclosed herein.

[0337] As used herein, d50 is defined as the median and represents the value at which half of the particle size distribution is above this point and half is below this point. Similarly, 90% of the distribution is below d90, and 10% of the distribution is below d10.

[0338] The starting powders of yttrium oxide, zirconium oxide, magnesium oxide, and aluminum oxide as disclosed herein are preferably crystalline and thus have long-range crystal order. Any one or all of the starting powders of yttrium oxide, zirconium oxide, magnesium oxide, and aluminum oxide can be sieved, tumbled, blended, ground, etc. according to methods known to those skilled in the art. In some embodiments, the starting powders of yttrium oxide, magnesium oxide, zirconium oxide, and / or aluminum oxide can optionally be calcined according to methods known to those skilled in the art. Starting powders, powder mixtures, and calcined powder mixtures with a high specific surface area (SSA), such as those greater than 20 m 2 / g of those nanopowders cause problems in terms of processability when loading the powder in the tool set, achieving uniform particle dispersion and mixing during the powder consolidation / mixing step, and forming the first layer containing the YAG phase during the in-situ reactive sintering method for forming YAG, as disclosed in International Application No. PCT / US20 / 60918, which is incorporated herein by reference. The starting powder according to the method disclosed herein contains yttrium oxide, magnesium oxide, zirconium oxide, and aluminum oxide and preferably has a specific surface area of 18 m 2 / g or less. Therefore, it is preferred that the powder mixture as disclosed herein does not contain or is substantially free of the nanopowders as disclosed herein and has a specific surface area (SSA) of about 18 m 2 / g or less.

[0339] The specific surface area is less than about 0.75 m 2The starting powders, powder mixtures, and / or calcined powder mixtures of / g may undergo agglomeration, requiring higher mixing energy and extended mixing times to combine and form the powder mixtures as disclosed herein. In addition, powders with surface areas in this range may reduce the driving force required to sinter to the high densities as disclosed herein, resulting in sintered ceramic bodies with lower densities and higher porosities. Preferred for use in the disclosed methods are starting powders having an SSA as disclosed herein of 1 m 2 / g to 18 m 2 / g, preferably 2 m 2 / g to 15 m 2 / g, and preferably 3 m 2 / g to 12 m 2 / g.

[0340] The d10 particle size of the yttrium oxide powder used as a starting material according to the embodiments disclosed herein is preferably 1 μm to 6 μm, preferably 1 μm to 5 μm, preferably 1 μm to 4 μm, preferably 2 μm to 6 μm, preferably 3 μm to 6 μm, preferably 4 μm to 6 μm, preferably 2 μm to 4 μm.

[0341] The d50 particle size of the yttrium oxide powder used as a starting material according to the embodiments disclosed herein is preferably 3 μm to 9 μm, preferably 3 μm to 8.5 μm, preferably 3 μm to 8 μm, preferably 3 μm to 7 μm, preferably 4 μm to 9 μm, preferably 5 μm to 9 μm, preferably 6 μm to 9 μm, preferably 4 μm to 8 μm. The yttrium oxide powder as disclosed herein may have an average particle size of about 5 μm to 9 μm.

[0342] The d90 particle size of the yttrium oxide powder used as a starting material according to the embodiments disclosed herein is preferably 6 μm to 16 μm, preferably 6 μm to 15 μm, preferably 6 μm to 14 μm, preferably 6.5 μm to 16 μm, preferably 7 μm to 16 μm, preferably 7.5 μm to 16 μm, preferably 7.5 μm to 14 μm.

[0343] Yttrium oxide powders generally have 2 m 2 / g to 10 m 2 / g, preferably 2 m 2 / g to 8 m 2 / g, preferably 2 m 2 / g to 6 m 2 / g, preferably 3 m 2 / g to 10 m 2 / g, preferably 4 m 2 / g to 10 m 2 / g, preferably 6 m 2 / g to 10 m 2 / g, and preferably 2 m2 / g to 4 m 2 The specific surface area (SSA) of / g.

[0344] The purity of the yttrium oxide starting material is preferably higher than 99.99%, preferably higher than 99.995%, preferably higher than 99.999%, more preferably higher than 99.9995% and more preferably about 99.9999%. This corresponds to an impurity level of 100 ppm and lower, preferably 50 ppm and lower, preferably 25 ppm and lower, preferably 10 ppm and lower, more preferably about 1 ppm, preferably 1 ppm to 100 ppm, preferably 1 ppm to 50 ppm, preferably 1 ppm to 25 ppm, preferably 1 ppm to 10 ppm, preferably 1 ppm to 5 ppm.

[0345] The average particle size or d50 particle size of the magnesium oxide powder used as a starting material according to the embodiments disclosed herein is typically 1.5 μm to 5.5 μm, 2 μm to 5.5 μm, 2.5 μm to 5.5 μm, 3 μm to 5.5 μm, 1.5 μm to 5 μm, 1.5 μm to 4.5 μm, and more preferably 2 μm to 4.5 μm.

[0346] The d90 particle size of the magnesium oxide powder used as a starting material according to the embodiments disclosed herein is typically 4 μm to 9 μm, preferably 5 μm to 9 μm, preferably 6 μm to 9 μm, preferably 4 μm to 8 μm, preferably 4 μm to 7 μm, and more preferably 5 μm to 7.5 μm.

[0347] The magnesium oxide powder typically has 0.5 m 2 / g to 10 m 2 / g, preferably 0.5 m 2 / g to 8 m 2 / g, preferably 0.5 m 2 / g to 6 m 2 / g, preferably 1 m 2 / g to 10 m 2 / g, preferably 2 m 2 / g to 10 m 2 / g, preferably 3 m 2 / g to 10 m 2 / g and more preferably 2 m 2 / g to 6 m 2Specific surface area (SSA) per g. The purity of the magnesium oxide starting material is preferably higher than 99.99%, preferably higher than 99.995%, more preferably higher than 99.9975%, preferably higher than 99.999%, and preferably higher than 99.9992%, as measured by ICPMS methods known in the art. Accordingly, the impurity content of the magnesium oxide powder can be 100 ppm or less, preferably 50 ppm or less, preferably 25 ppm or less, preferably about 10 ppm.

[0348] The zirconia powder according to step a) can be selected from the group consisting of unstabilized, partially stabilized, and stabilized zirconia. The reaction between the zirconia and yttria powders to form at least one crystal phase allows any zirconia powder to be used without the tetragonal / monoclinic phase transition that occurs with pure unstabilized zirconia. Thus, the zirconia powder forming at least the first layer can comprise any one or a combination of unstabilized, partially stabilized, and stabilized zirconia. Further powder characteristics of the zirconia and alumina (according to the second powder mixture) are disclosed in step b) of the following method.

[0349] The powders of at least two of alumina, magnesium oxide, yttrium oxide and at least one of unstabilized zirconia, partially stabilized zirconia and stabilized zirconia are combined to prepare at least a first powder mixture and at least a second powder mixture (according to any one or both of steps a) and b)), and powder preparation techniques such as wet or dry ball milling (axial rotation), wet or dry tumbling (upside down or vertical), jet milling, and combinations thereof can be used. The use of these powder combination methods provides a high-energy process for decomposing fine particles and agglomerates.

[0350] Using dry conditions, the starting powder can be ball milled or tumbled / rolled using high purity (>99.9%) alumina media to maintain the purity of the starting powder during mixing. In other embodiments, harder media such as zirconia media can be used to break up hard agglomerates. The high purity alumina media is tested using the ICPMS method as disclosed herein and is found to have a purity of 99.9% to about 99.99%. Use of zirconia media can result in trace amounts (such as less than 100 ppm) of zirconia in the multi-layer sintered ceramic body. The media used for dry ball milling can have a range of sizes, for example, 5 mm to 15 mm in diameter, and is added at a loading of about 50% to about 100% by powder weight. The media used for dry tumbling mixing can include at least one large-sized (about 20 mm to 40 mm in diameter) media element, without limitation. The dry ball milling and / or dry tumbling mixing can be carried out for a duration of 12 hours to 48 hours, preferably 16 hours to 48 hours, preferably 16 hours to 24 hours, preferably 18 hours to 22 hours. The dry ball milling or tumbling mixing process (axial rotation) can use 50 RPM to 250 RPM, preferably 75 RPM to 200 RPM, preferably 75 RPM to 150 RPM, preferably 100 RPM to 125 RPM, each for a container having a diameter of about 200 mm. The RPM can vary depending on the size of the container selected for use, and thus, those containers with a diameter greater than, for example, 200 mm can have a correspondingly lower RPM, as known to those skilled in the art. The dry tumbling / rolling mixing can be carried out at 10 rpm to 30 rpm, preferably about 20 RPM. After the dry ball milling and / or tumbling / rolling ball milling / mixing, the powder mixture can optionally be screened using a number of sieves that can have openings of, for example, 45 μm to 400 μm and blended, but there is no limitation on the repetition or sequence known to those skilled in the art.

[0351] Wet ball milling or wet tumbling / rolling mixing can be carried out by suspending the starting powder in various solvents (such as ethanol, methanol, and other alcohols) to form a slurry. The slurry in either process (ball milling or tumbling ball milling / mixing) can be formed to have a powder loading of 25% to 75% by weight of the powder, preferably 40% to 75% by weight of the powder, and more preferably 50% to 75% by weight of the powder during milling or mixing. Wet ball milling or wet tumbling / rolling mixing can improve the dispersion of the powder by increasing fluidity, thereby producing a fine and uniform mixture before heat treatment or calcination. In embodiments, a number of commercially available dispersants (such as polymethyl methacrylate (PMMA) and polyvinylpyrrolidone (PVP)) and other dispersants known to those skilled in the art can be optionally used, and the dispersant is added to the slurry. The dispersant can be optionally added in an amount of 0.05% to 0.2% by weight of the powder, preferably 0.05% to 0.1% by weight of the powder. The media loading for wet ball milling or wet tumbling / rolling mixing can vary from 30% to 100% by weight of the powder, preferably 30% to 75% by weight of the powder, and more preferably 30% to 60% by weight of the powder. Wet ball milling or tumbling mixing can be carried out for a duration of 8 hours to 48 hours, preferably 12 hours to 48 hours, preferably 16 hours to 48 hours, preferably 8 hours to 36 hours, preferably 8 hours to 24 hours, preferably 16 hours to 24 hours, preferably 12 hours to 24 hours. Ball milling can use RPMs of 50 RPM to 250 RPM, preferably 75 RPM to 200 RPM, preferably 75 RPM to 150 RPM, preferably 100 RPM to 125 RPM, each for a container having a diameter of about 200 mm. The RPM can vary depending on the size of the container selected for use, and containers with diameters greater than, for example, 200 mm can have a correspondingly lower RPM, as known to those skilled in the art. Wet tumbling / rolling mixing can be carried out at an RPM of 10 rpm to 30 rpm, preferably about 20 rpm. After wet ball milling and / or wet tumbling / rolling mixing, the powder mixture can be optionally screened using a number of sieves that can have openings of, for example, 45 μm to 400 μm and blended, but there is no limitation on the repetition or sequence known to those skilled in the art.

[0352] Jet milling processes known to those skilled in the art can also be used to thoroughly mix powders to form powders, powder mixtures, or calcined powder mixtures having a narrow particle size distribution. Jet milling uses a high-speed jet of an inert gas or air to impinge on the particles of the starting powder and / or powder mixture and / or calcined powder mixture without using a grinding or mixing medium, thereby maintaining the initial purity of the powder to be milled. The chamber can be designed such that the size of the larger particles can be preferentially reduced, which can provide a narrow particle size distribution in the final powder, powder mixture, or calcined powder mixture. The powder exits the jet milling chamber when it reaches a predetermined particle size determined in the machine settings prior to processing, thus ending the process. The starting powders, powder mixtures, and / or calcined powder mixtures as disclosed herein can be jet milled at a pressure of about 100 psi, either alone or in combination with any one or all of the powder milling / mixing methods as disclosed herein. After jet milling, the powder or powder mixture can optionally be screened using a number of sieves that can have openings, for example, from 45 μm to 400 μm, and blended, but there is no limitation on the repetition or sequence known to those skilled in the art.

[0353] Additional powder preparation procedures of milling, high-shear mixing, planetary milling, and other known procedures can also be applied. The foregoing powder preparation techniques can be used alone or in any combination thereof, or for more than one powder mixture, which are then sintered to form an integral multi-layer sintered ceramic body.

[0354] As known to those skilled in the art, when using a wet mixing or grinding process, the slurry can be dried by a rotary evaporation method, for example, at a temperature of about 40 °C to 90 °C for a duration of 1 to 4 hours, depending on the volume of the slurry to be dried. In other embodiments, spray drying techniques known to those skilled in the art can be used to dry the slurry. After drying, the powder mixture can optionally be screened using a sieve having openings, for example, from 45 μm to 400 μm, and blended, but there is no limitation on the repetition or sequence. The above powder preparation techniques can be used alone or in any combination thereof.

[0355] After drying, the specific surface area of the powder mixture of step a) can be 2 m 2 / g to 18 m 2 / g, preferably 2 m 2 / g to 17 m 2 / g, preferably 2 m 2 / g to 14 m 2 / g, preferably 2 m 2 / g to 12 m 2 / g, preferably 2 m 2 / g to 10 m 2 / g, preferably 4 m2 from / g to 17 m 2 / g, preferably 6 m 2 from / g to 17 m 2 / g, preferably 8 m 2 from / g to 17 m 2 / g, preferably 10 m 2 from / g to 17 m 2 / g, preferably 4 m 2 from / g to 12 m 2 / g, preferably 4 m 2 from / g to 10 m 2 / g and preferably 5 m 2 from / g to 8 m 2 / g.

[0356] By using high-purity grinding media, such as alumina media with a purity of 99.99% or higher, the purity of the powder mixture can be maintained from the purity of the starting materials after mixing / grinding. In some embodiments, zirconia grinding media can be preferably used, and zirconia can be introduced to an extent that 15 ppm to 100 ppm, 15 ppm to 75 ppm, preferably 15 ppm to 60 ppm, preferably 20 ppm to 30 ppm is retained in at least one first layer and / or at least one second layer of the multi-layer sintered ceramic body.

[0357] Step b) of the method as disclosed herein includes combining alumina powder and zirconia powder to prepare a second powder mixture, wherein the zirconia powder includes at least one of partially stabilized zirconia powder and stabilized zirconia powder; proportionally combining and mixing the starting powder materials containing the second powder mixture such that the second powder mixture forms at least one second layer 102 upon sintering, wherein at least one second layer 102 includes at least one of partially stabilized zirconia and stabilized zirconia (and combinations thereof) in an amount of not less than 5 vol% ZrO2 and not more than 30 vol% ZrO2 and the balance portion includes Al2O3. The starting powder materials selected for forming at least one second layer 102 are preferably high-purity commercially available powders. However, other oxide powders, such as those produced by chemical synthesis processes and related methods, can be used as long as the high-purity requirements are met. In some embodiments, according to the required CTE matching characteristics, toughness, and mechanical strength requirements of the plasma processing chamber components, at least one second layer 102 can include at least one of partially stabilized zirconia and stabilized zirconia (and combinations thereof) in an amount of not less than 10 vol% ZrO2 and not more than 25 vol% ZrO2 relative to the volume of at least one second layer 102 (and the balance portion includes Al2O3).

[0358] The following properties of the zirconia and alumina powders also apply to step a), except that the zirconia of step a) may comprise any one or combination of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. The zirconia powder according to step b) is preferably stabilized, partially stabilized, and combinations thereof.

[0359] The zirconia powder may have a particle size distribution with d10 from 0.08 μm to 0.20 μm, d50 from 0.3 μm to 0.7 μm, and d90 from 0.9 μm to 5 μm. The average particle size of the zirconia powder used as the starting material for the mixture according to one embodiment of the present invention may be from 0.3 μm to 1 μm.

[0360] The zirconia powder typically has a specific surface area (SSA) of 1 m 2 / g to 16 m 2 / g, preferably 2 m 2 / g to 14 m 2 / g, preferably 4 m 2 / g to 12 m 2 / g and more preferably 5 m 2 / g to 9 m 2 / g, as measured according to ASTM C1274.

[0361] The purity of the zirconia powder starting material is typically higher than 99.8%, preferably higher than 99.9%, preferably higher than 99.95%, preferably higher than 99.975%, preferably higher than 99.99%, and preferably higher than 99.995%. This corresponds to a total impurity content of 2000 ppm and lower, preferably 1000 ppm and lower, preferably 500 ppm and lower, preferably 250 ppm and lower, preferably 100 ppm and lower, preferably 50 ppm and lower, and preferably 25 ppm to 150 ppm, as measured using the ICPMS method disclosed herein. As is common in many commercially available zirconia powders, the zirconia used in the embodiments disclosed herein contains about 2 wt% to 5 wt% of a low amount of Hf. These purities of zirconia exclude Hf and any stabilizing compounds as disclosed in Table 1.

[0362] In an embodiment, the zirconia powder may comprise stabilizing compounds including at least one selected from the group consisting of yttrium oxide, lanthanum oxide (La2O3), cerium oxide (CeO2), magnesium oxide, samarium oxide (Sm2O3), calcium oxide, and combinations thereof. To form partially stabilized zirconia (PSZ), these stabilizing compounds may each be present in an amount of 0.5 mol% to 50 mol%, preferably 0.5 mol% to 30 mol%, preferably 0.5 mol% to 15 mol%, preferably 0.5 mol% to 10 mol%, preferably 1 mol% to 50 mol%, preferably 1 mol% to 30 mol%, preferably 1 mol% to 10 mol%, preferably 1 mol% to 5 mol%, and preferably about 3 mol%. To form stabilized zirconia (SZ), these stabilizing compounds may each be present in an amount greater than 6 mol% to about 45 mol%, preferably greater than 10 mol% to about 45 mol%, preferably greater than 25 mol% to about 45 mol%, preferably greater than 6 mol% to 30 mol%, preferably greater than 6 mol% to about 15 mol%, preferably greater than 8 mol% to 15 mol%. Table 1 provides additional guidance for stabilized or partially stabilized zirconia.

[0363] In certain embodiments, at least one second layer 102 is yttrium-stabilized and formed from a powder mixture comprising alumina and zirconia, wherein the zirconia is selected from the group consisting of yttrium-partially stabilized zirconia (PYSZ) or yttrium-fully stabilized zirconia (YSZ). Yttrium-partially stabilized zirconia (PYSZ) may be formed from a powder mixture comprising about 1 mol% to 10 mol% yttrium oxide, preferably 1 mol% to 8 mol% yttrium oxide, preferably 1 mol% to 5 mol% yttrium oxide, preferably 2 mol% to 4 mol% yttrium oxide, and preferably about 3 mol% yttrium oxide. Yttrium-stabilized zirconia (YSZ) may be formed from a powder mixture comprising about 8 mol% to about 15 mol% yttrium oxide, preferably 10 mol% to 15 mol% yttrium oxide, and preferably 12 mol% to 15 mol% yttrium oxide.

[0364] The alumina powder constituting the first powder mixture and the second powder mixture has the powder characteristics disclosed below.

[0365] The d10 particle size of the alumina powder used as a starting material according to an embodiment of the present disclosure is preferably 0.1 μm to 0.5 μm, preferably 0.1 μm to 0.4 μm, preferably 0.1 μm to 0.3 μm, preferably 0.2 μm to 0.5 μm, preferably 0.3 μm to 0.5 μm, preferably 0.4 μm to 0.5 μm, preferably 0.1 μm to 0.2 μm.

[0366] The d50 particle size of the alumina powder used as a starting material according to an embodiment of the present disclosure is preferably from 2 μm to 8 μm, preferably from 2 μm to 7 μm, preferably from 2 μm to 6 μm, preferably from 3 μm to 8 μm, preferably from 4 μm to 8 μm, preferably from 5 μm to 8 μm and more preferably from 2.5 μm to 5 μm.

[0367] The d90 particle size of the alumina powder used as a starting material according to an embodiment of the present disclosure is preferably from 15 μm to 40 μm, preferably from 15 μm to 30 μm, preferably from 15 μm to 25 μm, preferably from 20 μm to 40 μm, preferably from 30 μm to 40 μm and more preferably from 20 μm to 30 μm.

[0368] The specific surface area of the alumina powder is generally from 4 m 2 / g to 18 m 2 / g, preferably from 4 m 2 / g to 14 m 2 / g, preferably from 4 m 2 / g to 10 m 2 / g, preferably from 4 m 2 / g to 6 m 2 / g, preferably from 6 m 2 / g to 18 m 2 / g, preferably from 6 m 2 / g to 14 m 2 / g, preferably from 8 m 2 / g to 18 m 2 / g, preferably from 10 m 2 / g to 18 m 2 / g, preferably from 8 m 2 / g to 10 m 2 / g, and preferably from 6 m 2 / g to 10 m 2 / g.

[0369] As measured using the ICPMS method, the purity of the alumina starting material is generally higher than 99.99%, preferably higher than 99.995%, preferably higher than 99.999% and preferably higher than 99.9995%. Accordingly, the impurity content of the alumina powder can be 100 ppm or less, preferably 50 ppm or less, preferably 25 ppm or less, preferably 10 ppm or less and more preferably 5 ppm or less.

[0370] The alumina and zirconia powders are mixed in a proportion such that the zirconia is present in an amount of 10% to 30%, preferably 10% to 25%, preferably 10% to 20%, preferably 15% to 25%, preferably 20% to 25% and preferably 15% to 20% by volume of at least one second layer 102 (upon sintering) of the multi-layer sintered ceramic body.

[0371] The powder of at least one of alumina, partially stabilized zirconia, and stabilized zirconia is combined to prepare a second powder mixture, which can be carried out according to the materials and methods disclosed in step a) of the method.

[0372] Step c) of the method disclosed herein includes combining alumina, yttrium oxide, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia to prepare at least one third powder mixture. The at least one third powder mixture may contain alumina in an amount greater than 43% to 92.5% and less, yttrium oxide in an amount of 1% to 56% and less, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia in an amount of 0.4% and greater to 40%, each by weight of the at least one third powder mixture. Preferably, as measured according to ASTM C1274, the at least one third powder mixture has about 1 m 2 / g to 18 m 2 / g, preferably about 1 m 2 / g to about 14 m 2 / g, preferably about 1 m 2 / g to about 10 m 2 / g, preferably about 1 m 2 / g to about 8 m 2 / g, preferably about 2 m 2 / g to about 18 m 2 / g, preferably about 2 m 2 / g to about 14 m 2 / g, preferably about 2 m 2 / g to about 10 m 2 / g, preferably about 3 m 2 / g to about 9 m 2 / g, preferably about 3 m 2 / g to about 6 m 2SSA per / g. In a preferred embodiment, at least one third powder mixture may comprise about 73% alumina, about 6% yttria, and about 21% of at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia, each by weight of the at least one third powder mixture. In a further preferred embodiment, at least one third powder mixture comprises about 73% alumina, about 6% yttria, and about 21% of 3 mol% yttria partially stabilized zirconia, each by weight of the at least one third powder mixture. At least one third powder mixture forms at least one third layer 103 having multiple phases upon sintering, the multiple phases comprising YAG, alumina, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia. In other embodiments, at least one third powder mixture may form the YAG phase in batches upon sintering and thus comprises about 43 wt% alumina and 57 wt% yttria. At least one third layer comprising YAG will have a CTE that matches that of at least one first layer comprising YAG within the disclosed ranges.

[0373] Yttria, alumina, and zirconia powders are combined to prepare a third powder mixture, which can be carried out according to the powder materials and methods disclosed in steps a) and b) of the method. The third powder mixture can be dry ball milled, roll blended, wet milled, wet tumble blended, and other similar blending methods known to those skilled in the art.

[0374] As previously disclosed, combining powders of at least two of alumina, yttria, magnesia, and at least one of unstabilized zirconia, partially stabilized zirconia, and stabilized zirconia to prepare at least a first powder mixture, a second powder mixture, and a third powder mixture (according to any one or two of steps a), b), and c)) can be carried out using powder preparation techniques such as wet or dry ball milling (axial rotation), wet or dry tumbling (upside down or vertical), jet milling, and combinations thereof. The use of these powder combining methods provides a high energy process for breaking down particles and agglomerates.

[0375] Step d) of the method disclosed herein includes calcining at least one of the first powder mixture, the second powder mixture, and the third powder mixture by applying heat to raise the temperature of at least one of them to a calcination temperature and maintaining the calcination temperature for calcination, thereby forming at least one of a first calcined powder mixture, a second calcined powder mixture, and a third calcined powder mixture. This step can be carried out such that moisture can be removed and the surface condition of the powder mixture is uniform before sintering. The calcination can be carried out at a temperature of 600 °C to 1200 °C, preferably 600 °C to 1100 °C, preferably 600 °C to 1000 °C, preferably 600 °C to 900 °C, preferably 700 °C to 1100 °C, preferably 800 °C to 1100 °C, preferably 800 °C to 1000 °C, and preferably 850 °C to 950 °C. The calcination can be carried out in an oxygen-containing environment for a duration of 4 hours to 12 hours, preferably 4 hours to 10 hours, preferably 4 hours to 8 hours, preferably 6 hours to 12 hours, preferably 4 hours to 6 hours. After calcination, at least one of the first powder mixture, the second powder mixture, and the third powder mixture can be sieved and / or tumbled and / or blended according to known methods to form at least one first calcined powder mixture, a second calcined powder mixture, and a third calcined powder mixture. Preferably, at least one of the first powder mixtures is calcined. The calcination may or may not cause a decrease in the specific surface area.

[0376] The first powder mixture may have a d10 particle size of 0.06 μm to 4 μm, preferably 0.08 μm to 4 μm, preferably 0.1 μm to 4 μm, preferably 0.2 μm to 4 μm, preferably 0.3 μm to 4 μm, preferably 0.4 μm to 4 μm, preferably 0.08 μm to 3 μm, preferably 0.08 μm to 2 μm, preferably 0.08 μm to 1 μm, preferably 0.5 μm to 3 μm, preferably 1 μm to 2 μm, preferably 1 μm to 3 μm.

[0377] The second powder mixture may have a d10 particle size of 0.075 μm to 0.4 μm, preferably 0.075 μm to 0.3 μm, preferably 0.075 μm to 0.2 μm, preferably 0.1 μm to 0.4 μm, preferably 0.1 μm to 0.3 μm, preferably 0.1 μm to 0.2 μm, and preferably about 0.2 μm.

[0378] The first powder mixture may have a d50 particle size of from 0.7 μm to 50 μm, preferably from 1 μm to 40 μm, preferably from 1 μm to 30 μm, preferably from 1 μm to 20 μm, preferably from 1 μm to 10 μm, preferably from 1 μm to 5 μm, preferably from 5 μm to 50 μm, preferably from 10 μm to 50 μm, preferably from 20 μm to 50 μm, preferably from 30 μm to 50 μm, preferably from 3 μm to 8 μm, preferably from 5 μm to 10 μm, and preferably from 6 μm to 15 μm.

[0379] The second calcined powder mixture may have a d50 particle size of from 1 μm to 100 μm, preferably from 1 μm to 80 μm, preferably from 1 μm to 60 μm, preferably from 1 μm to 40 μm, preferably from 10 μm to 100 μm, preferably from 20 μm to 100 μm, preferably from 30 μm to 100 μm, preferably from 20 μm to 80 μm, preferably from 20 μm to 60 μm, and preferably from 20 μm to 40 μm.

[0380] The first calcined powder mixture may have a d90 particle size of from 10 μm to 350 μm, preferably from 10 μm to 300 μm, preferably from 10 μm to 250 μm, preferably from 10 μm to 200 μm, preferably from 10 μm to 175 μm, preferably from 10 μm to 150 μm, preferably from 10 μm to 100 μm, preferably from 10 μm to 75 μm, preferably from 10 μm to 50 μm, preferably from 10 μm to 40 μm, preferably from 10 μm to 25 μm, preferably from 20 μm to 350 μm, preferably from 40 μm to 350 μm, preferably from 60 μm to 350 μm, preferably from 100 μm to 350 μm, preferably from 150 μm to 350 μm, preferably from 200 μm to 350 μm, preferably from 12 μm to 330 μm, preferably from 100 μm to 330 μm, preferably from 100 μm to 250 μm.

[0381] The second calcined powder mixture may have a d90 particle size of from 20 μm to 250 μm, preferably from 20 μm to 220 μm, preferably from 20 μm to 150 μm, preferably from 20 μm to 100 μm, preferably from 50 μm to 220 μm, preferably from 70 μm to 220 μm, preferably from 100 μm to 220 μm.

[0382] In certain embodiments, the higher temperature calcination conditions disclosed herein can result in the formation of crystalline phases and agglomeration of the calcined powder mixture, and thus can result in greater variability in the overall particle size distribution, and in particular can result in greater differences in the overall d50 and d90 particle sizes. In other embodiments, the lower temperature calcination conditions disclosed herein may not affect the particle size distribution of the calcined powder mixture relative to the starting materials, and thus the particle size distribution is within the same or a similar range as the starting powder materials. Variations between batches during calcination and the management of heat transfer can also contribute to variations in the particle size distribution. Accordingly, a wide range of particle size distributions, and in particular the d50 and d90 particle sizes of the powder mixture, can be produced by the calcination conditions disclosed herein.

[0383] As measured according to ASTM C1274, at least one first calcined powder mixture, second calcined powder mixture, and third calcined powder mixture can each have from about 1 m 2 / g to about 18 m 2 / g, preferably from about 1 m 2 / g to about 14 m 2 / g, preferably from about 1 m 2 / g to about 10 m 2 / g, preferably from about 1 m 2 / g to about 8 m 2 / g, preferably from about 2 m 2 / g to about 18 m 2 / g, preferably from about 2 m 2 / g to about 14 m 2 / g, preferably from about 2 m 2 / g to about 12 m 2 / g, preferably from about 2 m 2 / g to about 10 m 2 / g, preferably from about 3 m 2 / g to about 9 m 2 / g, and preferably from about 3 m 2 / g to about 6 m 2 / g of specific surface area (SSA).

[0384] The first calcined powder mixture can have a total impurity content of 5 ppm to 200 ppm, preferably 5 ppm to 150 ppm, preferably less than 100 ppm, preferably less than 75 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably less than 10 ppm, preferably less than 8 ppm, preferably less than 5 ppm, preferably 5 ppm to 50 ppm, preferably 5 ppm to 30 ppm, preferably 3 ppm to 20 ppm, based on the mass of the first calcined powder mixture.

[0385] Table 11 shows the ICPMS purity results of an exemplary first powder mixture prior to forming a polycrystalline YAG layer.

[0386] Table 11

[0387]

[0388] *N / A indicates elements present in the starting powders from which the powder mixture was formed.

[0389] Table 12 shows the ICPMS purity results of an exemplary first powder mixture prior to forming a spinel layer.

[0390] Table 12

[0391]

[0392] *N / A indicates elements present in the starting powders from which the powder mixture was formed.

[0393] Table 13 shows the ICPMS purity results of an exemplary first powder mixture prior to forming a yttrium oxide - zirconium oxide layer.

[0394] Table 13

[0395]

[0396] *N / A indicates elements present in the starting powders from which the powder mixture was formed;

[0397] For each of Tables 10 - 14, N / D indicates elements detected below the reporting limit of the ICPMS. The reported purity is the average of 5 batches of the powder mixture.

[0398] The second powder mixture may have a total impurity content of 5 ppm to 200 ppm, preferably 5 ppm to 150 ppm, preferably less than 100 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably 10 ppm to 100 ppm, preferably 10 ppm to 80 ppm, preferably 10 ppm to 60 ppm, preferably 10 ppm to 40 ppm, preferably 20 ppm to 80 ppm, preferably 30 ppm to 60 ppm, relative to the mass of the second powder mixture.

[0399] Table 14 shows the ICPMS purity results of an exemplary second powder mixture prior to forming at least one second layer 102.

[0400] Table 14

[0401]

[0402] The results in Table 14 are the average of 5 powder batches. As depicted in Table 14, the second powder mixture may contain an amount of magnesium oxide of about 5 ppm and lower, preferably 3 ppm and lower, as measured relative to the mass of the at least one second powder mixture. The powder mixtures containing alumina and at least one of stabilized zirconia and partially stabilized zirconia as disclosed herein do not contain or are substantially free of dopants and / or sintering aids as disclosed herein. Hf, Y, and Zr are not considered impurities, dopants, or sintering aids and are not listed in Table 14.

[0403] The starting powders comprising at least one first powder mixture and a second powder mixture have different characteristics, such as particle size and purity. Thus, the characteristics of the powder mixture, such as purity, may be higher than at least one of these starting powders individually due to combination with another starting powder that may have a higher purity.

[0404] Tables 10 to 14 indicate the extremely high purity (>99.99% relative to 100% pure powder) of at least one powder mixture that forms at least one crystalline phase of YAG, magnesium aluminate spinel, yttrium oxide, and zirconia (where zirconia is present in an amount of not less than 10 mol% and not more than 25 mol%) and alumina and zirconia (where the zirconia comprises at least one of stabilized zirconia and partially stabilized zirconia) in batches (upon sintering). As listed in these tables, each of these powder mixtures may contain an amount of iron (Fe) of less than 0.5 ppm, preferably less than 0.25 ppm, relative to the mass of the respective powder mixture.

[0405] Step e) of the method as disclosed herein includes separately disposing a first calcined powder mixture, a second calcined powder mixture, and a third calcined powder mixture within a volume defined by a tool set of a sintering apparatus to form at least one layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third ...

Claims

1. A multi-layer sintered ceramic body, the multi-layer sintered ceramic body comprising: At least one first layer containing polycrystalline YAG, wherein the at least one first layer containing polycrystalline YAG contains pores, and wherein the pores have a maximum size of 0.1 μm to 5 μm. At least one second layer containing alumina and zirconia, wherein the zirconia contains at least one of stabilized zirconia and partially stabilized zirconia, and wherein the at least one second layer contains zirconia in an amount of 10% to 30% by volume relative to the volume of the at least one second layer, and At least one third layer containing YAG, alumina, and zirconia. Wherein the at least one second layer is disposed between the at least one first layer and the at least one third layer. wherein when measured according to ASTM E228-17, the absolute value of the coefficient of thermal expansion (CTE) difference between any one of the at least one first layer, the at least one second layer, and the at least one third layer is from 0 to 0.75×10 -6 / °C, Wherein the at least one first layer, the at least one second layer, and the at least one third layer form an integral sintered ceramic body, and Wherein when measured using XRD, SEM, and image processing methods, the at least one first layer contains polycrystalline YAG in an amount of 98% to 99.9% by volume, and the balance contains at least one crystal phase selected from the group consisting of alumina, yttrium oxide, YAM, YAP, and combinations thereof.

2. The multi-layer sintered ceramic body according to claim 1, wherein the absolute value of the difference in coefficient of thermal expansion between any of the layers is from 0 to 0.7×10 -6 / °C.

3. The multi-layer sintered ceramic body according to claim 1, wherein the absolute value of the difference in coefficient of thermal expansion (CTE) between any of the at least one first layer, the at least one second layer, and the at least one third layer is maintained over the entire temperature range from 200 °C to 1400 °C.

4. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one first layer has a density of 4.47 g / cc to 4.56 g / cc when measured according to ASTM B962-17.

5. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one first layer has a Sa of 0.0005 μm to 2 μm when measured according to ISO standard 25178-2-2012 or a Sz of 0.3 μm to 5 μm when measured according to ISO standard 25178-2-2012.

6. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one second layer contains partially stabilized zirconia.

7. The multi-layer sintered ceramic body according to any one of claims 1 to 3, the multi-layer sintered ceramic body having a maximum size of 100 mm to about 625 mm, wherein the term "about" when used in combination with a number allows a difference of plus or minus 10%.

8. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one second layer contains about 16 vol% zirconia relative to the volume of the at least one second layer, wherein the term "about" when used in combination with a number allows a difference of plus or minus 10%.

9. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one first layer containing polycrystalline YAG contains pores, and wherein the pores have a maximum size of 0.1 μm to 1 μm when measured using SEM.

10. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein when measured using SEM, the at least one first layer containing polycrystalline YAG has a cumulative pore distribution of about 2μm 2 / mm 2 to about 800μm 2 / mm 2 and the term "about" used in conjunction with a number allows for a plus or minus 10% variation.

11. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein when measured using SEM, the at least one first layer containing polycrystalline YAG has a porosity of 0.0005% to 2% by surface area percentage.

12. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein when measured using the ICPMS method, the at least one first layer containing polycrystalline YAG has a total impurity content of less than 5 ppm to 50 ppm relative to the mass of the at least one first layer.

13. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein when measured according to ASTM B962-17, the at least one second layer has a density of 4.19 g / cc to 4.46 g / cc.

14. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one second layer contains 16% by volume of zirconia and has a density of about 4.32 g / cc when measured according to ASTM B962-17, wherein the term "about" used in conjunction with a number allows a difference of plus or minus 10%.

15. The multi-layer sintered ceramic body according to claim 14, wherein when measured according to ASTM E228-17, the at least one second layer has a coefficient of thermal expansion (CTE) in the temperature range of 200 °C to 1400 °C of 6.98×10 -6 / °C to 9.26×10 -6 / °C.

16. The multi-layer sintered ceramic body according to claim 14, wherein when measured according to ASTM D150, the at least one second layer has a dielectric loss of 7×10 - or less at a frequency of 1 MHz and ambient temperature.

17. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein when measured using the ICPMS method, the at least one second layer has a total impurity content of 5 ppm to 200 ppm relative to the mass of the at least one second layer.

18. The multi-layer sintered ceramic body according to any one of claims 1 to 3, wherein the at least one first layer has a thickness d1, the at least one second layer has a thickness d2, and the at least one third layer has a thickness d3, wherein the thickness d2 of the at least one second layer is 60% to 85% of the total thickness of the at least one first layer, the at least one second layer, and the at least one third layer.

19. A method for preparing the multi-layer sintered ceramic body according to claim 1, the method comprising the following steps: a. Combining powders containing yttrium oxide and alumina to prepare a first powder mixture; b. Combining alumina powder with at least one of partially stabilized zirconia powder and stabilized zirconia powder to prepare a second powder mixture; c. Combining alumina powder, yttrium oxide powder with at least one of unstabilized zirconia powder, partially stabilized zirconia powder, and stabilized zirconia powder to prepare at least one third powder mixture; d. Calcining at least one of the powder mixtures by applying heat to raise the temperature of at least one of the first powder mixture, the second powder mixture, and the third powder mixture to a calcination temperature and maintaining the calcination temperature to perform calcination, thereby forming at least one of a first calcined powder mixture, a second calcined powder mixture, and a third calcined powder mixture; e. The first powder mixture, the second powder mixture, and the third powder mixture are separately disposed within an internal volume defined by a tool set of a sintering apparatus to form at least one layer of the first powder mixture, at least one layer of the second powder mixture, and at least one layer of the third powder mixture, and a vacuum condition is created within the volume, wherein the tool set includes a die, the die includes side walls, the side walls include an inner wall and an outer wall, wherein the inner wall has a diameter defining the internal volume capable of receiving the powder; and an upper punch and a lower punch operatively coupled to the die, wherein each of the upper punch and the lower punch has an outer wall, the outer wall defining a diameter smaller than the diameter of the inner wall of the die, whereby when at least one of the upper punch and the lower punch moves within the internal volume of the die, a gap is defined between each of the upper punch and the lower punch and the inner wall of the die, wherein the gap is 10 μm to 100 μm wide; f. While heating to a sintering temperature, pressure is applied to and the layers of the first powder mixture, the second powder mixture, and the third powder mixture are sintered to form the multi-layer sintered ceramic body, wherein the at least one layer of the first powder mixture forms at least one first layer, the at least one layer of the second powder mixture forms at least one second layer, and the at least one layer of the third powder mixture forms at least one third layer; and g. The temperature of the multi-layer sintered ceramic body is reduced, wherein the at least one first layer contains polycrystalline YAG, and the at least one second layer contains alumina, wherein the alumina contains at least one of stabilized zirconia and partially stabilized zirconia, and the at least one third layer contains YAG, alumina, and zirconia, wherein the at least one second layer is disposed between the at least one first layer and the at least one third layer.

20. The method according to claim 19, wherein when measured using ICPMS, the first powder mixture, the second powder mixture, and the third powder mixture have a combined total impurity content of 200 ppm or less.

21. The method according to claim 19 or 20, wherein the second powder mixture contains from 15% to 34% by weight, relative to the weight of the second powder mixture, of partially stabilized zirconia or stabilized zirconia.

22. The method according to claim 19 or 20, wherein when determined by an x-ray diffraction method, the first powder mixture, the second powder mixture, and the third powder mixture are crystalline.

23. The method according to claim 19 or 20, wherein the second powder mixture contains partially stabilized zirconia.

24. The method according to claim 19 or 20, wherein the second powder mixture contains yttria partially stabilized zirconia.

25. The method according to claim 19 or 20, wherein the second powder mixture comprises 3 mol% yttria partially stabilized zirconia.

26. The method according to claim 19 or 20, wherein the pressure applied to the at least one first layer, the at least one second layer, and the at least one third layer of the first powder mixture, the second powder mixture, and the third powder mixture is from 5 MPa to 100 MPa.

27. The method according to claim 19 or 20, wherein the temperature of the calcination step is from 600 °C to 1200 °C.

28. The method according to claim 19 or 20, wherein the sintering temperature is from 1000 °C to 1700 °C.

29. The method according to claim 19 or 20, the method further comprising the steps of: h. Optionally annealing the multi-layer sintered ceramic body by applying heat to raise the temperature of the multi-layer sintered ceramic body to an annealing temperature; and i. Lowering the temperature of the annealed multi-layer sintered ceramic body.

30. The method according to claim 19 or 20, the method further comprising the steps of: j. Machining the multi-layer sintered ceramic body to form multi-layer sintered ceramic components in the shape of windows, lids, dielectric windows, RF windows, rings, focusing rings, machining rings, deposition rings, nozzles, injectors, gas injectors, shower heads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESC), and positioning disks.

31. A multi-layer sintered ceramic body prepared by the method according to any one of claims 29 to 30.

32. The multi-layer sintered ceramic body according to claim 31, the multi-layer sintered ceramic body having a maximum dimension of 100 mm to about 625 mm, wherein the term "about" when used in combination with a number allows a variation of plus or minus 10%.

Citation Information

Patent Citations

  • Programmable System and Method of Spark Plasma Sintering

    US20100156008A1

  • Method and system for clamping semiconductor wafers

    US5262029A

  • Apparatus for hot wall reactive ion etching using a dielectric or metallic liner with temperature control to achieve process stability

    US5798016A

  • Low voltage electrostatic clamp for substrates such as dielectric substrates

    US5838529A

  • Plasma processing apparatus

    US5911852A